Parametric calibration of a thermo-hydro-mechanical coupled swelling model for viscous soil using Bayesian methods - Changhong Wang; Ting He; Yongqing Wei; Haidong Zhang; Fei Li (European Journal of Environmental and Civil Engineering, 2026)

Development of a sandwich ELISA analysis platform using dual nanobodies for quantitative detection of bovine lactoferrin in dairy products - Li Cao; Ting Zhang; Yan-Ping Li; Qinghua He; Zhui Tu (International Dairy Journal, 2026)

Metabolomics-driven insights into the multi-target antibacterial mechanisms of 2-methoxycinnamaldehyde against Bacillus cereus and its application in pork preservation - Xinrui Li; Renjin Xiang; Yuhan Tan; Fei He; Ting Huang; Jiahao Wang; Kai Yin; Xiaoshan Shi; Yanxiang Wang; Junming Tu; Xian Xia; Jingjing Li (Food Microbiology, 2026)

Thermo-mechanical behavior of medium sandstone under cryogenic conditions: Role of unfrozen water content - Bo Liu; Jie Zhang; Yanhui Han; Ting Li; Lulu He; Lei Gao; Shuhui Li (Cold Regions Science and Technology, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Hypoxia-preconditioned bone marrow mesenchymal stem cells alleviate acute liver failure in association with the VEGF/c-Met pathway - Mei-Mei Lan; Rui-Zhi Shi; Zhe-Yu Li; Wen-Jun Qiao; Yong-Juan Guan; Wen-Qiang He; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Single-cell transcriptomic profiling combined with Mendelian randomization illuminates molecular drivers of bladder cancer - Junrui He; Zhuoying Jiang; Shan Peng; Lijuan Peng; Zhongyou Xia; Ting Ma; Xiaojun Tan; Qiongxian Long; Ji Wu (Molecular Genetics and Genomics, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Sustainable vegetation restoration of degraded mines improves soil quality by mediating the activity and composition of phoD-harboring bacteria - Jieyu Dong; Ziyu Luo; Jinsong He; Taimoor Hassan Farooq; Xiaohong Wu; Jun Wang; Ting Liu; Yingchun Fang; Wende Yan; Hattan A. Alharbi; Yakov Kuzyakov (Gondwana Research, 2026)

Contrasting impacts of biodegradable and conventional microplastics on heavy metal bioavailability in soils: A multilevel meta-analysis - Xue-Dan Cui; Zheng-Xiao Jiang; Yi-Hao Mei; Ting-Ting He; Xiao Tan; Ai-Jun Lin; Gui-Lan Duan (Environmental Pollution, 2026)

Rationally tailoring defect levels in Prussian blue analogues for enhanced rubidium adsorption - Gan Li; Wanghai He; Qiang Li; Fei Xu; Jiazheng Qin; Ting Wang; Mingshan Yang; Xin Hu; Dahuan Liu (Desalination, 2026)

A crystallinity-switch strategy for in-situ encapsulating Pd nanoclusters toward selective conversion of CO2 - Zhao-Cheng Shi; Jing Li; Xue-Feng Zhang; Ming-Ming Wu; Zhonggao Zhou; Meng-Tian Zhang; Chun-Ting He (Chemical Engineering Journal, 2026)

Influence of the intrinsic properties of nanopipettes on sensing performance - Wenhao Ma; Rong Tian; Shixuan He; Shaoxi Fang; Bohua Yin; Yongjia Wang; Ting Weng; Wanyi Xie; Danqun Huo; Changjun Hou; Deqiang Wang (Chemical Engineering Journal, 2026)

CAMERA: A programmable CRISPR-gated logic system for high-fidelity assessment of Mycobacterium tuberculosis - Jiu Pu; Dan Bai; Yaoyi Zhang; Yiqi Zhang; Li Zhang; Yu He; You Wu; Na Yin; Zhe He; Shun Yao; Ting Xu; Yongchang Wu; et al. (Chemical Engineering Journal, 2026)

Dandelion-like Pd/Cu nanozyme with multi-enzyme activities: A colorimetric sensor array for PFAS discrimination - Hui-ting Hu; Xiao-mei Li; Wen-cai Jiang; Chen Ni; Yu-yang He; Guo-qi Zhang; Hao Yu; Zhi-Bo Hou (Analytica Chimica Acta, 2026)

A chromosome-level genome assembly and multi-omics analyses provide insights into the molecular basis of low-temperature tolerance in Coptodon zillii - Liming Luo; Liting Chen; Haotian Wu; Hengquan Zhao; Lingyu Kong; Kun Zhou; Yumeng Sun; Zhichang He; Xin Yan; Zhongbao Guo; Ting Huang; Yongju Luo; et al. (Aquaculture, 2026)

Integrated analysis of muscle proteomics and neurotransmitter-targeted metabolomics in Penaeus vannamei infected with Enterocytozoon hepatopenaei (EHP) - Zhipeng Yin; Yajie Tian; Chuanyu He; Fan Yang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Aquaculture, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Formation of post-traumatic and non-traumatic knee joint contracture: Role of macrophage polarization in joint capsule and skeletal muscle - Feng Wang; Fan Bai; Ting Zhou; He Liu; Ding-Jiang Wu; Yun Zhou; Wen Li (Tissue and Cell, 2026)

Identification and functional validation of a beta-amyrin synthase for Clinopodiside A biosynthesis in medicinal plant Clinopodium chinense - Qianlan Liu; Chun Liu; Zitong Tan; Yu Fu; Ting He; Yi Yuan; Yuling Tai (Plant Science, 2026)

Precursor signal identification of coal rupture based on deformation heterogeneity and acoustic emission in time and frequency domain - Xiangguo Kong; Xuguang Li; Ting Liu; Di He; Zhibo Zhang; Ali Muhammad (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Multi-objective optimization of a TetraSpar-type floating wind turbine considering motion performance and cost - Chuankai Zhao; Ting Cui; Guanghua He; Zhengxiao Luan; Chaogang Liu; Haobo Ma (Ocean Engineering, 2026)

Corrigendum to 'Magnetic and mineralogical evidence for mid- to late Holocene monsoon variability in sediments from Yuehu Lagoon, eastern China' [Palaeogeogr. Palaeoclimatol. Palaeoecol. 698 (2026) 113910] - Menghan Li; Kuang He; Zhaoxia Jiang; Junjie Wu; Ting Hao; Wenhui Li; Xiaohui Zhao; Hanlin Hao; Yuewei Hu; Haonan Song; Fenghui Li; Sanzhong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Sustainable water management in an upstream watershed under transboundary eco-compensation policy: a bi-level robust optimization model - Linhuan He; Yee Van Fan; Yuhong Shuai; Liming Yao; Petar Sabev Varbanov; Ting Pan (Journal of Hydrology, 2026)

Gradient sulfur-vacancy engineering of MoS2 for selective non-radical peroxymonosulfate activation: Toward enhanced interference resistance in complex water matrix - Xuexia Guo; Ting Li; Huinan Zhao; Wenbin Huang; Lu Zeng; Zhangnan Yao; Shuanghong Tian; Chun He (Journal of Environmental Chemical Engineering, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Integration of machine learning-predicted collision cross sections for the discrimination of flavonol 3-O- and 7-O-glycoside isomers - Xue-Chao Song; Xiongyuan Si; Ting He; Ruidong Zi; Yu Zhou; Wenzhi Yang (Food Chemistry, 2026)

Dual-metal-site MOF nanozyme with enhanced activity for highly sensitive colorimetric detection of Cr(VI) in dairy products - Mengyue Gao; Zhiheng Li; Mengjie Liu; Ting He; Xiaolu Su; Yueting Zhao; Zhiqiao Zou; Yanxing Yao; Fengmei Jin; Zhihao Li; Lihua Wang (Food Chemistry, 2026)

Interlocking architecture-enabled ultrasensitive iontronic pressure sensor based on [BMIM]BF4-functionalized sponge - Xiaohui Guo; Xiaomeng Yao; Bing Hu; Xinran He; Hongtao Tan; Yaqi Yu; Haining Wang; Jiashu Cao; Zhiyuan Liu; Zhangling Duan; Ting-Jung Lin; Yunong Zhao (Chemical Engineering Journal, 2026)

Toward reversible Zn electrode: A mechanistic review on interfacial designs in aqueous Zn metal batteries - Chi-Yu Lai; Ting-Yu Wang; Zi-Fan He; Yi-Ting Lu; Chi-Chang Hu (Chemical Engineering Journal, 2026)

Chemotaxonomic significance of dipeptides and flavonoids in the whole plants of Euphorbia dentata Michx - Ye Chang; Tian-Yi Chun; Xue Wen; Xiang-Ting He; Guo-Wei Zhang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Equivalent emissivity correction of the blackbody on-board MWRI-RM - Dong Ke-Song; Xing Rui-Xian; Bai Chuan; XU Jing; Meng Wan-Ting; He Jia-Kai; Jiang Li-Fei (International Journal of Remote Sensing, 2026)

A novel socioeconomic downscaling method by integrating multi-dimensional spatial proximity with multi-source remote sensing data - Wenke Li; Ting Hu; Linxin Li; Yinxia Cao; Wei He (International Journal of Remote Sensing, 2026)

MaizeStereo: 2D Gaussian splatting-driven stereo foundation model for in-field proximal 3D maize phenotyping - Ziang Niu; Siqi Liu; Yuan Gao; Ting Huang; Yong He; Zhengjun Qiu (Computers and Electronics in Agriculture, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Lake evolution and possible forcing mechanisms since the last Deglaciation in the Qaidam Basin, NE Tibetan Plateau - He Ma; Xueyun Ma; Yongli Wang; Zhifu Wei; Geng Wang; Ting Zhang; Wei He (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Magnetic and mineralogical evidence for mid- to late Holocene monsoon variability in sediments from Yuehu Lagoon, eastern China - Menghan Li; Kuang He; Zhaoxia Jiang; Junjie Wu; Ting Hao; Wenhui Li; Xiaohui Zhao; Hanlin Hao; Yuewei Hu; Haonan Song; Fenghui Li; Sanzhong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Complete genome sequence of a novel Pseudomonas sp. GW-45 isolated from Antarctic Ardley cove showing DMSP degradation capability - Yi-He Zhang; Yong-Qiang Hu; Zuo-Qi Wang; Chun-Yang Li; Ting Hu; Zhong Hu; Yin-Xin Zeng (Marine Genomics, 2026)

Transcriptome analysis provides molecular evidence for muscle growth regulation in Litopenaeus vannamei infected with Ecytonucleospora hepatopenaei (EHP) - Chuanyu He; Zhipeng Yin; Yajie Tian; Fan Yang; Zheng Cao; Cuixia Wang; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Journal of Invertebrate Pathology, 2026)

A synthetic microbial community for the enhanced removal of complex emerging pollutants from domestic wastewater - Ting Xu; Hui Yun; Yuru Zhao; Yue He; Siyu Chen; Ting Ma; Wenjie Zhang; Liang Peng; Xiangkai Li (Journal of Hazardous Materials, 2026)

Freeze-dried chocolate as a one-bite carrier for calcium, magnesium and vitamin D3: uniform codelivery with enhanced stability, instant disintegration and site-specific release - Qianqian Li; Lu Yang; Ting Xu; Yuhui Wang; Lulu Zhang; Juan Hao; Yuwei He; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2026)

Integrated effects of geographical origin, fruit color, and cultivation type on quality and bioactive properties of cherry tomato in China - Wanyue Hong; Ting Fan; Xudong Zhang; Qi Wang; Luping He; Chunmei Wei (Food Chemistry, 2026)

UEV1A attenuates MDA5-mediated antiviral immune response by reducing its ubiquitination and aggregation - Jiaxin Wang; Rongyao Sun; Ting Li; Houcheng Liang; Huan He; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Machine learning-optimized coarse-grained simulations reveal multicomponent solvent-regulated phase separation for precise control of porous polymers - Yun Hao Feng; Bo Zhi Chen; Shi Long Zhang; Chu Qi Wang; Yu Ting He; Yuan Gao; Jing-yi Kang; Ling Liang; Qiang Xu; Bin Du; Xin Dong Guo (Chemical Engineering Journal, 2026)

Nano-confined MXene/covalent organic framework photothermal bioreactors for efficient catalysis and temperature control - Chen-Xi He; Hui-Ting Li; Jia-Ying Chen; Zhen-Feng Zhang; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Bioresource Technology, 2026)

Capsicum oleoresin supplementation on growth performance, physiological and blood parameters, antioxidant, and immune responses of heat-stressed lambs - Yannan Ma; Zhixian Liu; Fan Wu; Lei Yang; Jiao Luo; Wen Chen; Zhaomin Lei; Pengjia He; Ting Liu; Shuzhen Song; Shuai Wang; Jianping Wu; et al. (Animal Feed Science and Technology, 2026)

Interdecadal intensification of late-spring precipitation over the Hengduan Mountains since the late 1990s - Meiying Zheng; Huizhi Liu; Shengyuan Liu; Haoran Li; Xiaoyang Liu; Lijun Xie; Guotao Zhang; Ting Yang; Fei Wang; Yunhao Gu; Junjie Zhao; Shuo He (Climate Dynamics, 2026)

Comprehensive Transcriptomics and Biochemical Analysis Provide New Insights into the Light Intensity Regulation Growth and Medicinal Quality of Dendrobium nobile - Ting Li; Haolin Liu; Yijun Fan; Hui Wang; Linlong Xu; Siyu He; Jie Ma; Junlan Wu; Chunhong Mou; Meng Zhao; Li Chen; Xuyang Liu; et al. (Journal of Plant Growth Regulation, 2026)

Multi-omics, machine learning, and molecular simulation identify CD44 as a candidate target in endocrine-disrupting chemical–associated thyroid cancer progression - Yifan Hu; Keshu Liu; Ting Chen; Zhizhen He; Shuang Li; Wu Hu; Qiuyang Fu; Xiong Chen (Molecular Diversity, 2026)

Early Neoproterozoic (∼900 Ma) tectonothermal events in the southwestern Yangtze Block: Evidence from monazite and rutile U-Pb geochronology - Xiao-Ying Cao; Jun-Ping Liu; Shu-Ting Wang; Yu-Chao Wang; Wei Gao; Yan Yang; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2026)

A multi-model dynamic adaptive fusion model for irregular wave forecasting - Menghua Li; Guanghua He; Zhengxiao Luan; Ting Cui; Dongrui jiang; Chaogang Liu; Chuankai Zhao (Ocean Engineering, 2026)

Axially coordinated cobalt single-atom membrane enabling electron-transfer–singlet oxygen synergy for highly selective micropollutant oxidation - Ting Liu; Zuoming Fan; Mingrui He; Mengfei Wang; Yulun He; Bo Han; Jun Ma (Journal of Hazardous Materials, 2026)

Gut dysbiosis and Escherichia coli-associated enrichment of antibiotic resistance genes in diarrheal yak calves - Ze Cao; Huanyu Gong; Huilin Qin; Ting Wei; Xiaoqiang He; Kairi Yang; Xiaowei Li; Yanwen Wang; Yunqiang Jia; Xi Lan; Wen He; Xiaoping Jing; et al. (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Wet-grinding carbonation of concrete slurry waste under low-concentration CO2 for preparing low-carbon foam concrete - Jin Yang; Hao Zheng; Maogao Li; Ying Su; Ting Li; Bohumír Strnadel; Tesfaye Alemu Mohammed; Xingyang He (Journal of Environmental Management, 2026)

Better representation of linear features in species distribution models: Mapping the distribution of the Scaly-sided Merganser (Mergus squamatus) - Yangsirui Zhang; Peizhong Liu; Lixing Gu; Li Wen; Ying He; Zijian Wang; Liangjun Zhou; Ting Lei; Cai Lu; Qing Zeng; Guangchun Lei (Journal of Environmental Management, 2026)

A Global Meta-analysis of Minerals in Human Milk: Quantifying Variations by Lactation Stage, Geography, and Analytical Method - Nan Li; Ting Li; Yuqi Huang; Liufeng Zheng; Jian He; Sufang Duan; Jing Li; Zeyuan Deng (International Dairy Journal, 2026)

Hypoallergenic casein peptides derived from strain–enzyme combined hydrolysis attenuate allergic immune responses and modulate gut microbiota in mice - Xiaomei Zhang; Minting Rong; Jinlan Xie; Ting Wang; Zhigui He; Aiying Xu; Xiaomeng Wu; Haizhu Wu (International Dairy Journal, 2026)

Blending with quinoa flour enhances the quality of fish balls: A natural strategy for inhibiting freeze-thaw deterioration - Jiebin Cai; Hailin Zheng; Yufeng Lin; Jiyuan He; Wei Deng; Zexuan Zheng; Binxiong Liu; Yanqiong Chen; Ting Fang (Food Chemistry, 2026)

Maternal Bifidobacterium bifidum BD-1 supplementation during late gestation modulates offspring gut microbiota succession and responses to DSS-induced acute colitis in a delivery-mode-dependent manner - Chenrui Peng; Chang Lu; Xiaoting Li; Lunpu Zhang; Yao Zeng; Xiaona Wu; Ting Wu; Fang He; Xi Shen (Food Bioscience, 2026)

The synthesis of alkaline earth metal-organic framework based on asymmetric triazine hexacarboxylic acid and iodine capture performance - Shao Bin Xu; He Qun Cai; Rong Huo; Ting Zhang; Jing Jin; Yong Heng Xing; Feng Ying Bai (Environmental Research, 2026)

Iodine vacancy-engineered BiOI steering selective singlet oxygen generation for high-flux antibiotic degradation with peroxyacetic acid activation - Yuchen Chu; Ting Zhou; Yuxi Zeng; Siying He; Jiawei Yue; Wenjun Wang; Yang Yang; Ziwei Wang; Fanzhi Qin; Hongda Liu; Xiaoming Li; Jie Liang; et al. (Chemical Engineering Journal, 2026)

Innovative technologies and future perspectives in tumor microbiomics - Wan-Ting He; Xiaofang Xing; Fei Wang; Le Li; Ye Cheng; Gang Yao (Science China Life Sciences, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

Portable Upper-limb Muscle Tone Assessment by Integrating Multi-sensor Signals - Yue Zhang; Ying Zheng; Hao ShangGuan; Ting Chen; Wan-Zhu Wang; Ya-Lan Wang; Peiqiang Lin; Bingwei He; Wenyao Hong; Xin-Yuan Chen (Annals of Biomedical Engineering, 2026)

Integrated Transcriptomic and Proteomic Analysis Reveals the Immune Response of Largemouth Bass ( Micropterus salmoides ) to Aeromonas hydrophila Infection - Fuyan Chen; Shuiping Wen; Xuehai He; Aiying Lei; Ting Huang; Yushan Wu; Honglian Tan; Youyong Liang; Xiaohua Lu; Meizhen Su; Jianbin Li; Xianhua Ouyang (Journal of Fish Diseases, 2026)
Largemouth bass ( Micropterus salmoides ) is an economically important freshwater fish species in China that is frequently affected by disease outbreaks caused by Aeromonas hydrophila . This study employed an integrated transcriptomic and proteomic approach to investigate the response of the liver in largemouth bass at 72 h post‐infection with A. hydrophila via intraperitoneal injection. We identified differentially expressed genes (DEGs; 2136 upregulated and 200 downregulated) and differentially expressed proteins (DEPs; 1683 upregulated and 1817 downregulated). Functional enrichment analysis indicated that the upregulated DEGs/DEPs were significantly involved in immune and inflammatory responses, encompassing pathways, such as TNF signalling, NF‐kappa B signalling, complement and coagulation cascades and B cell receptor signalling, while the downregulated DEGs/DEPs were primarily associated with metabolic processes, especially lipid metabolism. Integrated transcriptomic and proteomic analysis identified 420 correlated DEG/DEP pairs, among which 154 were consistently upregulated and 19 consistently downregulated. The upregulation of eight key immune‐related DEG/DEPs, including complement components (C1q, C7b, C1r‐A), MYD88 and BCL10, was verified by RT‐qPCR. Collectively, these findings provide valuable insights into the molecular basis of immune defence against A. hydrophila in largemouth bass and identify potential immune‐related biomarkers that may be useful in the development of effective prevention and control strategies.

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

Distribution and Evolution of Net Carbon Sink in Chinese Sugarcane Industry - Yuan Xie; Qibin Wu; Ting He; Peiting Hong; Xinyi Chen; Niandong Chen; Youxiong Que (Sugar Tech, 2026)

Effects of Different Dietary Inclusion Levels of Soybean Meal Supplemented with Crystalline Amino Acids on Mineral Deposition in Different Tissues of Weaned Piglets - Luqi Cai; Ting Yao; Liuqin He; Yulong Yin; Tiejun Li (Biological Trace Element Research, 2026)

Microbiome immune crosstalk in Sjögren’s syndrome: mechanistic insights and translational perspectives - Xiang-Yu Qi; Meng-Yuan Wang; Tian-Chi Wei; Fu-Biao Shao; Shu-Han Liu; Ding Han; Jing-Wen Cheng; Yun-He Zhao; Lei Shi; Jing Luo; Ting Cheng; Sheng-Xiao Zhang (Immunologic Research, 2026)

Rockburst mitigation by microwave destressing in a deep drill-and-blast tunnel: thermal–damage–stress evolution with a slotted-wall coaxial applicator - Yuntan Ao; Xia-Ting Feng; Shiping Li; Xiaojun Zhang; Juan He; Tianyang Tong; Yifan Zhang; Feng Lin (Tunnelling and Underground Space Technology, 2026)

NPY-Y2R driven neuroimmune signaling as a potential therapeutic target for trigeminal neuralgia: clinical and experimental evidence - Zi-Le He; Chao Xu; Qi-Fan Yang; Cong-Zhou Han; Ting Wu; Yu-Qing Xu; Yun-Ze Liu; Liang-Yu Ni; Si-Qi Jia; Tang-Yu Zhang; Yun Wang; Yi Feng (Science Bulletin, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Near-freezing temperature storage delays postharvest lignification and senescence of water bamboo shoot by regulating ROS metabolism and lignin biosynthesis pathway - Chenxia Liu; Jinglin Zhang; Hui He; Qiankun Wang; Chunfang Wang; Longshen Wang; Xiao Wang; Bingjie Chen; Yuemei Zhang; Yi Zhang; Ting Min; Yongjin Qiao; et al. (Postharvest Biology and Technology, 2026)

PM2.5-bound organophosphate esters and childhood attention-deficit hyperactivity disorder symptoms: A population-based study from China - Chu Chu; Xuan Liu; Yan-Xu Chen; Jia-Xiang Dong; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Xia Liang; Yang Zhou; Muhammad Amjad; Yan Yang (NeuroToxicology, 2026)

Revisiting familial aggregation of prostate cancer within the 3D framework of genetics-epigenetics-environment - Kunshan Shi; Baotai Liang; Ting He; Dongfang Jiang (Mutation Research - Reviews in Mutation Research, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Unveiling the antioxidant potential of a Laetiporus sulphureus peptide fraction: from Nrf2/HO-1-mediated cytoprotection to in silico screening of novel candidates - Jiyuan He; Huilin Chen; Zhaonan Wei; Yuxin Xu; Shengrong Liu; Qi Wei; Ting Fang (Food Chemistry, 2026)

First-trimester profiling of maternal plasma metals and vitamins in relation to gestational hypertension - Ting Wu; Tao Li; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Environmental Research, 2026)

Long-term stability and environmental safety of in-situ stabilization combined with micro-fertilization for cadmium mitigation in a soil-rice system: A four-year field experiment - Liqin He; Ziyao Li; Min Nie; Ting Li; Yuepeng Yin; Zhihong Guo; Jiufang Du; Jibin Yin; Taolin Zhang; Changfeng Ding (European Journal of Agronomy, 2026)

Electronic tuning of δ-MnO2 via interlayer Ag+ for efficient ozone decomposition under humid conditions - Ting Li; Zhongyu Wang; Xinyao Lei; Yuyan He; Minghao Shi; Mingjia Zhang; Shule Zhang; Qin Zhong (Chemical Engineering Journal, 2026)

Covalent organic frameworks membrane with gradient hydrophilic channel for moisture-enabled electric generation - Jun Zhang; Jing-Dong Feng; Ruo-Meng Zhu; Yong Liu; Yu-Ou He; Yu-Ting Que; Shuai Geng; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

Unveiling the electronic promotion effect of La in PdLa/In2O3 for boosting furfural highly selective hydrogenation to furfuryl alcohol at room temperature - Junyuan Xu; Jiani He; Yu Fang; Junliang Liao; Ting Xiong; Luna Ruan; Weizhen Wang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2026)

Correction: Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Response of greenhouse gas emissions, nitrogen loss and microbial communities to the presence of conventional and biodegradable microplastics in soil - Wenxu Li; Mengxiao Li; Jiaju He; Zhenyu Huang; Jian Zeng; Christopher W.N. Anderson; Minghua Zhou; Cheng Zhang; Xuesong Gao; Di Zhao; Ting Lan (Applied Soil Ecology, 2026)

Optimized Nitrogen Reduction Enhances Biomass Accumulation and Nitrogen Uptake of Maize–Soybean Intercropping Systems by Modulating Root Morphological Plasticity and Rhizosphere Enzymatic Activities - Ting Li; Jiao Wu; Liang He; Le Kang; Rina Wu; Yun Xiang; Jianmin Li (Journal of Soil Science and Plant Nutrition, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Amino acid and appendicular skeletal muscle mass insufficiency are associated to cognitive decline in Chinese population - Ting Tang; Shuxian Zhang; Yanni Pu; Siquan Li; Bin Jiang; Huiting Liang; Kunmu Zheng; Yan Zheng; He Huang; Jin Li; Xiaodong Pan (GeroScience, 2026)

Redefining PHOX2B-Related Neurodevelopmental Disorders as Circuitopathies: A New Paradigm in Autonomic Network Medicine - Zixu Zhang; Shengru Hu; Yaxuan Chen; Ting He; Wei Xie; Mingdao Mu (Neuroscience Bulletin, 2026)

Four new cysteine derivatives with cytotoxic activity from Poecilobdella manillensis - Qingqing Fan; Peixing He; Hang Xiao; Juan He; Ting Wang; Zhenbei Lan; Feng Tian; Jianyuan Tang; Li Ma (Phytochemistry Letters, 2026)

Effect of platform roll motion on aerodynamic performance of floating offshore wind turbine under yawed conditions - Guanghua He; Haobo Ma; Zhengxiao Luan; Chuankai Zhao; Ting Cui; Ronghua Zhu; Hassan Ghassemi (Ocean Engineering, 2026)

Experimental study on flow field characteristics around a novel composite enclosure aquaculture facility module under steady current conditions - Meng He; Ting Tan; Qian Gu; Zhuowei Zhou; Wenbo Gao; Wenyuan Wang; Ningchuan Zhang; Quanke Su (Ocean Engineering, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Bmal1 regulates hippocampal oxidative damage in cognitive memory impairment induced by artificial light at night in mice - Ting Lei; Jie Xia; Huiying Du; Dandan Xu; Miao He; Wei Liu; Hui Hua; Tianyao Yang (Journal of Photochemistry and Photobiology B: Biology, 2026)

High-pressure de-sublimation for enhanced cryogenic CO2 capture in LNG production from natural gas with high CO2 content - Ting He; Zijian Xiong; Yiwen Tian; Shuyang Huang; Jiatong Jiang (Journal of Cleaner Production, 2026)

Hydro-mechanical-chemical coupling model and migration law for arsenic pollution in soil of industrial land - Ting He; Changhong Wang; Yongqing Wei; Baolin Hu (Journal of Environmental Sciences, 2026)

Lanthanum-modified biochar for dual removal of particulate/dissolved phosphorus in agricultural runoff: Performance and reuse as slow-release fertilizer - Ting Chen; Jiayi Lu; Fenghao Lin; Zhiqiang Chen; Junjie Wei; Jie He; Ying Wang; Xiujuan Tang; Jun Yin (Journal of Environmental Sciences, 2026)

Risk assessment, source apportionment and driving mechanism of soil heavy metals in coal mining areas of Xinjiang, China - Xin He; Fei Zhang; Ting Zhou; Boyu Wang; Xuan Zhang; Xiangyu Liu; Zia Ahmed; Mou Leong Tan; Ziheng Feng; Zhihui Li; Xu Ma (Gondwana Research, 2026)

Electronic structure modulation induced by synergistic interaction of CQDs and iron atom active sites for efficient direct coal liquefaction - Wei Song; Xin Wen; Chunrong He; Xinyue Chen; Ting Wang; Xue Wang; Kaiyu Liu; Penggao Liu (Fuel, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

From selection to design: Reshaping aptamer discovery with artificial intelligence - Xin Yang; Shijian Ding; Meishen Ren; Huarui Zhang; Xiaohui Tao; Ning Zhang; Yihao Zhang; Hewen Jiange; Yufei Pan; Shanshan Yao; Luyao Wang; Yuan Ma; et al. (Chemical Engineering Journal, 2026)

Preparation, properties of bond energy-driven LKCC sequential drug-releasing hydrogel and its application in biofilm-infected wound repair - Jiangchuan He; Huan Wang; Yunhe Zheng; Yu Huang; Ting Wang; Hanchao Zhou; Kailai Liu; Yuchen Zhang; Jinpeng Wen; Jingya Qu; Pengchong Wang; Ling Liu; et al. (Chemical Engineering Journal, 2026)

Engineering oxygen vacancies in Ni/CeO2-nanorods via MOF templating for high-efficiency photothermal CO2 hydrogenation - Xiong Bai; Yuqi Wu; Yuan Sun; Xiaolei Guo; Yongkai Niu; Ting Meng; Hongwei Zhang; Jinlu He (Chemical Engineering Journal, 2026)

Janus structured magnetic MOFs-polyarylether nitrile/MXene composite films with gradient interfaces for electromagnetic interference shielding and thermal management - Yunfeng Guo; Jiabin Hu; Xin Sun; Ting Zhang; Shaoqian Zhou; Liang He; Hongbo Shen; Lifen Tong; Shuning Liu; Xiaobo Liu (Chemical Engineering Journal, 2026)

Active site-directed tandem catalysis on Pt-loaded nitrogen-rich carbon for driving piezo-synthesis of hydrogen peroxide and in-situ utilization for emerging contaminants removal - Huinan Zhao; Ting Li; Wei Liu; Kaiwen Wang; Yanhong Lu; Lu Zeng; Jia He; Lingling Hu; Chun He (Chemical Engineering Journal, 2026)

Flexible tactile sensing systems: Material innovations, fabrication strategies, and intelligent applications in human-machine interfaces - Xingfeng Zhao; Yangyang Pei; Maomao He; Fangli Wang; Ting Liu; Shoujia Zhu; Xiaoyan Li; Yue Li; Bin Liu; Hongjian Zhang; Linghai Xie; Wei Huang (Chemical Engineering Journal, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Boron and Selenium Combine to Alleviate Cadmium Stress and Improve Quality and Yield of Cherry Tomatoes - Ting Hong; Xuanxuan Liu; Zhongqun He; Yanmei Qin; Kaiyue Liu; Shaobo Cheng; Lihong Su; Dalong Shao; Xin Guo; Xiaoting Zhou (Journal of Plant Growth Regulation, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Sea Spray Aerosol Generation Techniques and Their Influence on Heterogeneous Chemistry - Xingchen Yang; Yiming Huang; Ting Lei; Yucong Guo; Xiang He; Maofa Ge; Weigang Wang (Aerosol Science and Engineering, 2026)

Structural decomposition enables multi-omics dissection of common and organ-specific aging - He Huang; Yi Li; Qinglin Song; Liyun Yuan; Yuqi Yang; Minwei Zhu; Renliang Sun; Yue Hu; Chenyihang Xiong; Ting Ni; Yun Liu; Andrés Ruiz-Linares; et al. (Science China Life Sciences, 2026)

Numerical modelling of local scour around pile foundations: A hydrodynamic–geotechnical review - Jiujiang Wu; Kunyong He; Ting Yang (Marine Georesources & Geotechnology, 2026)

Distribution and transport of trace organic contaminants from land to the coastal sea - Shi-Jie Lv; Ting Pan; Rui Tang; Jun-Rong Liang; Hui He; Lei Mai (Marine Pollution Bulletin, 2026)

Synergistic nitrogen removal by robust heterotrophic nitrification-aerobic denitrification and substantial assimilation in a novel Zobellella sp․ - Shun Yao; Chuxiao Hu; Xuan Ou; Qi Xiu; Honglin He; Yahan Hou; Xinrui Zhang; Ting Ma; Jidong Gu; Wenjie Xia (Water Research, 2026)

Biocontrol of tobacco bacterial wilt by Bacillus velezensis Y19: insights into chemotaxis, competition and antagonism - Yajie Hu; Xiaolan Yang; Huiping Wu; Qunling Li; Guangxiong Xiao; Feng Wu; Feng Li; Zihua He; Xiaoxing Lin; Ting Ding (Physiological and Molecular Plant Pathology, 2026)

Nonlinear hydrodynamic response of a horizontal cylinder near the free surface based on a time-varying Morison coefficient model - Ting Cui; Xiaolei Shang; Wenkai Huang; Chuankai Zhao; Pengfei Liu; Hangwei Zhang; Zhengxiao Luan; Guanghua He (Ocean Engineering, 2026)

A review of hydrodynamic response and mitigation strategies of floating offshore wind turbines under extreme conditions - Guanghua He; Chuankai Zhao; Ting Cui; Zhengxiao Luan; Chaogang Liu; Runhua He (Ocean Engineering, 2026)

Waste-derived elastic carbon catalysts for integrated CO2 capture and cycloaddition to cyclic carbonates - Ting Wang; Zhipeng Ren; Wenyu He; Fan Zhang; Kyung Hoon Min; Byeongseok Kim; Sang Eun Shim; Denian Li; Yingjie Qian; Haoran Yuan (Journal of Hazardous Materials, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Boron-Doped Co3O4/CoMoO4 heterostructure on nickel foam as a robust bifunctional catalyst for efficient overall water splitting - Zheng Yang; Zeyang He; Vadim Efimov; Feitao Fan; Kuzmin Anton; Ting Bian; Shitan Yan (Fuel, 2026)

Inhibitory effect of pulsed electric field pretreatment on acrylamide formation in air-fried French fries and its mechanism - Jian Li; Yue-Wei Huang; Yi-Tong Li; Shi-Yin Luo; Wei-Yan Xiong; Jin-Hua Wang; Jun-Hu Cheng; Ting-Shi He; Xin-An Zeng (Food Research International, 2026)

A high-performance LaSA-Co MAs catalyst derived implantable flexible electrochemical sensor for endogenous dopamine detection - Binqi He; Jiawei Li; Qianzuo Liu; Xinyue Xiang; Sifan Sun; Haoran Yang; Guosheng Cheng; Maiyong Zhu; Ying Hao; Ting Zhang; Tie Li (Chemical Engineering Journal, 2026)

Manipulating non-radical pathway preference in PMS-mediated phenolic degradation: Substituent-dependent catalyst-pollutant interfacial interaction over single-atom Fe-N-C - Fan Huang; Xianhu Long; Ting Li; Xuexia Guo; Lingling Hu; Huinan Zhao; Shuanghong Tian; Minhua Su; Chun He (Chemical Engineering Journal, 2026)

Fine structural features of polysaccharides and gut microbiota Co-regulate mucin O-glycosylation: Mechanisms and advances - Tong Zhao; Bo Zhang; Xuansheng Hu; Feng Jia; Qianna Zheng; Ting Lu; Siyuan Tan; Wuying Lang; Nianwu He; Xuhua Liang (Carbohydrate Polymers, 2026)

Stem Cell-Derived Exosomes Improve Neurological Dysfunction in a Rat Model of Moderate-to-Severe Cerebral Palsy - Tingting Peng; Huijuan Lin; Xiaoli Zeng; Yunlan Xie; Jie Luo; Lingjie Zhang; Shiya Huang; Zhiyi Ye; Xiaolin Guo; Wen Le; Mingtong Zhang; Wenhui Li; et al. (Stem Cell Reviews and Reports, 2026)

Microneedle-mediated delivery of hydroxypropyl-β-cyclodextrin-encapsulated Angelica sinensis (Danggui) essential oil for acne treatment: efficacy and mechanisms - Xiaoli Liu; Xiaojuan Li; Weijun He; Xiaoyu Han; Ting Xiao; Shiqi Guo; Yujie Jia; Liqun Lin; Ming Yang; Li Wang; Yuehong Xu (Drug Delivery and Translational Research, 2026)

Novel air gap membrane absorption structure for ammonium salt crystallization - Ting Zhou; Tao Sun; Jun Zhang; Qingyao He; Shuiping Yan (Water Research, 2026)

Magnetite in lunar impact glasses formed in the presence of water - Ting Li; Jieqi Xing; Yang Li; John A. Tarduno; Xuelin Zhu; Zelong Shi; Ye Zheng; Qian He; Ziying Li; Sheng He; Jun Zhong; Liumin Deng; et al. (Science Bulletin, 2026)

Multi-pathway antifungal mechanism of liquiritin against Fusarium sulphureum unlocks new green strategies for potato storage - Yaqin Tian; Yalan He; Ting Liu; Weixia Yang; Lichao Pan; Haiwei Ren; Tianyou Chen; Wenguang Fan (Postharvest Biology and Technology, 2026)

Fusing SWAN priors with tucker decomposition: A training-free framework for sparse wave field reconstruction - Shanxun Sun; Zhicong Yang; Zihan Cai; Lianfang Ye; Yanni Kou; Ting He (Ocean Engineering, 2026)

Nature-based sludge treatment systems: A review of constructed wetlands for sludge management - Ruoyi Zhang; Yaqian Zhao; Ting Wei; Jialu Wang; Zhiyu Yu; Chang He (Journal of Water Process Engineering, 2026)

Enhancing CO2-to-CO conversion over B-Cd Co-doped TiO2 through band structure tuning and photothermal synergy - Zhenyu Zhu; Lin Dong; Jiao-Jiao Shi; Mei-Xia Yang; Yue Tian; Lu-Ting Pan; Weitao Wang; Zhen-Hong He (Journal of Environmental Chemical Engineering, 2026)

Efficient nitrate and ammonium removal by psychrotolerant strain Pseudomonas yamanorum EH-G3 under acidic conditions - Qifeng Wu; Ruoyu Li; Ting Zou; Mei Li; Jianguo Zou; Tengxia He (Journal of Environmental Chemical Engineering, 2026)

Remediation of cadmium-contaminated soils by mercaptosuccinic acid-intercalated hydrotalcite: Effects on soil quality and cadmium accumulation in rice - Liqin He; Changfeng Ding; Min Nie; Ting Li; Ziyao Li; Taolin Zhang; Yurong Wang; Xingxiang Wang (Journal of Environmental Management, 2026)

Microwave melting of lunar regolith simulant in an unchambered environment: Insights from physical model experiments - Jia-Qi Lu; Zheng-Wei Li; Xia-Ting Feng; Cheng-Dan He; Yong-Jun Wang; Yang Zuo; Jin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Sibakazin: a novel black fly derived non-classical kazal protease inhibitor, targeting antiplatelet (P2Y12/GPVI) pathways without perturbing coagulation - Zhuorui Li; Yanmei He; Yan Shen; Miao He; Ting Lin; Jiayi Yang; Lixian Mu; Jing Wu; Hailong Yang (Insect Biochemistry and Molecular Biology, 2026)

Prioritizing alkylated and oxygenated PAHs over PAHs in freshwater organisms: Evidence from a Chinese freshwater lake - Shanshan Wang; Pengpeng He; Yangyang Liang; Xuemei Zhang; Yunzhi Yan; Zijiao Yuan; Ting Fang; Yuheng Xia; Xiaoguo Wu (Environmental Research, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Coupled Effects of Reservoir Level Fluctuations and Rainfall on Landslide Deformation Using InSAR and DEM Analysis - Liu Tie-biao; Liu Ming-quan; Luo Shi-lin; He Kun-lin; Yan Guang-zhi; Chen Guo-feng; Cao Su-ting (Geotechnical and Geological Engineering, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Potential contribution of terrestrial plants in the marginal sea food web: Evidence from in situ diet of the pelagic copepods in the South China Sea - Haoyang He; Lianming Zheng; Senjie Lin; Ling Li; Peihao Liu; Ting Li; Zhidi Gong (Marine Pollution Bulletin, 2026)

Membrane filtration as an effective alternative to manual isolation for soil tardigrade DNA extraction - Zi-Kai Liu; Weidong Chen; Ju-Pei Shen; Zi-Yang He; Hang-Wei Hu; Dan-Ting Yu; Ji-Zheng He (Soil Biology and Biochemistry, 2026)

TBCK syndrome pathogenesis: the TBCK-PPP1R21-C12orf4 complex regulating RAB5-dependent endo-lysosomal homeostasis - Yalan Wang; Xiayun Xu; Xiaotong Cao; Huiying He; Yue Qin; Ting Deng; Zhigang Zhang; Lingqian Wu; Chenji Wang; Hongyan Wang (Science Bulletin, 2026)

Comprehensive analysis of Clade A PP2C family in poplar unveils PtrPP2C-9 as a negative regulator of osmotic stress tolerance through ABF3/GBF3 network - Yuan Zhang; Rui-Quan Wang; Xin-Yi Wang; Shu-Ying Wei; Hao Li; Shuang-Lian Deng; Jia-Hui Liu; Ting Wang; Liang-Hua Chen; Fang He (Plant Science, 2026)

Integrated machine learning and density functional theory to design C₃N₅ piezo-catalysts toward precise control of selective reactive oxygen species and efficient water purification - Ting Li; Xianhu Long; Wei Liu; Fan Huang; Huinan Zhao; Tao Zhong; Jingyun Fang; Chun He (Journal of Hazardous Materials, 2026)

Policy-driven distinct dust pollution patterns in a super-large magnesite mining area: Spatiotemporal analysis integrating satellite remote sensing and CALPUFF model - Baodong Ma; Ting Kang; Shuxian Gao; Shuai He; Defu Che; Yuansheng Zhang (Journal of Cleaner Production, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

A quantification analysis on atmospheric bioaerosol dispersion in seasonal meteorological scenarios and risks: A LSTM modelling and visualization - Ting Zhang; Yufei Wang; Dingqiang Zhang; Lin He (Gondwana Research, 2026)

Iron single-atom/cluster nanozyme with enhanced oxidase-like activity for fluorescent/colorimetric analysis of Total antioxidant capacity in food - Meiling Chen; Yongmin Lei; Junlin Liu; Qiming Liu; Xingjian Song; Ting He; Guo-jun Zhang; Yujie Sun; Yulin Zhang; Yuqing Qin; Shaowei Chen (Food Chemistry, 2026)

Dynamic modeling of competitive growth between Listeria monocytogenes and background microbiota in Flammulina velutipes - Sijie He; Xuejie Liu; Qing Yu; Yangyang Xu; Ting Fang; Yeru Wang; Changcheng Li (Food Control, 2026)

Immunotoxicity and mechanism analysis of zebrafish embryos exposure to benzothiazole and its derivatives - Wan-Ting Huang; Run-Fan Wu; Zhong-Qian Xuan; Jia-Qi Wu; Ming-Fang He (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Interlayer-engineered ammonium vanadate cathodes via Na+/PEG Co-intercalation for fast and stable Zn-ion storage - Jian Guo; Shuo Meng; Xiao Yan; Qiuxian Wang; Ting He; Lu Chen; Lujie Zuo; Ya Tang; Hongbin Zhao (Chemical Engineering Journal, 2026)

Polycyclic aromatic hydrocarbons-induced suppression of the PPARα/ACAA1 axis drives hepatic steatosis: Integrating epidemiology, network toxicology, and experimental validation - Haonan Cui; Peng Zou; Wang Yang; Shijun He; Jinyuan Shi; Ting Sun; Mengge Wang; Zhiyong Song; Hanni Guan; Tong Wang; Lei Sun; Qing Chen; et al. (Chemico-Biological Interactions, 2026)

Early predicting brain metastases of EGFR positive lung adenocarcinoma patients by CT radiomics - Xinliu He; Chao Guan; Ting Chen; Houde Wu; Liuchao Su; Mingfang Zhao; Li Guo (Physical and Engineering Sciences in Medicine, 2026)

Alisol B 23-acetate alleviates high-fat diet-induced insulin resistance by activating the SIRT1/FOXO1 axis and PI3K/AKT pathway - Wenjun He; Zhenxuan Kong; Jingshu Cai; Zhuyun Wang; Li Ma; Xiaoqiu Xiao; Ting Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Physiological and Secondary Metabolism of Dendrobium nobile Lindl in Response to High Temperature Stress - Linlong Xu; Yijun Fan; Xueyan Tan; Jie Ma; Ting Li; Siyu He; Hui Wang; Liangjie Zhu; Le Zeng; Aoxue Luo (Journal of Plant Growth Regulation, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Soil phosphorus dynamics during cropland reforestation - Wenchao Wu; Rongxiao Che; Song Zhang; Yunlong He; Benjamin L. Turner; Dong Liu; Fang Wang; Ting Li; Anquan Xia; Zejin Zhang; Tong Li; Guangbing Xu; et al. (Agriculture, Ecosystems & Environment, 2026)

The role of KPNA3 in multiple myeloma: implications for targeting nuclear import - Hongmei Luo; Ziyue Mi; Jingcao Huang; Jingjing Wen; Siyao He; Haonan Yang; Yue Zhang; Linfeng Li; Xiang Liu; Xinyu Zhai; Fangfang Wang; Xinai Gan; et al. (Apoptosis, 2026)

Taxonomic Revision of Fenouilia and Lithoglyphopsis (Gastropoda, Pomatiopsidae): Synonymy Confirmed by Molecular and Morphological Data With New Species From Southern China - Hui Chen; Zhong‐Guang Chen; Ying‐Ying Zhang; Yu‐Ting Dai; Shan Ouyang; Hong‐Quan Xiang; Yue‐Ming He; Yi‐Zhi Lu; Xiao‐Chen Huang; Xiao‐Ping Wu (Zoologica Scripta, 2026)
China harbours remarkable yet understudied diversity in Pomatiopsidae, with many taxa overlooked due to minute shell sizes and morphological convergence. Through integrative taxonomic analysis of the endemic genus Fenouilia across southern China, we demonstrate that Lithoglyphopsis Thiele, 1928 is a junior synonym of Fenouilia Heude, 1889, supported by both morphological synapomorphies and multilocus phylogenetic analyses (COI, 16S, 18S and 28S). We further synonymize Fenouilia sinensis (Bavay & Dautzenberg, 1910) and Lithoglyphus taliensis Annandale, 1924 with F. kreitneri (Neumayr, 1880) and transfer two species from Jullienia and Hubendickia to Fenouilia : F. carinata (Fulton, 1904) comb. nov. and F. chinensis (Liu, Wang & Zhang, 1980) comb. nov. Seven new species are described: F. chongzuoensis H. Chen, Z.‐G. Chen, Y.‐M. He & X.‐P. Wu, sp. nov., F. guangxiensis H. Chen, H.‐Q. Xiang, Y.‐M. He & X.‐C. Huang, sp. nov., F. kingkongi H. Chen, H.‐Q. Xiang, Y.‐M. He & X.‐P. Wu, sp. nov., F. pengshijii H. Chen, H.‐Q. Xiang, Y.‐M. He & X.‐P. Wu, sp. nov., F. tangkelii H. Chen, H.‐Q. Xiang, Y.‐M. He & X.‐P. Wu, sp. nov., F. yiliangensis H. Chen, H.‐Q. Xiang, Y.‐M. He & X.‐P. Wu, sp. nov. and F. wangzhiyaoi H. Chen, H.‐Q. Xiang, Y.‐M. He & X.‐C. Huang, sp. nov., substantially expanding the known diversity of this genus. Our findings highlight the prevalence of cryptic speciation in Pomatiopsidae and underscore the need for combined morphological‐molecular approaches in freshwater gastropod systematics.

Magnetically controlled delivery capsule endoscopy for precise drug delivery to intestinal lesions - Chen He; Xi Jiang; Ting Zhang; Yizhi Chen; Xiaoou Qiu; Zhaoshen Li; Zhuan Liao (Drug Delivery and Translational Research, 2026)

Multiomics approaches identify immunometabolic crosstalk in triploid cyprinid fish after Edwardsiella tarda 1 l-4 infection - Ruo-Xing Yu; Ting Luo; Qin-Yang He; Zi-Rou Zhong; Jie Peng; Yao-Hui Li; Zhuang-Wen Mao; Ming-Zhu Huang; Zi-Le Qin; Xu-Ying Kuang; Zi-Xuan Fang; Jian Li; et al. (Aquaculture, 2026)

Petrology, geochemistry and geochronology of the Kekeya ash (SW Tarim Basin): Implications for its origin and provenance - Jia-Jun Mo; Yu-Ting Zhong; Man Wang; Le Zhang; Qiong Wu; Qiang Ma; He Wang; Jahandar Ramezani; Xiao-Long Huang; Fu-Yuan Wu; Yi-Gang Xu (Lithos, 2026)

Formation of residual water in sandstone CO2-H2O system: A comprehensive study based on orthogonal experiment and nuclear magnetic resonance method - Yi Li; Wendong Dan; Yujie Diao; Li He; Ting Liu (Journal of Hydrology, 2026)

Impacts of the mega cascade reservoirs on riverine hydrothermal regimes based on deep learning - Meixiu Yu; Jinjie Guan; Jianyun Zhang; Junliang Jin; Qingshe Meng; Hanlin Song; Zixuan Xu; Xiaolong Liu; Jiayi He; Ting Fu (Journal of Hydrology, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Revealing the immobilization mechanism of radioactive Cs⁺ through tailored mineral lattice architectures: Inspiration from natural mineral structures - Xueyan He; Chao Wang; Huimin Hu; Junwei Huang; Ting Jiang (Journal of Environmental Chemical Engineering, 2026)

Socioeconomic inequality in flood exposure and compound urban flood risk: A multistage assessment across 30,000 towns in China - Zhen He; Jinghao Hei; Zhiqiang Wu; Otthein Herzog; Lan Li; Ting Yang; Xiang Li (Journal of Environmental Management, 2026)

Exploring different modification methods of biochar for Se(IV) removal from water: Synergistic effect of adsorption and reduction - Yu-Ying Wang; Juan Yu; Rong-Ting Jiao; Li-Li He; Yao Su; Yun-Long Wang; Hui Lin; Yan Shi; Hao-Hao Lyu (Journal of Contaminant Hydrology, 2026)

Progressive uncertainty-guided network for binary segmentation in high-resolution remote sensing imagery - Jiepan Li; Wei He; Ting Hu; Minghao Tang; Liangpei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Te-Cu dual adsorption-conversion function cathode enables high-energy-density and long-lifespan liquid metal batteries - Weixin Zhang; Xin He; Ting Zhang; Haomiao Li; Shuai Yan; Xianbo Zhou; Yewei Guo; Min Zhou; Wei Wang; Kai Jiang; Kangli Wang (Chemical Engineering Journal, 2026)

Economically feasible and carbon-negative emission disposal of saline wastewater: Concentration-electrolysis integrating waste heat recovery and co-disposal of industrial waste salt - Xiaoyang Chen; Yuhai He; Ting Zhao; Peixiong Tan; Naizhen Yu; Chan Zou; Yipeng Wang; Huimin Liu (Chemical Engineering Journal, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Design, synthesis and activity evaluation of usnic acid monoesterification derivatives - Qing Zhang; Jun-Li He; Xiao-Xia Zhuo; Yi-Meng Hao; Hong-Ting Duan; Yan Jia; Jing-Jing Wang; Li-Ning Wang (Natural Product Research, 2026)

MEP3D: Improved clustering-based 3D point cloud method for comprehensive maize ear phenotypic trait extraction - Xinyue Sun; Ting Huang; Ziang Niu; Cheng Yang; Yong He; Zhengjun Qiu (Computers and Electronics in Agriculture, 2026)

Saline patch identification using a semi-supervised knowledge integration deep learning framework based solely on UAV RGB imagery - Zhen Li; Zhigang Sun; Ting Yang; Zhen Liu; Wentao Sun; Yixuan Zhang; Jundong Wang; Yajuan He; Zeqian Yang; Wei Han (Computers and Electronics in Agriculture, 2026)

Hydrological connectivity and nutrient thresholds drive seasonal dynamics of fish community in the Changjiang River-Shijiu Lake connected system - Yidong Liang; Wanlu He; Xue Xue; Ting Zhang; Junlei Ma; Yulin Bai; Dian Fang; Zhen Kuang (Marine Pollution Bulletin, 2026)

Photolysis of hexa(methoxymethyl)melamine in aquatic systems: Critical roles of UV-shielding effect, hydrated electron and 3DOM* induced by dissolved organic matter - Jinfan Chen; He Liu; Dehao Song; Mei Wang; Ting Tang; Songhan Zeng; Sile Wu; Xiaodong Du; Xueqin Tao; Zhi Dang; Guining Lu (Water Research, 2026)

Carbon quantum dots boost microbial biofilm−based hydrovoltaic electricity generation - Ting−Ting Chen; Zhi−Wu Yan; Feng−Ying Cai; Qiu−Xiang He; Han−Hui You; Christopher Rensing; Jian Lü; Shungui Zhou (Water Research, 2026)

Scale effect of DEM simulations for the ice resistance on ships navigating in level ice - Lu Liu; Ting Wang; Xing Zhou; Guangwei He; Aleh Kanavalau; Shunying Ji (Ocean Engineering, 2026)

Simultaneous transformation of tetracycline and nitrogen (ammonium/nitrite) by Sphingobacterium kyonggiense T8: Performance, pathway, genomics, and mechanisms - Yifei Leng; Yangqi Peng; Huan He; Ting He; Fengyi Chang; Wen Xiong; Zhu Li (Journal of Hazardous Materials, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Hydrochemical characteristics, evolution, and controlling factors of a karstic river with reservoirs: Insights from spatial-temporal analysis - Jiang Wu; Ting Wang; Tang Liu; Jia-Ju Liu; Nan Xu; Hui Zeng; Ling-Yan He (Journal of Environmental Sciences, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

Desalination of MSWI fly ash washing wastewater coupled with in-plant flue gas waste heat: Techno-economic analysis and carbon emission accounting - Xiaoyang Chen; Yuhai He; Ting Zhao; Lifang Gong; Chan Zou; Huimin Liu (Desalination, 2026)

Decorating the bridge in through-space charge-transfer emitter with an electron-withdrawing group for facile synthesis, tunable emission/transport property and improved electroluminescence performance - Yan Shu; Dajun Zhuang; Ting Li; Zetian Wang; Yongjun Song; Lei He (Chemical Engineering Journal, 2026)

Corrigendum to “Novel orthodontic adhesives with antibacterial, mineralization and fluorescence properties for enamel demineralization prevention” [Chem. Eng. J. volume 500 (2024) 156737] - Ting Luo; Jiarong Yan; Lingyun Cao; Xiaozhu Liao; Nannan Wang; Fang Hua; Hong He (Chemical Engineering Journal, 2026)

Simultaneous interface and bulk morphology control by a kinked self-assembled molecule for 20 % efficient organic solar cells - Ting Su; Jinjian He; Haoling Zhang; Xiyu Cheng; Miaomiao Zhang; Yaoyao Zhu; Renyong Geng; Shuisheng Chen; Xin Song (Chemical Engineering Journal, 2026)

A versatile hydrogel with sequential drug-releasing capability for the programmable healing of suppurative otitis media - Datao Hu; Jinpeng Wen; Hanchao Zhou; Yunhe Zheng; Jiangchuan He; Yu Huang; Ting Wang; Kailai Liu; Yuchen Zhang; Jingya Qu; Pengchong Wang; Ke Wang (Chemical Engineering Journal, 2026)

Photobiomodulation Reduces Fibrous Scar Formation After Spinal Cord Injury by Downregulating CXCL3 Expression in Macrophages - Zhihao Zhang; Hongwen Gu; Ting He; Yuanhang Zhao; Shilei Tang; Kangen Han; Yin Hu; Hongwei Wang; Hailong Yu (Molecular Neurobiology, 2026)

M1 macrophage exosomes inhibit lung adenocarcinoma growth by up-regulating KLF6 via the reduction of ALKBH5-mediated KLF6 demethylation - Jian Gou; Ting Jia; Shasha Song; Jie He; Dan Zhao (Molecular and Cellular Biochemistry, 2025)

LSD1 modulates ovarian reserve establishment by modifying FOXO3 and mitophagy-related genes - Shaogang Qin; Zijian Zhu; Tianhua Zhu; Yi Lin; Meina He; Ting Zhao; Meng Gao; Yibing Bao; Lin Lin; Jingwen Zhang; Longping Liu; Jianbin Wang; et al. (Science Bulletin, 2025)

Humidity change in the upper-middle Yangtze River watershed during the MIS3 and its relationship to the East Asian Summer Monsoon - Liuliu Feng; Yixuan Wang; Runsheng He; Liang Tang; Ran Wei; Ting Chen (Quaternary Science Reviews, 2025)

Straw-induced hematite-to-magnetite conversion in alkaline media: Experimental study and potential in Bayer process - Xin He; Guo-zhi Lv; Bing-shen Liu; Qing-dong Li; Xiao-lei Zhang; Zhuang-zhuang Yun; Ting-an Zhang (Minerals Engineering, 2025)

Nuclear factor E2 related factor 2 may alleviate liver injury by regulating iron overload and lipid peroxidation induced by chronic fluorosis - Xiao Xiao; Xi Tu; Na Wei; Wen-Wen He; Xiao-Xiao Zeng; Wei Liao; Jie Deng; Yang-Ting Dong; Xiao-Lan Qi; Yan Xiao; Wei Hong; Yan He; et al. (Journal of Trace Elements in Medicine and Biology, 2025)

Unveiling characteristics of algae pond aerosolization and pathogen transmission: Temporal regulation simulation responding to nutrient inflows under the rain scenarios - Ting Zhang; Lin He (Journal of Hazardous Materials, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Photodegradation of sulfisoxazole during nitrite-sensitized photolysis - Xu Gao; Xiaoyu Li; Yaowu Xu; Xinyu Zhan; Ting Zhou; Bing Zhou; Xin Wang; Yuhang He; Chunyu Wang; Han Mao (Journal of Environmental Chemical Engineering, 2025)

Temporal-spatial laws of microseismic events induced by the fracture evolution of overburden strata and the relationship with gas emission during coal mining engineering - Xiangguo Kong; Hui Zhang; Yankun Ma; Ting Liu; Pengxiang Zhao; Ali Muhammad; Di He; Aohan Zhao (Journal of Applied Geophysics, 2025)

Ready-to-eat beef steaks prepared by superheated steam: from texture and flavor to storage stability - Jiyuan He; Lunzhou Lin; Jiebin Cai; Chengjun Liu; Yaming Xiao; Yajie Shen; Binxiong Liu; Ting Fang (International Journal of Gastronomy and Food Science, 2025)

Neurophysiological and multimodal sensory evaluation of baijiu and food pairing liking - Yu Fu; Cheng Wang; Guoliang He; Shaohui Fan; Deliang Wang; Gaochong Lv; Lucas P.J.J. Noldus; Ting Jiang; Jie Huangfu (Food Research International, 2025)

Automatic immunomagnetic beads clean-up coupled with HPLC-FLD for rapid, simple and high-throughput detection of zearalenone in cereal foods and feeds - Zhiming Xiao; Jun Zhang; Yinji Jin; Bo He; Ting Yao; Jing Tian; Fan Mo; Decheng Suo; Shi Wang; Runxian Li; Lijie Zhang; Shen Hu; et al. (Food Chemistry, 2025)

Human milk fat Substitutes alleviate dextran sulfate sodium induced cognitive deficits in mice by modulating brain fatty acid and ether Lipid metabolism - Yangzheng He; Linhui Zeng; Han Liao; Jing Li; Yong Sun; Hongyan Li; Ting Luo; Zeyuan Deng (Food Bioscience, 2025)

Antifungal activity and preservation efficacy of Bacillus velezensis fermentation supernatant against Phyllosticta capitalensis-induced black spot in postharvest guava fruit - Jiyuan He; Zhaojie Gao; Zehao Yang; Shan Wang; Jianping Rao; Ting Fang; Tuanwei Chen (Food Bioscience, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

Rapid culture-free species identification and phenotypic antibiotic susceptibility test for polymicrobial infection by single-cell Raman spectroscopy - Miao Yu; Liliang Wang; Yiwen Xu; Jiyong Yang; Changsong Zhang; Ting Wang; Siyu Meng; Jingkai Wang; Qiang Zhao; Zhiqiang Zhang; Huijie Hu; Huan Zeng; et al. (Chemical Engineering Journal, 2025)

Room-temperature fabrication of layer-by-layer assembled aromatic phosphonium ionic organic single crystals for efficient environmental remediation: iodine capture and thorium(IV) sequestration - Mingxia Sun; Jia Chen; Ting Zhang; Jing He; Yunyun Zhang; Huifeng Liu; Wei Xu; Zhao Wang; Hongdeng Qiu (Chemical Engineering Journal, 2025)

Iron single-atom catalysts drive peroxymonosulfate activation for efficient degradation of extracellular antibiotic resistance genes through singlet oxygen-mediated DNA damage - Yunhong Zhang; Ping Yu; Xujing Guo; Lan Wang; Wenguo Wang; Liangwei Deng; Hongwei Zhang; Ting He; Zhaokun Xiong; Bo Lai (Chemical Engineering Journal, 2025)

Protein-driven multiscale structural evolution and oil absorption in Tigernut (Cyperus esculentus L.) starch during thermal extrusion - Xiao-Shuang Cai; Jing-Wen Qin; Zhong-Wei Wu; Wan-Tong Zhao; Wen-Ting Yin; Yu-Xiang Ma; Hua-Min Liu; Jing-Ren He (Carbohydrate Polymers, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Linking leaf‒litter‒soil stoichiometry to microbial carbon‒use efficiency across different forest types in north subtropical China - Zongxin Liu; Junjie Lei; Yuanying Peng; Wei Zheng; Ting He; Wende Yan; Peng Dang (CATENA, 2025)

Association between short-term exposure to ambient fine particulate matter & components and the risk of spontaneous abortion - Jialiang He; Wenzheng Zhou; Xin Ming; Yunping Yang; Ziyi He; Yannan Li; Ting Dong; Xinzhen Chen; Min Zhang; Yankun Wang; Yubin Ding; Wei Zhou (Atmospheric Pollution Research, 2025)

Identification of AhFPA1 as the causal gene underlying qEFT13.1, a key QTL for early flowering in peanut - Zhao Li; Yu Liu; Qingliang Hu; Jiahao Liang; Zehua He; Yixin Wang; Wenrui Zhang; Ting Pan; Gonghao Ma; Jing Wang; He Zhang; Zhenghao Lv; et al. (Theoretical and Applied Genetics, 2025)

Mechanism of Axial Chain Rockbursts in Deep Tunnels: Structural Plane-Induced Stress Concentration Triggered by Drilling and Blasting - Hong-Pu Li; Ben-Guo He; Xia-Ting Feng; Wen-Jing Niu; Tao Ma (Rock Mechanics and Rock Engineering, 2025)

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

Therapeutic effect of total glucosides of paeony on IgA vasculitis nephritis: progress and prospects - Zhifeng Wang; Jiao Yang; Pengfen He; Junfeng Lan; Ting Shi; Shuangfeng Xu; Zhihui Hao; Yujiang Xi; Jian Wang; Ping He (Molecular Biology Reports, 2025)

The accuracy and real resolution of karyotyping technique in detecting chromosomal aberrations identified by molecular genetic methods - Shuo Zhang; Yaqiong He; Yi Huang; Yueping Zhang; Yanzhi Du; Ting Zhang; Yun Sun; Yao Lu (Molecular Genetics and Genomics, 2025)

Comparative analysis of the WRKY gene family between Chimonanthus praecox and C. salicifolius - Wei Zou; Gui-Ting Hu; Fang-Fang Gui; Xin-Chen He; Priyanka Borah; Li Zhu; Hui-Juan Ning; Li-Yuan Yang (Genetica, 2025)

Key copper homeostasis genes and inflammatory mechanisms in ischemic stroke: A bioinformatics and experimental study - Ting Shi; Zhifeng Wang; Jiao Yang; Pengfen He; Daman Tian; Junfeng Lan; Shuangfeng Xu; Aiming Yang; Liwei Xing; Yujiang Xi; Jian Wang (Functional & Integrative Genomics, 2025)

Retraction Note: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Deep learning-based tunnel advance geological forecast for polygon targets via regional GPR data - Ting-wei Yang; Jing-he Li; Ye-hui Cao; Bin Xiong; Liu-ye Wei (Applied Geophysics, 2025)

Aeromagnetic characteristics and lithologic mapping in Panzhihua-Anyi area - Jiao-jiao Li; Yong-jun Zhang; Yi-yuan He; Ting-yan Zhao; Shi-jun Li (Applied Geophysics, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Co-optimization of distributed energy systems: A three-layer framework leveraging a novel diagram-driven method - Junquan Guan; Weike Mo; Yongyi Li; Weiliang Wang; Ting He; Chang Huang (Journal of Cleaner Production, 2025)

The influences of China's Cultivated Land Fertility Protection Subsidy policy on farmers' agro-eco-environmental protection behavior: an application of the extended theory of planned behavior - Ting Liu; Linwei Du; Jiaona Hou; Xiancheng Zeng; Wenyan Zhang; He Xu (Journal of Environmental Management, 2025)

Solar radiation on complex underlying surfaces in Xinjiang: A typical arid and semi-arid region in the northwestern China - Chengming Zhang; Xin Liu; Shuyi Chen; Jianrong Bi; Yonghang Chen; Qing He; Ting He; Yunhong Xu; Hui Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Thermodynamic optimization and exergy analysis of a combined cryogenic CO2 capture process for hydrogen production via steam methane reforming - Ting He; Kai Zhang; Duo Xu; Song Yang; Liqiong Chen; Siyue Ren (Fuel, 2025)

Efficient extraction of perfluoroalkyl carboxylic acids from food samples using a fluorinated magnetic metal-organic framework adsorbent - Ting Liu; Chunyan Sang; Yuwei Liu; Bing Shao; Gengsheng He (Food Chemistry, 2025)

Superheated steam for disinfection of dehydrated Porphyra yezoensis - Jiyuan He; Xiaoyan Huang; Chen Liu; Jiebin Cai; Lunzhou Lin; Qi Wei; Ting Fang (Food Control, 2025)

Nitrogen transformation in the crop-soil system determines the exacerbation of yield-scaled N2O emissions from rice paddies under climate change - Yuanyuan Wang; Wei Huang; Ziqi Xu; Zhenghua Hu; Tingwu Liu; Guihua Lu; Kezhi Zheng; Dan Dong; Yonggang Xu; Shuqi He; Gecong Ma; Ting Li; et al. (Field Crops Research, 2025)

Humid heat’s nonlinear impact on school-age children’ sleep health: Evidence from Guangdong, China - Yuan Gao; Li-Zi Lin; Wen-Wen Bao; Wan-Ting He; Yun-Ting Zhang; Guang-Hui Dong; Shenjing He (Environmental Research, 2025)

IFNγ-exosomes accelerate wound healing by suppressing immune rejection of allogeneic keratinocytes in collagen/PRP scaffolds via the IDO-kynurenine pathway - Shijie Song; Weidong Zhang; Wei Ji; Ting Li; Kai Guo; Xiang He; Dahai Hu; Huilin Liu; Yunchuan Wang (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Optimizing hematite reduction in high - Iron bauxite during Bayer process via bagasse: A path to efficient resource utilization - Xin He; Guo-zhi Lv; Xiao-lei Zhang; Qing-dong Li; Bing-shen Liu; Zhuang-zhuang Yun; Ting-an Zhang (Biomass and Bioenergy, 2025)

Editorial Expression of Concern: The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2025)

Tracing spatial variations in ecological and economic benefits to support basic dimensions of wellbeing during urban expansion - Shi Xue; Zhou Fang; Carena van Riper; Yang Bai; Wei He; Ting Wang; Qin Zhou; Changgao Cheng; Zhongde Huang (Sustainable Cities and Society, 2025)

Pyrogenic carbon accelerated electron transfer process of dissolved organic matter in paddy soil - Yufei Wu; Hao Ren; Ting He; Chen Cheng; Jinshuo Zhang; Peng Zhang; Bo Pan (Science of The Total Environment, 2025)

UV-guided separation of polyacetylenol glycosides from the edible roots of Codonopsis pilosula and their anti-inflammatory activity - Xilan Jiang; Lun Wang; Yao Chen; Yi Zuo; Mengdan Liu; Bin Chen; Dong Fu; Yujiao He; Mingkui Wang; Ting Shen; Fu Li (Phytochemistry, 2025)

Protective effects of nicotinamide mononucleotide on DNA damage and cell death in A549 cells and aging in C. elegans caused by hydrogen peroxide - Chuncao He; Xueying Sun; Ting Xu; Xiaoqiang Hu; Jinyi Han; Kexin Xu; Qin Song; Ting Duan; Jun Yang (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2025)

Specific dual-mode fluorometric and colorimetric detection of nitrite based on oxidase-like activity of carbon dots/iron alkoxide composite - Dingfeng Wang; Liwei Gao; Xinru Liu; Linfan Wang; Ting Zhang; Guoqiang Guo; Hongxing He; Da Chen (Food Chemistry, 2025)

Maillard reaction based chitosan-monosaccharide films and the application in fruit preservation - Panpan Zhao; Danping Zheng; Ting Li; Haoyang Peng; Jiaqi He; Jinyi Shi; Jinzhong Zhao; Peng Li; Wuxia Zhang (Food Hydrocolloids, 2025)

Impact of system size on pattern transitions in dissolving rough fractures: experiments, multi-physics coupling simulations and theoretical analysis - Ting Wang; Yaning He; Yanlong Li; Ran Hu; Yang Zhou; Yifeng Chen; Junrui Chai; Yunhe Liu (Computers and Geotechnics, 2025)

The PRIDE system: A photo-responsive platform for high-efficiency isolation of extracellular vesicles for Parkinson's disease diagnostics - Wenjing Zhang; Ting Zhang; Jiayu Ding; Jingwen Cao; Zheyan He; Yanling Liu; Yong Juan Zhao; Chungen Qian; Chenzhong Li; Jiasi Wang; Bo Peng; Cheng Jiang (Chemical Engineering Journal, 2025)

Preparation of N-doped porous biochar with high CO2 adsorption performance via one-step molten salt thermal treatment - Tian Xie; Jing He; Liang-Chen Xu; Ting Yan; Quan-Wen Pan; Li-Wei Wang; Wei-Guo Pan (Chemical Engineering Journal, 2025)

Unveiling the vertical dynamics of atmospheric ammonium in Asia megacity: A GRASP-based investigation of spatiotemporal patterns and source drivers - Yining Tan; Ting Yang; Hongyi Li; Ping Tian; Yifan Song; Jiancun He; Yutong Tian; Yele Sun; Zifa Wang (Atmospheric Research, 2025)

Analysis of the relationship between C, N, P and dry matter content of 41 subtropical woody plants from seasonal and developmental scales - Zheng-Chao Yu; Xiao-Ting Zheng; Wei Lin; Wei He; Hui Zhu; Chang-Lian Peng (Trees, 2025)

Proteome Profiling of Serum Reveals Pathological Mechanisms and Biomarker Candidates for Cerebral Small Vessel Disease - Yun-chao Wang; Hang-hang Zhu; Liu-Chang He; Ya-ting Yao; Lei Zhang; Xin-li Xue; Jing-yi Li; Li Zhang; Bo Song; Chang-he Shi; Yu-sheng Li; Yuan Gao; et al. (Translational Stroke Research, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Lactiplantibacillus plantarum RS20D Alleviates Male Reproductive Toxicity Induced by Pubertal Exposure to Di-n-butyl Phthalate and Mono-n-butyl Phthalate - Yuan-ting Zhu; Xing-jie Wang; Shu-liang Liu; Jing-hui Lai; Jian-long Li; Qin Li; Kai-di Hu; Ai-ping Liu; Yong Yang; Li He; Shu-juan Chen; Xiao-lin Ao; et al. (Probiotics and Antimicrobial Proteins, 2025)

Design, synthesis and antitumor activity of 4-indazolylpyrimidine derivatives as EGFR inhibitors - Ting Yang; Xiaoling He; Ting Wu; Wenqiang Zhu; Zhiwu Long; Yi Le (Molecular Diversity, 2025)

Transcriptome Reveals Molecular Characteristics and Immune Response in Triploid Cyprinid Fish Infected with a Novel Pathogenic Aeromonas sp. AS1-4 - Qin-Yang He; Jie Peng; Ruo-Xing Yu; Ting Luo; Yao-Hui Li; Zi-Rou Zhong; Zi-Le Qin; Fei Wang; Jian Li; Sheng-Wei Luo (Marine Biotechnology, 2025)

LSTM-based receiver clock modeling and prediction for GNSS urban positioning - Zhiqiang Dai; Simei Sun; Ting Xie; Chunlei Zhai; Zhigang Hu; Xiangwei Zhu; Shaofeng He; Fan Feng (GPS Solutions, 2025)

Influence of herbal extract blend supplementation on growth performance, liver and intestinal health, intestinal transcriptome, and resistance to Aeromonas veronii in Micropterus salmoides with optimized feeding intervals - Zi ying Zeng; Dong dong Yu; Yi Ting Shen; Xing han He; Shun Yang; Hui Fei (Animal Feed Science and Technology, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

Fungal diversity associated with cherry leaf spot in Yantai city, Shandong province, China - Yumeng Wang; Ting Liu; Chuang Han; Xiaoyan Yu; Xi Xu; Yuhan Guo; Xinying He; Wensheng Xiang; Xiangjing Wang; Junwei Zhao (Physiological and Molecular Plant Pathology, 2025)

Innovative starch-based alkaline thermal reduction of hematite: A fundamental study on mineral phase reconstruction and its potential in the Bayer process - Xin He; Guo-zhi Lv; Song Wang; Qing-dong Li; Zhuang-zhuang Yun; Ting-an Zhang (Minerals Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Acidic pH as the deterministic factor shaping microbial community dynamics and interactions in molasses-fed sulfate-reducing bioreactors - Mingyu He; Mengmeng Wang; Yanyi Liang; Yuting Zhang; Qi Zou; Ting Ma; Mengyun Chen; Wensheng Shu; Baichuan Cao (Journal of Hazardous Materials, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Optimizing removal and control of inclusions/impurities and recovery of valuable elements in metallurgical melts via electric field: toward circular economy and resource efficiency - Wen-zhi Xia; Hai-chuan Wang; Ruipeng Pang; Yun Zhou; Zhi-you Liao; Ting Wu; Baowen He; Guang-da Bao; Zhen Hou; Shao-long Chu; Ping-fan Ren (Chemical Engineering Journal, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

A dual-polysaccharide (carboxylated chitosan-carboxymethyl cellulose sodium) gastrointestinal dynamic response in situ hydrogel for optimized oral targeted inflammatory bowel disease therapy - Yuchen Zhang; Kailai Liu; Yunhe Zheng; Jiangchuan He; Yu Huang; Jiayang Gao; Xi Chen; Ting Wang; Hanchao Zhou; Jinpeng Wen; Qinyue Yu; Ke Wang; et al. (Carbohydrate Polymers, 2025)

A rich carbohydrate-lipid kitchen waste upcycling via Chlorella vulgaris cell proliferation and biomass production strategy - Ting Zhang; Hao Zhou; Mingming Zhao; Dingqiang Zhang; Lin He (Bioresource Technology Reports, 2025)

ZmDof08, a zinc finger transcription factor, plays critical roles in photosynthesis in maize - Ting Li; Jinjie Guo; Jiahao Zhang; Ping Deng; Yuanyuan Xu; Xinjia Li; Yu He; Lian Zhou; Chaofeng Li; Chaoxian Liu (Plant Cell Reports, 2025)

Melatonin Mitigates Sleep Restriction-Induced Cognitive and Glymphatic Dysfunction Via Aquaporin-4 Polarization - Huaiqing Sun; Qiuchen Cao; Xiaoxin He; Xinyu Du; Xueqin Jiang; Ting Wu; Ming Xiao (Molecular Neurobiology, 2025)

The summer pattern of phytoplankton pigment assemblages in response to water masses in the Yellow Sea - Ting Lü; Hao Zhou; Mengfan He; Lei Lin; Yujue Wang; Dongyan Liu (Journal of Oceanology and Limnology, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Phase and defect engineering of 1T/2H MoS2-x nanosheets for enhanced piezocatalytic inactivation of antibiotic-resistant bacteria - Huinan Zhao; Zhangnan Yao; Ting Li; Yanhong Lu; Kaiwen Wang; Jia He; Shuanghong Tian; Fan Huang; Chun He (Journal of Hazardous Materials, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

High value-added conversion of atmospheric pollutants and greenhouse gases: assessment of bottlenecks and optimization strategies for mainstream catalytic technology - Tao Zhong; Xianhu Long; Zhangnan Yao; Ting Li; Huinan Zhao; Su Tang; Shuanghong Tian; Chun He (Journal of Cleaner Production, 2025)

Steam-baking for disinfection of dehydrated Porphyra yezoensis - Jiyuan He; Xiaoyan Huang; Qi Wei; Ting Fang (Innovative Food Science & Emerging Technologies, 2025)

Efficiently hydrogenolysis of aromatic ether C-O bonds in lignite and model compounds over carbon-coated NiCo bimetallic catalyst - Caitao Chen; Juan Ma; Yakun Tang; Xiaohui Li; Guangbo Liu; Hanyao Song; Yingluo He; Noritatsu Tsubaki; Lang Liu; Ting Liu (Fuel, 2025)

Lacticaseibacillus paracasei NCU-21 improves ethanol-induced gastric mucosal injury by regulating the Nrf2/HO-1 signalling pathway and gastrointestinal microbiota in mice - Jie You; Xinyi Zhang; Leiping Ding; Yifeng Yu; Qingling Yang; Tangchang Xu; Zhipeng He; Ting Li; Jing Wei; Tingtao Chen (Food Research International, 2025)

A novel hybrid machine learning approach for accurate retrieval of ocean surface chlorophyll-a across oligotrophic to eutrophic waters - Ting Qin; Tianlong Liang; Donglin Fan; Hongchang He; Guiwen Lan; Bolin Fu (Environmental Research, 2025)

MgFe-LDHs/Vallisneria natans combined system for simultaneous elimination of endogenous N and P pollution in eutrophic water: Performance, synergetic mechanism, and metagenomics analysis - Zihao Hu; Zeyu Li; Yin Xu; Feifei He; Jiani Zhang; Ting Li (Environmental Research, 2025)

Prim-O-glucosylcimifugin-loaded nanodrug hydrogel alleviates periodontitis and colitis via modulating macrophage polarization and microbiota balance - Chengye Ding; Xinjia Cai; He Zhang; Yixin Ma; Liyuan Chen; Xiaolan Wu; Min Yu; Chang Li; Hangbo Liu; Shiying Zhang; Xinmeng Shi; Ting Zhang; et al. (Chemical Engineering Journal, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

CD73 polymorphisms are associated with schizophrenia - He-Xia Peng; Li-Li Zhang; Dan Jiang; Na Jian; Ting-Mei Zhang; Jia-Guo Luo; Hai-Yan Yin (Purinergic Signalling, 2025)
Ecto-5’-nucleotidase/CD73 enzyme plays a key role in the regulation of extracellular adenosine levels, thereby exerting influence on adenosine homeostasis. Emerging evidence suggests that perturbations in purines and ecto-5’-nucleotidase activity are associated with an augmented susceptibility to schizophrenia. However, the precise impact of genetic variations in CD73 on individuals with schizophrenia remains poorly understood. Here, our study demonstrated that rs3734442 allele and rs4431401 heterozygote were conferred a significant risk of schizophrenia disease (rs3734442: odds ratio, 0.556; 95% CI, 0.375 to 0.825; p = 0.004; rs4431401: odds ratio, 1.881, 95% CI, 1.117 to 3.166; p = 0.020). Comparing different genders, we observed a significant association between rs3734442 genotypes and male cases (rs3734442: odds ratio, 0.452; 95% CI, 0.257 to 0.796; p = 0.007). Likewise, there was a significant association between rs4431401 genotypes and male patients (rs4431401: odds ratio, 2.570; 95% CI, 1.196 to 5.522; p = 0.015). Based on family history and antipsychotics medication usage, our data reveals that the rs9444348 allele exhibits the most significant association with familial susceptibility to schizophrenia (odds ratio, 1.541; 95% CI, 1.009 to 2.353; p = 0.048 for A vs G). Moreover, individuals carrying variants of rs6922, rs2229523, and rs2065114 while being treated with clozapine demonstrate a higher frequency proportion compared to those receiving risperidone treatment ( p = 0.035; p = 0.049; p = 0.027 respectively). Additionally, our results indicate that patients with GG genotype of rs9444348 had significantly higher likelihood of using clozapine instead of sulpiride ( p = 0.048). Overall, our data strongly suggest that genetic variations in CD73 are significantly associated with schizophrenia risk and may serve as valuable resources for identifying therapeutic targets.

Plant clippings improved soil microbial community structure and potential functionality in farmland as organic amendments: fresh vs dry - Zhen Cheng; Yarong Sun; Ting Zhou; Jiangbo Qiao; Yingge Xie; Jinlong He; Dong Wang; José A. Siles; Gao-Lin Wu (Plant and Soil, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

Upregulating mTOR/S6 K Pathway by CASTOR1 Promotes Astrocyte Proliferation and Myelination in Gpam−/−-induced mouse model of cerebral palsy - Zhaofang Chen; Liru Liu; Xiaolin Guo; Yage Zhang; Mengru Zhong; Yi Xu; Tingting Peng; Tingting Peng; Yuan Zhang; Qingfen Hou; Danxia Fan; Ting Gao; et al. (Molecular Neurobiology, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Viscosity is a nonnegligible factor in the waste activated sludge fermentation: Taking hyaluronan as an example - Yan-Lin Hu; Kun Dai; Qing-Ting Wang; Chen-Yuan Zhou; Xing-Chen Huang; Xiao-Fei Yang; He-Liang Pang; Raymond Jianxiong Zeng; Fang Zhang (Water Research, 2025)

Synergistic recovery for Al and Ga within high-alumina fly ash by carbochlorination using the response surface method - Wang Long; Zhao Xin-xin; Zhang Zi-mu; Zhang Ting-An; Lv Guo-Zhi; Dou Zhi-He; Liu Yan; Fan zhi-yu (Waste Management, 2025)

Jet control of tandem cylinders with variable radius using deep reinforcement learning - Xian-Jun He; Ting-Shuai Tong; Ming-Yu Wu; Chun Zheng; Zhi-Hua Chen (Ocean Engineering, 2025)

Not for nothing, microplastics can (potentially) reduce the risk of mosquito-to-human transmission of arboviruses - Jian-hang Li; Xiao-hui Liu; He-ting Gao; Guo-rui Liang; Teng Zhao; Chun-xiao Li (Journal of Hazardous Materials, 2025)

Comprehensive revealing the destructive effect and inhibitory mechanism of oxytetracycline on aerobic denitrification bacteria Acinetobacter sp. AD1 based on cell state, electron behavior and intracellular environment - Qidi Mao; Jianguo Bao; Jiangkun Du; Yi Zhang; Yu Zhou; Ting He; Benai Cheng (Journal of Hazardous Materials, 2025)

Tracking nutritional and quality changes in frozen pork: A 12-month study using 7 categories of meat parameters and VIS/NIR spectroscopy - Xi Tang; Hui Xiao; Ting Luo; Jiacheng Wei; Ruiqiu He; Junhui Duan; Shijun Xiao; Nengshui Ding; Lusheng Huang; Zhiyan Zhang (Food Chemistry, 2025)

Designing stable walnut oil Pickering emulsions: Interfacial behavior and zero-order release of stigmasterol and β sitosterol using walnut protein-high methoxyl pectin-gallic acid complexes - Xu Zhang; Xiaoqian Zhan; Ruonan He; Honghong Zhang; Yazhuan Li; Wenyu Liu; Ting Wang; Ting Zhang; Changqing Wei (Food Chemistry, 2025)

Synergy of carbon - pollution - ecology ——The future of synergetic reduction of pollution and carbon emissions - Huanzhi Wang; Ting Liu; He Xu; Erfu Dai; Huimin Hou (Environmental Impact Assessment Review, 2025)

Mixed-cation engineering of hybrid antimony chlorides for band gap-directing deep-blue emission - Ren-Jie He; Lin-Xia Yang; Xin-Yu Ma; Ting-Jie Wang; Zengsheng Guo; Jinling Miao; Suna Wang; Cuncheng Li; Guang-Ning Liu (Chemical Engineering Journal, 2025)

Electrocatalytic upcycling of polylactic acid hydrolysate and simultaneous hydrogen production - Ping He; Jiang-nan Xu; Jia-yang Dou; Bing Xu; She-ying Dong; Ting-lin Huang; Jun-Jie Zhu (Chemical Engineering Journal, 2025)

Concentration-dependent effects of polystyrene microplastics on methanogenic activity and microbial community shifts in sewer sediment - Lucheng Li; Ting Xiao; Zanji He; Qijin Chen (Bioresource Technology, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Time-Delayed Rockbursts Induced by Dynamic Disturbances: 793 Cases in Deep Tunnels - Ben-Guo He; Heng-Yuan Zhang; Xia-Ting Feng; Xiang-Rui Meng (Rock Mechanics and Rock Engineering, 2025)

Assessing sensitivity and uncertainty in rod ejection accidents: A combined PCE-POD approach - Yijun Zhang; Wenhuai Li; Sitao Peng; Jinggang Li; Ting Wang; Qingyun He; Tao Wang; Haoliang Lu; Zeng ling (Annals of Nuclear Energy, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Endothelial GTPBP3 directs developmental angiogenesis and neovascularization after limb ischemia via the mtROS/HRl/ATF4/mTORC1 axis - Donglu Qin; Jiarui Hu; Yang Yang; Xin Li; Jia He; Jin Chen; Xin Guo; Cheng Wei; Fengjiao Wang; Ting Yi; Chenyu Li; Bilian Yu (Angiogenesis, 2025)

Effects of Maternal Trace Elements Exposure in Early Pregnancy on Maternal Thyroid Hormones and Birth Outcomes - Ting Wu; Tao Li; Chen Zhang; Yan-Hui Hao; Si-Wei Zhang; Xuan-Ping Wang; Yi-Cong Meng; Yan-Ting Wu; He-Feng Huang (Biological Trace Element Research, 2025)

Unlocking the future potential of SWATH-MS: Advancing non-target screening workflow for the qualitative and quantitative analysis of emerging contaminants - Di Xia; Guofang Pan; Yaxiong Liu; He Liu; Bo Zhao; Jiahui Wu; Ting Tang; Guining Lu; Rui Wang (Water Research, 2025)

Synthetic microbial community maintains the functional stability of aerobic denitrification under environmental disturbances: Insight into the mechanism of interspecific division of labor - Yue He; Hui Yun; Liang Peng; Wenxue Wang; Ting Xu; Wenjie Zhang; Xiangkai Li (Water Research, 2025)

Unveiling the intricate dynamics of PM2.5 sulfate aerosols in the urban boundary layer: A pioneering two-year vertical profiling and machine learning-enhanced analysis in global Mega-City - Hongyi Li; Ting Yang; Yifan Song; Ping Tian; Jiancun He; Yining Tan; Yutong Tian; Yele Sun; Zifa Wang (Urban Climate, 2025)

Government-involved urban meteorological networks (UMNs): A global review - Carmen Hau Man Wong; Yu Ting Kwok; Yueyang He; Edward Ng (Urban Climate, 2025)

Mitigation of methane emissions from urban sewer sediments: Sulfate addition and freeze-drying treatment - Lucheng Li; Lu Xu; Ting Xiao; Zanji He; Qijin Chen (Process Safety and Environmental Protection, 2025)

α-Pyrones, root growth inhibitors from a mesophotic zone sponge-associated fungus Purpureocillium sp. NBUF263 - Yu-Ying Liu; Ting-Ting Wei; Guang-Jun Ran; Xiao-Hui Li; Salman Khan; Tao Cai; Chan-Ting Lai; Hong-Kun Wang; Bin Wu; Hai-Xiao Jin; Wei-Yan Zhang; Ting-Ting Wang; et al. (Phytochemistry Letters, 2025)

A recycled polymetallic catalyst derived from acid mine drainage(AMD) for efficient tetracycline removal via peroxymonosulfate activation - Penghui Li; Ting Luo; Chunyao Gu; Peng He; Jianyu Zhu; Min Gan; Ke Zhang (Journal of Water Process Engineering, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Surfactant-modulated synthesis of BiOBr-C (C-Br channel) flower-like microspheres for efficient removal of different contaminants from water: Pathway, DFT calculation and degradation mechanism study - He Kang; Yiming Sun; Xiang Fei; Yongli Yin; Weidong Wu; Ting Fan; Yaqing Zhang; Xing Fan; Haifeng Zhou; Peng Liang (Journal of Environmental Chemical Engineering, 2025)

Enhanced transformation of sulfadiazine by horseradish peroxidase activated persulfate progress: Characteristics, pathways, mechanisms, and ecotoxicities - Yifei Leng; Ying Zhang; Xiong Chen; Ting He; Fengyi Chang; Zhu Li; Yu Huang; Jun Wang; Wen Xiong (Journal of Environmental Chemical Engineering, 2025)

Global levels and variations of breast milk fatty acids and triacylglycerols: A systematic review and meta-analysis - Xinggang Ni; Zhiyi Zhang; Zeyuan Deng; Sufang Duan; Ignatius Man-Yau Szeto; Jian He; Ting Li; Jing Li (Food Chemistry, 2025)

Injectable polyphenol hydrogel prevents peritoneal adhesion intensified by intraperitoneal microbial infection - Jinpeng Wen; Yunhe Zheng; Jiangchuan He; Datao Hu; Yu Huang; Kailai Liu; Yuchen Zhang; Ting Wang; Hanchao Zhou; Ke Wang (Chemical Engineering Journal, 2025)

Chemical constituents of Ainsliaea fragrans and their chemotaxonomic significance - Xiao-Ting He; Yun-Na Wang; Xue-Mei Zhou; Jing-Jing Zhang; Xiao-Li Li; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2025)

Light intensity is a crucial factor that regulates growth, physiological traits, antioxidant defense, and metabolite acquisition in Dendrobium denneanum - Hui Wang; Siyu He; Yijun Fan; Ting Li; Linlong Xu; Jie Ma; Junlan Wu; Haolin Liu; XuYang Liu; ChunHong Mou; Meng Zhao; Li Chen; et al. (Physiology and Molecular Biology of Plants, 2025)

Vincristine exerts antiglioma effects by inhibiting the PI3K/AKT signaling pathway: A mechanistic study based on network pharmacology, bioinformatics analysis, and experimental validation - Zhihua Chen; Jiahong Wang; Ting He; Donggen Rao; Ziyang Wang; Jianming Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Co-application of nitrification inhibitors with straw or biochar yielded varying effects on soil nitrification rate, N2O emissions, and ammonia oxidizers - Xiaoqian He; Jiaju He; Hongjie Shen; Zhuo Zeng; Di Zhao; Cen Cheng; Minghua Zhou; Ting Lan (Journal of Soils and Sediments, 2025)

Protein Kinase C Epsilon Overexpression Protects the Heart Against Doxorubicin-Induced Cardiotoxicity Via Activating SIRT1 - Danyong Liu; Chunyan Wang; Yao Chen; Xiaolei Huang; Yajie Wen; Shan Duan; Yin Cai; Xia Li; Jianfeng He; Kaijia Han; Ting Li; Yuantao Li; et al. (Cardiovascular Toxicology, 2025)
Doxorubicin (DOX)-induced cardiotoxicity (DIC) is known to be associated with reduction of cardiac protein kinase C epsilon (PKC-ε). PKC-ε promotes cell survival and protects hearts against various stresses. However, it is unclear whether or not the reduction in cardiac PKC-ε expression plays a causal role in DIC and in particular the potential underlying mechanism whereby PKC-ε may protect against DIC. C57BL/6 mice (8–10-week-old) were either treated with DOX administered intraperitoneally for a duration of 4 weeks to produce cardiotoxicity, or untreated in which mice received the same volume of saline. In vitro, neonatal rat ventricle cardiomyocytes were exposed to DOX for 24 h in the absence or presence of adenovirus overexpressing PKC-ε. Cardiomyocytes in a subgroup were treated with sirtuin-1 (SIRT1) selective inhibitor Ex527. Four weeks after DOX, cardiac contractile function was decreased concomitant with increased serum CK-MB and LDH levels as well as increases in Bax-to-Bcl-2 ratio and Cleaved Caspase 3 proteins expression, while PKC-ε and Sirt1 protein expressions were significantly decreased. In vitro, DOX reduced cardiomyocyte PKC-ε and SIRT1 protein expression, decreased cardiomyocyte viability, and increased LDH release with concomitant increases in oxidative stress and apoptosis. These changes were attenuated by overexpression of PKC-ε. IP study showed that PKC-ε could directly or indirectly bind SIRT1 in cardiomyocytes, and the protect effects of PKC-ε were further canceled by SIRT1 inhibition. In conclusion, activating SIRT1 may represent a major mechanism whereby PKC-ε protects the heart against DOX-induced cell apoptosis and oxidative stress. Graphical Abstract Dox induces cardiotoxicity via inhibiting PKC-epsilon/Sirt1 signaling which can be reversed by PKC-epsilon overexpression.

Effect of high in-situ asymmetric stress on the brittle failure of the boundary of an underground powerhouse - Ben-Guo He; Shi-Chen Qiu; Xia-Ting Feng; En-Rong Liu; Tao Chen; Shencun Yan (Bulletin of Engineering Geology and the Environment, 2025)

Contribution of microbial necromass to soil organic carbon and its influencing factors during plantation recovery in a subtropical rocky desertification region - Junjie Lei; Xiaoqian Gao; Ting He; Zongxin Liu; Wende Yan; Peng Dang (Applied Soil Ecology, 2025)

Capillary flow of hybrid mode for enhancement of flow rate on μTADs - Yixi Shi; Haonan Li; Hao Chen; Xionghui Li; Muyang Zhang; Qinghao He; Jie Zhou; Jiahua Zhong; Xinyi Chen; Huiru Zhang; Lok Ting Chu; Weijin Guo (Analytica Chimica Acta, 2025)

Hsa_circ_0006260 Mediates Trophoblast Function by Fibronectin Type III Domains Containing Protein 5 via Interacting with miR-770-5p - Wei Liu; Xiao-Chun Hu; He Huang; Meng-Ting He (Biochemical Genetics, 2025)

Deep learning for predicting water saturation using rock physics analysis and geostatistics theory: A case study of the Psh8 in GFZ area, Ordos Basin - Yong-gang Wang; Ya-ting Wang; De-yong Zhao; Ke-han Cai; Wei-fang Liu; Yu-ting He (Applied Geophysics, 2025)

Characterisation of an anticomplement polysaccharide BP-S1 from seeds of Brucea javanica - Xiao He; Ting Tan; Shilin Yang; Yulin Feng; Quan Wen (Natural Product Research, 2025)

External voltage regulates hydrogen and vivianite recovery from fermentation liquid in microbial electrolysis cell equipped with iron anode: Performance and mechanism - Ting Zhao; Zhihong Liu; Zhengtong Guo; Xiaoyun Yin; Wenhai Zhu; Zhangwei He; Wenzong Liu; Xiuping Yue; Aijuan Zhou (Journal of Environmental Management, 2025)

Long-term study of Citrus changshan-huyou Y.B. Chang essential oil: Chemical transformations and their impact on antibacterial efficacy - Wenbin Xiao; Jiajing Guo; Yanjiao Fu; Zixuan Li; Tongping Zhang; Mingwang He; Ting Liu; Yangbo Xiao; Xuebo Shang; Fuhua Fu; Gaoyang Li; Donglin Su; et al. (Food Chemistry, 2025)

Rational design of alginate lyase ALYI1 for improving the antioxidant activity of the alginate oligosaccharides - Jin-Ping Huang; Jin-Xin Zhao; Ming-jing Zhang; Jiru Han; Ya-Tong Han; Xue-Ting Wang; Tian-Bao Wu; Jun-Nan He; Cai-Mei Chen; Yan-Xia Zhou (Food Chemistry, 2025)

Exposure-effect of PFOS and PFOA on lung function: An integrated approach with epidemiological, cellular, and animal studies - Jia-Xin Zhou; Xiao-Di Qin; Xuan Liu; Wan-Ting He; Mohammed Zeeshan; Shyamali C. Dharmage; Jennifer Perret; Dinh Bui; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Prediction of chlorination degradation rate of emerging contaminants based on machine learning models - Yufan Du; Ting Tang; Dehao Song; Rui Wang; He Liu; Xiaodong Du; Zhi Dang; Guining Lu (Environmental Pollution, 2025)

Pore space optimization of hybrid ultramicroporous material for exceptional one-step C2H4 purification from C2H2/CO2/C2H4 mixture - Hong-Xiang Nie; Hong-Wei Chen; Ting Wang; Hongliang Huang; Qiang Gao; Mei-Hui Yu; Jian Zhu; Li-Bo Li; Zhenjie Zhang; Ze Chang; Xian-He Bu (Chemical Engineering Journal, 2025)

Knitted forming material with a lock-ring structure for individual puncture protection - Xuliang Yu; Ting Su; Xinhua Liang; Honglian Cong; Haijun He; Gaoming Jiang; Pibo Ma (Chemical Engineering Journal, 2025)

New perspectives on water chemistry classification of travertine/tufa - Qunwei Dai; Ting Zhang; Dejun An; Jingwen He; Jie Cui; Qiongfang Li; Ronglin Xu; Faqin Dong; Zheng Dang; Qianxi Song (Applied Geochemistry, 2025)

Physical contraction strategy for large-scale fabrication of reduced graphene oxide-coated solid phase microextraction fibers - Linlin Wei; Jianyun Sun; Xingguo Wang; Ting Qi; Aiying Song; Rong Liu; Xinghe He (Analytica Chimica Acta, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Dynamic analysis of fungal community and metabolome associated with postharvest diseases in banana peel under natural condition - Ping Yi; Ming Zhao; Fang Huang; Li Li; Jian Sun; Lihong Xie; Dongning Ling; Jiemin Li; Min Huang; Ting Gan; Yayuan Tang; Changbao Li; et al. (Postharvest Biology and Technology, 2025)

Faceted-nanorods morphologies V2O5 nanostructures for enhanced CO2 photocatalytic conversion to CH4 under UV irradiation - Chih-Chiang Wang; An-Ya Lo; Yi-Jen Huang; Han-Chang Shih; Fuh-Shien Shieu; Tzu-Hsien Tseng; He-Ting Tsai (Journal of Environmental Chemical Engineering, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Do phenolic contents relate to their in-vitro cytotoxicity against colorectal cancer cell lines from Calvatia lilacina (puffball mushroom)? - Jie-Ling Cao; Jie-He Guo; Will Leung; Ya-Ting Liu; I-Lin Tsai; Shu-Ling Huang; Yi-Sheng Wang; Yin-Hung Lai (Food Bioscience, 2025)

Surface display of aspartate ammonia-lyase from Lactobacillus paracasei on Pichia pastoris - Chen-Chi Chang; Yi-Hao Huang; Hua-Kun Fu; Kai-Wei Chang; Shih-Hsuan Chen; Yu-Ting Yu; Xin-Ying Lau; Jhih-Ying Ciou; He-Yuan Hsieh; Yung-Ju Chen; Lu-Sheng Hsieh (World Journal of Microbiology and Biotechnology, 2025)

A haplotype-resolved genome assembly of tetraploid Medicago sativa ssp. falcata - Wanying Li; Xuanzhao Li; Wei Li; Haibo Yang; Diandian Guo; Ting Guo; Yingying Meng; Qiang He; Hao Lin; Huilong Du; Lifang Niu (Science China Life Sciences, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Targeting ferroptosis for the treatment of female reproductive system disorders - Rui Ye; Yi-ming Mao; Yi-ran Fei; Yue Shang; Ting zhang; Zhe-zhong Zhang; Yong-lin Liu; Jun-yu Li; Shi-liang Chen; Yi-bo He (Journal of Molecular Medicine, 2025)

Intelligent decoding platform for peptide sequences: SERS detection via high affinity self-assembled silver nanoparticles and machine learning analysis - Ting Zhang; Yingying He; Chengming Li; Huan Yao; Mingxu Zhang; Yang Li (Analytica Chimica Acta, 2025)

Replication factor C4, which is regulated by insulin-like growth factor 2 mRNA binding protein 2, enhances the radioresistance of breast cancer by promoting the stemness of tumor cells - Xiao-Yu Zhu; Pi-Song Li; Hui Qu; Xing Ai; Zi-Ting Zhao; Jia-Bei He (Human Cell, 2025)

Btn2p influences arginine metabolism and ethanol tolerance in Saccharomyces cerevisiae during Huangjiu fermentation - Ruosi Fang; Ting Xia; Shuhui Wu; Jiamin He; Gongnian Xiao (Food Bioscience, 2025)

Bayesian enhanced graph neural networks: Refining design spaces for hollow concrete components with optimum mechanical performance - Alexander Lin; Hanmo Wang; Wei He; Shawn Owyong; Huan Ting Chen; Tam H. Nguyen (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Sulfurized anthracene as a new cathode material for highly reversible magnesium storage - Xi Chen; Sibylle Riedel; Sirshendu Dinda; Ting Wang; Fangfang He; Xiaojian Tu; Jinfeng Peng; Hans Joachim Räder; Björn Schmidt; Raiker Witter; Zhenyou Li; Maximilian Fichtner; et al. (Chemical Engineering Journal, 2025)

Human activities dominated terrestrial productivity increase over the past 22 years in typical arid and semiarid regions of Xinjiang, China - Xin He; Fei Zhang; Ting Zhou; Yue Xu; Yangjing Xu; Chi Yung Jim; Brian Alan Johnson; Xu Ma (CATENA, 2025)

Lake level variability on the Northeastern Tibetan Plateau linked to interaction between Westerlies and Asian monsoon since the last deglaciation - Xueyun Ma; Zhifu Wei; Gen Wang; Ting Zhang; Pengyuan Zhang; Kaikang Liang; Zengguang Guo; Shangkun Li; Xiaomei Zhang; Jianzhen Chen; Zelong Li; Wei He; et al. (CATENA, 2025)

Codon Usage Bias: A Potential Factor Affecting VGLUT Developmental Expression and Protein Evolution - Yiran Zhao; Yu Zhang; Jiaxing Feng; Zixian He; Ting Li (Molecular Neurobiology, 2025)

Diagnostic accuracy of Xpert MTB/RIF Ultra for detecting pulmonary tuberculosis and rifampicin resistance: a systematic review and meta-analysis - Man-Qing Wang; Ya-Fang Zheng; Yu-Qi Hu; Jin-Xia Huang; Zi-Xin Yuan; Zu-Yan Wu; Lu-Fang Huang; Chu-Ting Tang; Feng-Yi Zhang; Yan Chen; Jin-Ke He; Xu-Guang Guo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Identification of novel CDH23 heterozygous variants causing autosomal recessive nonsyndromic hearing loss - Baoqiong Liao; Wuming Xie; Rutian Liu; Qi Zhang; Ting Xie; Dan Jia; Shuwen He; Hailong Huang (Genes & Genomics, 2025)
Background Hearing loss adversely impacts language development, acquisition, and the social and cognitive maturation of affected children. The hearing loss etiology mainly includes genetic factors and environmental factors, of which the former account for about 50–60%. Objective This study aimed to investigate the genetic basis of autosomal recessive non-syndromic hearing loss (NSHL) by identifying and characterizing novel variants in the CDH23 gene. Furthermore, it seeks to determine the pathogenic potential of the noncanonical splice site variant c.2398-6G > A. Methods Comprehensive clinical evaluation and whole-exome sequencing (WES) were performed on the girl. The WES analysis revealed two novel variants in the CDH23 gene, associated with nonsyndromic deafness 12 (DFNB12). To further explore the pathogenicity of these variants, functional studies involving in vivo splicing analysis were performed on the novel noncanonical splice site variant, c.2398-6G > A, which was initially classified as a variant of uncertain significance (VUS). Results Whole-exome sequencing of the patient identified two compound heterozygous variants in CDH23 : c.2398-6G > A, a noncanonical splice site variant, and c.6068C > A (p. Ser2023Ter), a nonsense mutation. In vitro splicing assays demonstrated that c.2398-6G > A caused aberrant splicing, leading to a frameshift (p. Val800Alafs*6) and the production of a truncated protein, as confirmed by structural protein analysis. The study revealed novel mutations as likely pathogenic, linking both variants to autosomal recessive NSHL. Conclusions Our analyses revealed novel compound heterozygous mutations in CDH23 associated with autosomal recessive NSHL, thereby expanding the mutational landscape of CDH23 -related hearing loss and increasing knowledge about the CDH23 splice site variants.

The Systematic Analysis of the Impact of China Water Improvement and Fluoride Reduction Project on Children - Bo Yang; Feiqing Wang; Xu Yang; Jinyang Cheng; Juan Chen; Bingbing Li; Ying Zhou; Xiaoxu Chen; Bo Wei; Xiaoshuang Yuan; Ting Tian; Dongxin Tang; et al. (Biological Trace Element Research, 2025)

Inhibition of the canonical Wnt/β-catenin pathway interferes with macropinocytosis to suppress pseudorabies virus proliferation - Chongyang Wang; Ting Wang; Qingrun He; Qili Hou; Liuyuan Duan; Ruochen Hu; Yu Han; Yongchun Yang; Houhui Song; Zengqi Yang (Veterinary Microbiology, 2025)

Rupture directivity and seismogenic structures of strong aftershocks in the northeastern rupture zone of the 2008 Wenchuan earthquake - Ting Liu; Xiaohui He; Yipeng Zhang; Zhiliang Liu; Wenjun Zheng; Peizhen Zhang; Yi Wang (Tectonophysics, 2025)

Plasma proteomics identifies proteins and pathways associated with incident depression in 46,165 adults - Jujiao Kang; Liu Yang; Tianye Jia; Wei Zhang; Lin-Bo Wang; Yu-Jie Zhao; Jia You; Yue-Ting Deng; Yi-Jun Ge; Wei-Shi Liu; Yi Zhang; Yi-Lin Chen; et al. (Science Bulletin, 2025)

Organic-inorganic geochemistry and paleontology reveal the Paleocene paleoecology and source rock development in the Lishui-Jiaojiang Sag, East China Sea Shelf Basin - Jiahao He; Dujie Hou; Youjun Tang; Ting Wang; Jun Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Facile preparation of MOFs composite nanofibers for the efficient separation of Co(II) from wastewater - Yang Luo; Xiayuan Zhu; Guang Yang; Qi Zou; Ting Liang; Yushuang Chen; Bai He; Guoyuan Yuan (Journal of Water Process Engineering, 2025)

Mechanistic insights for efficient removal of intracellular and extracellular antibiotic resistance genes by iron-based nanocopper: Intracellular oxidative stress and internalization of nanocopper - Hao Wang; Ping Yu; Xujing Guo; Wenguo Wang; Lan Wang; Hongwei Zhang; Liangwei Deng; Hongnan Yang; Ting He; Peike Wu; Yunhong Zhang (Journal of Hazardous Materials, 2025)

Nitrogen, sulfur, iron, and microbial communities co-shape the seasonal biogeochemical behaviors of As and Sb in coastal tidal flat wetlands associated with rivers - Shen Kong; Ting Luo; Lili Xue; Yang Zou; Shijing Dai; Dongmei He (Journal of Hazardous Materials, 2025)

Adsorption‐enhanced Fenton catalytic membrane for high-efficiency, high-quality drinking water treatment - Yulun He; Mingrui He; Ting Liu; Dongwei Lu; Zongyao Zhou; Jun Ma (Journal of Hazardous Materials, 2025)

Preparation of wood formaldehyde-free adhesive by concentrated water delignification black liquor - Ting Zhang; Jianli Tan; Yongqi Li; Yexuan Tang; Yan He; Yuanyuan Ge; Xuemin Cui (Journal of Cleaner Production, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Solid phase extraction-surface enhanced Raman spectroscopy (SPE-SERS) test of antibiotic residues in Milk based on au@ MIL-101 NPs - Mengyue Gao; Qiao Chen; ZhiHao Li; YiFang Zhan; LiHua Wang; Ting He; Qi Yao; Fengmei Jin; Jiming Hu (Food Chemistry, 2025)

Enhancing the formation of functional glucosinolate degradation products in fermented broccoli stalk by-product with lactic acid bacteria - Qinghang Wu; Daqun Liu; Jianming Zhang; Ting Li; Haiyue Niu; Xiaoting Xin; Shengming Zhao; Chengyun He; Chengcheng Zhang (Food Chemistry, 2025)

Leveraging zebrafish models for advancing radiobiology: Mechanisms, applications, and future prospects in radiation exposure research - Ting Xu; Fan Liu; Jiaxuan He; Peiye Xu; Junying Qu; Hanbing Wang; Jinghui Yue; Qinsi Yang; Wei Wu; Guoming Zeng; Da Sun; Xia Chen (Environmental Research, 2025)

Influence of the main controlling factors on the tangential restitution coefficient of rockfall impact - Zhong-Min Ji; Ting-Hui Wang; Jie Wu; Fa-Quan Wu; Zhen-Hua Li; Dong-Po Wang; Yi-Ju Tang; Chang-Le Zhao; Qing-He Niu (Engineering Geology, 2025)

Targeted volatile fatty acid production based on lactate platform in mixed culture fermentation: Insights into carbon conversion and microbial metabolic traits - Jun Yin; Jianyu Jin; Jing Wang; Hongwei Fang; Xiaoqin Yu; Jie He; Ting Chen (Bioresource Technology, 2025)

Acoustic insulation optimization of walls and panels with functional graded hollow sections using graph transformer evaluator and probability-informed genetic algorithm - Hanmo Wang; Tam H Nguyen; Zhuyin Lu; Febi Rhiana; Dickson Fong; Wei He; Shawn Owyong; Huan Ting Chen; Alexander Lin (Building and Environment, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

First data on aquaculture of the narrow-barred Spanish mackerel (Scomberomorus commerson) in ponds - Pei-Sheng Chiu; Yeong-Torng Chu; Yen-Hung Lee; Jia-Shin He; Li-Chi Cheng; Ting-Jeng Chang; Jinn-Rong Hseu; Jinn-Shing Weng; Feng-Cheng Wu (Aquaculture International, 2025)

Involvement of copper in cell death and cancer - Jiahao Xie; Yue Su; Wenzhong Shang; Yanfang Wu; Junjia He; Ting Li; Yeyu Shen; Youni Zhang; Xiangmin Tong; Qiong Bian (Apoptosis, 2025)

Effects of Enterocytozoon hepatopenaei infection on intestinal immune defense and physiological processes of Penaeus vannamei - Zheng Cao; Chuanyu He; Zhipeng Yin; Caiyi Chen; Fan Li; Dongchun Yan; Ting Li; Linrui Chang; Lingjun Si (Frontiers in Marine Science, 2025)
As the main pathogen causing growth retardation, EHP is considered to be mainly parasitic in the hepatopancreas of shrimp. However, the intestines of shrimp infected with EHP frequently exhibit syndromes such as jejunum and white midgut. Therefore, the challenge experiment was carried out in this study to compare the differences in intestinal histology, digestion and absorption, immune defense and oxidative stress of P. vannamei between the control group and EHP infection group. Histological analysis showed that EHP infection significantly damaged the intestine of the shrimp, including intestinal villus rupture and outer membrane impairment. Concurrently, EHP infection can trigger intestinal immune response, and the expression of key immune genes like Toll, myeloid differentiation factor, anti-lipopolysaccharide factor, and Relish was significantly enhanced, while the expression of IMD and alkaline phosphatase was suppressed. Additionally, antioxidant genes manganese superoxide dismutase, catalase, glutathione peroxidase, glutathione-S-transferase, and nuclear factor E2-related factor 2 were up-regulated to varying extents in EHP infection group, and the contents of lipid peroxides and malondialdehyde were heavily accumulated. Moreover, the expression levels of key genes involved in nutrient absorption, transport and synthesis, such as glucose transporter 1, Na + -K + ATPase, fatty acid synthase, acetyl-CoA carboxylase, rapamycin kinase, mTOR regulation-related protein, eukaryotic translation initiation factor 4E binding protein, ribosomal protein S6 kinase, were significantly up-regulated. However, the activities of amylase, lipase, and trypsin were inhibited in EHP infection group throughout the experiment. In summary, EHP infection damaged the intestine of P. vannamei , accompanied by immune response and oxidative stress. At the same time, nutrient transport and synthesis pathways were activated, while digestive enzyme activities were inhibited, indicating that in order to maintain survival, shrimps must accelerate material transport. Unfortunately, it remains in a state of nutrient deficiency that ultimately affects growth.

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Exploring synergistic efficiency of air pollution and carbon reduction and its influencing factors: Insights from China - Yiting Yang; He Xu; Xue Yang; Yi Zhang; Ting Liu (Resources, Conservation and Recycling, 2025)

Observation, distribution, and characteristics of microplastics in sediments from the estuary and river network areas of Pearl River Delta, China - Haijun He; Ting Yu; Xueli Chen; Yujie Yang; Feng Li; Huayang Gan (Regional Studies in Marine Science, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Recycling Fe and improving organic pollutant removal via in situ forming magnetic core-shell Fe3O4@CaFe-LDH in Fe(II)-catalyzed oxidative wastewater treatment - Ting He; Jie Sun; Liangwei Deng; Jialin Ming; Changwei Hu (Journal of Environmental Sciences, 2025)

Magnetic field inhibited the deterioration of frozen dough via promoting the interaction between starch and gluten - Ting-Shi He; Han Tao; Mei Liu (Journal of Cereal Science, 2025)

On-demand removable hydrogel film derived from gallic acid-phycocyanin and polyvinyl alcohol for fruit preservation - Wei Gong; Ting-qi Yang; Wan-ying He; Yu-xin Li; Jiang-ning Hu (Food Chemistry, 2025)

Engineered food-derived hesperetin as heterojunction photosensitizer for inhibiting Staphylococcus aureus and degrading patulin, and its application in perishable strawberries - Ting Du; Jiazhen Wang; Zhenqing Guo; Yu He; Shaochi Wang; Xiang Li; Nannan Qiu; Jianlong Wang; Wentao Zhang (Food Chemistry, 2025)

Multi-dimensional digital core simulation based research on heat transfer characteristics of multiphase fluids - Yanchi Liu; Baiquan Lin; Ting Liu; Jiahao He (Computers and Geotechnics, 2025)

Microfluidic fabrication of lipid nanoparticles for co-delivery of siRNA and hydroxychloroquine: An engineered theranostic platform for enhanced breast cancer treatment - Lu Huang; Wenli Guo; Ting Zhao; Yanru Feng; Yue Li; Qingqing An; Chenxi Li; Yiwei Tian; Huaxing Zhang; Chenming Zhou; Yanan Sun; Chaoxing He; et al. (Chemical Engineering Journal, 2025)

Elastomer foam templated three dimensional hybrid hydrogels for heterogeneously integrated stretchable electronics - Changqing Qin; Qian Wang; Ting Fang; Lin Wang; Cheng Yang; Yong Lin; Chong Bai; Wenqiang He; Likang Ding; Jinheng Zhang; Dongchan Li; Desheng Kong (Chemical Engineering Journal, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

Highly degradable bio-based plastic with water-assisted shaping process and exceptional mechanical properties - Jingjing Wang; Yuan Liang; Yuhan Chen; Hai Wan; Wenbin Jin; Ting Luo; Yuwei Chen; Peng Wei; Shuohan Huang; Yong He; Yanping Wang; Yumin Xia (Carbohydrate Polymers, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Interactive effects of microplastics and cadmium on soil properties, microbial communities and bok choy growth - Mengxiao Li; Jiaju He; Xiaofeng Chen; Xiaoman Dong; Shuang Liu; Christopher W.N. Anderson; Minghua Zhou; Xuesong Gao; Xiaoyan Tang; Di Zhao; Ting Lan (Science of The Total Environment, 2024)

Distribution and driving mechanisms of antibiotic resistance genes in urbanized watersheds - Ping Yu; Xujing Guo; Wenguo Wang; Lan Wang; Hongwei Zhang; Liangwei Deng; Hongnan Yang; Ting He; Peike Wu; Yunhong Zhang (Science of The Total Environment, 2024)

The evolution of cropping structure in prehistoric Xizang - Yanren Wang; Qi Yang; Jishuai Yang; Shalini Sharma; Yunzhe Huang; Wei He; Tinley Tsring; Shihua Hu; Songtao Chen; Qingli Sun; Ting You; Zhengquan Gu; et al. (Science Bulletin, 2024)

Dynamic aromatics: Evaluating fragrance quality shifts and implementation of real-time rapid detection in Hedychium cut flowers during senescence - Yiwei Zhou; Qin Wang; Xue Wei; Ting Gao; Farhat Abbas; Fulong Yan; Jingjuan He; Yunyi Yu; Rangcai Yu; Yanping Fan (Postharvest Biology and Technology, 2024)

Numerical examination of wave forces on partially submerged horizontal circular cylinders near free surface - Hong-Fei Mao; Yuan-Ting Yang; Jin-Bo Lin; Zhong-Bing Zhou; Ming He (Ocean Engineering, 2024)

Pore and fracture characteristics and diagenetic evolution mechanisms of low-maturity lacustrine shales from the Paleogene Shahejie Formation in the Jiyang Depression, Bohai Bay Basin, Eastern China - Quan Rao; Zhiliang He; Tian Dong; Weiqing Wang; Xunyao Wang; Liqiang Rao; Ting Wang; Liwen Huang (Marine and Petroleum Geology, 2024)

Environmental taxes promote the synergy between pollution and carbon reduction: Provincial evidence from China - Yiting Yang; Yi Zhang; Yuxin Zhang; Ting Liu; He Xu (Journal of Environmental Management, 2024)

Midseason drying increases soil dissolved organic carbon and rice yield via soil cbbL bacteria - Jinsong He; Wei Wang; Ting Liu; Wende Yan; Xiaohong Wu; Junjie Lei; Yichen Xu; Yazhen Chen; Yuxin Yao; Wenqiong Jiang; Zhentao Shen; Asma Farooq (Journal of Environmental Management, 2024)

Fe, N-doped carbon dots/RF in self-Fenton cascade reaction: Improved photodegradation mechanism and toxicity evaluation - Yuanyuan Yang; Guijing Chen; Jie Yu; Min He; Mingze An; Ting Lei; Qingqing Qin; Shuhao Qin (Journal of Environmental Chemical Engineering, 2024)

Development of arcuate faults and controls on hydrocarbon accumulation in the Tiantai slope, Xihu Depression, East China Sea basin - Lang Yu; Yixin Yu; Yiming Jiang; Wei Zou; Gongcheng Zhang; Xianjun Tang; Ting Tang; Xinxin Liang; Xinjian He; Dongxia Chen (Journal of Asian Earth Sciences, 2024)

Molecular insights into the anti-spoilage effect of salicylic acid in Favorita potato processing - Wenhua Wang; Liping Hong; Zhijun Shen; Mingqiong Zheng; Hongyan Meng; Ting Ye; Zhikai Lin; Lianghua Chen; Ying Guo; Enming He (Food Chemistry, 2024)

Urine is better for rare earth elements bimonitoring in long-term exposed population: An exposure-response relationship study - Zhizhou He; Li Liu; Ting Wang; Cailan Zhou; Xuewei Zhang; Nan Wu; Mengmeng Xu; Jianqiong Gao; Bin Li; Yonglan Wang; Qiang Zhi; Chenguang Zhang; et al. (Environmental Research, 2024)

Riparian restoration in sandy zones with alfalfa as pioneer plant in initial stage of soil and water bioengineering - Lin Yang; Lina Cao; Ting Cao; Hongyong Xiang; Chunguang He; Jia Li; Xiaoyue Zhang; Sayramgul Abu Dumusa; Yu Leng (Ecological Engineering, 2024)

An aptamer-integrated conductive microneedle biosensor for real-time transdermal cortisol monitoring - Li Yue Jing; Yangkai Fan; Bo Zhi Chen; Dehui Li; Yu Ting He; Guo Liang Zhang; Ling Liang; Jie Du; Yuan Wang; Xin Dong Guo (Chemical Engineering Journal, 2024)

Enhanced ethanol synthesis via CO2 hydrogenation using La-Doped CuFeOx catalysts - Kailong He; Yetong Li; Zhenbo Li; Jie Chen; Li Tan; Ting Qiu; XinGang Li; Xiaoxun Ma; Chengyi Dai (Chemical Engineering Journal, 2024)

Template-free approach to fabricate uniformly N-doped hierarchical porous carbons from waste oil - Jin Lu; Ting Song; Yan Chen; Suyun Xu; Pinjing He; Hua Zhang (Waste Disposal & Sustainable Energy, 2024)

Comparative study of sampling strategies for machine learning-based landslide susceptibility assessment - Xiao-Dong Liu; Ting Xiao; Shao-He Zhang; Ping-He Sun; Lei-Lei Liu; Zu-Wu Peng (Stochastic Environmental Research and Risk Assessment, 2024)

A Contrastive-Learning-Based Deep Neural Network for Cancer Subtyping by Integrating Multi-Omics Data - Hua Chai; Weizhen Deng; Junyu Wei; Ting Guan; Minfan He; Yong Liang; Le Li (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Hg-mining-induced soil pollution by potentially toxic metal(loid)s presents a potential environmental risk and threat to human health: A global meta-analysis - Li Chen; Xiaosan Luo; Haoran He; Ting Duan; Ying Zhou; Lequn Yang; Yi Zeng; Hansong Chen; Linchuan Fang (Soil Ecology Letters, 2024)

Prevalence of Tick Infection with Bartonella in China: A Review and Meta-analysis - Yuhua Wang; Ruishan Li; Ting Yin; Zhen He; Zhenhua Lu; Zhongjun Shao; Yong Long (Acta Parasitologica, 2024)

Studies on the Role of MAP4K2, SPI1, and CTSD in Osteoporosis - Chao Sun; Wanxiong He; Leipeng Wang; Ting Hao; Xiaolong Yang; Wei Feng; Yonggang Wu; Chenyang Meng; Zhi Wang; Xiaofeng Chen; Mingqi Sun; Feng Zheng; et al. (Cell Biochemistry and Biophysics, 2024)

Study on safe construction distance of the Lushan Tunnel with Class V surrounding rock based on discrete element - Peng He; Zheng-Hu Ma; Feng Jiang; Gang Wang; Yong-Gang Zhang; Zhi-Yong Xiao; Cheng-Cheng Zheng; Wen-Peng Yuan; Zhi-Qiang Yan; Ting-Fang Liu; Ying Zhuang; Xiao-Qian Ding (Applied Geophysics, 2024)

Log Facies Identification via Dynamic Classifier Selection - Mei He; Shu-wen Guo; Ting He; Hao Li; Chun-xiang Guo; Yu Zhong; Fang-fang Wang (Applied Geophysics, 2024)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Advancement and challenges in tea brewing: The dynamic principles, influencing factors, innovative processing technologies and pollutants - Yunqing Liu; Xinyu Feng; Ting Gao; Yani Pan; Helin Lv; Ming Chen; Yili Shen; Wan Zhu; Yuye Yao; Lixin He; Shuying Gong; Fangyuan Fan; et al. (Trends in Food Science & Technology, 2024)

Sappanone A ameliorates acute lung injury through inhibiting the activation of the NF-κB signaling pathway - Jing Du; Piao Zhou; Xin Zhao; Yu-Ting He; Cheng-Shi He; Rui-Yu Wang (Toxicology and Applied Pharmacology, 2024)

Metabolomics reveals the potential mechanism of La(III) promoting enrichment of Sodium hydrogen arsenate and Roxarsone in Solanum nigrum L. - Yining Zhu; Ruijie Che; Zhongtian Dong; Ting Guo; Xin He; Jining Li; Fenghe Wang (Science of The Total Environment, 2024)

High emission of black carbon in heavy-duty diesel vehicles: Insights from microscopic operating conditions - Ting Chen; Xiao He; Liqiang He; Yan You; Lewei Zeng; Mingqiu Gao; Fengbin Wang; Yihuan Cao; Zhenhua Li; Xuan Zheng; Shaojun Zhang; Guangyi Xu; et al. (Science of The Total Environment, 2024)

Ensuring China's food security in a geographical shift of its grain production: Driving factors, threats, and solutions - Shi Xue; Zhou Fang; Carena van Riper; Wei He; Xuxia Li; Fan Zhang; Ting Wang; Changgao Cheng; Qin Zhou; Zhongde Huang; Yang Bai (Resources, Conservation and Recycling, 2024)

Investigating the role of membrane lipid composition differences on spray drying survival in Lactobacillus bulgaricus using non-targeted Lipidomics - Fengzhi Qiao; Shaolei Wang; Jian He; Weilian Hung; Xia Ma; Pimin Gong; Jiadong Li; Ting Sun; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2024)

Recombinant Bacillus subtilis expressing functional peptide and its effect on blunt snout bream (Megalobrama amblycephala) in two state of stress - Wei Xiong; Guang-zhen Jiang; Chao-fan He; Hao-kun Hua; Mian-ting Du; Wan-ting Huang; Hui-ting Xu; Mei-ting Zhou; Xi Wang; Hui-xing Guo; Ai-min Wang; Shang-zhi Sun; et al. (Fish & Shellfish Immunology, 2024)

Microplastics exposure disrupts nephrogenesis and induces renal toxicity in human iPSC-derived kidney organoids - Bingrui Zhou; Yunliang Wei; Long Chen; Anxiu Zhang; Ting Liang; Jian Hui Low; Zhizhen Liu; Sheng He; Zhongyuan Guo; Jun Xie (Environmental Pollution, 2024)

Bioaerosols emission from source facilities in a wastewater treatment plant: Critical exposure time and sensitivity analysis - Yi-ning Hu; Wei-di Wan; Jun-ting Wu; Tian-nuo Lai; Wajid Ali; Shan-shan He; Sai Liu; Xiang Li; Zhe-ren Tang; Cheng-yun Wang; Cheng Yan (Environmental Pollution, 2024)

Formation of Na-O bonds in NaZn(BH4)3·xTHF for enhancing sodium conductivity - Qijing Gao; Dingguan Liang; Ting He; Liang Tang; Minghong Wu; Wenqian Chen (Chemical Engineering Journal, 2024)

Novel orthodontic adhesives with antibacterial, mineralization and fluorescence properties for enamel demineralization prevention - Ting Luo; Jiarong Yan; Lingyun Cao; Xiaozhu Liao; Nannan Wang; Fang Hua; Hong He (Chemical Engineering Journal, 2024)

Removal of antibiotics from aquaculture wastewater using a continuous flow/EC/PMS coupled system - Lulu Long; Jingrong Li; Ting Hou; Min Liu; Yuhuan Lin; Xingwei Zhu; Chao Chen; Gang Yang; Jingsong He (Chemical Engineering Journal, 2024)

Dissecting the temporal genetic networks programming soybean embryo development from embryonic morphogenesis to post-germination - Yen-Ching Wang; Wei-Hsun Hsieh; Liang-Peng Lin; Meng-Hsun He; Ya-Ting Jhan; Chu-Jun Huang; Junpeng Zhan; Ching-Chun Chang; Tzung-Fu Hsieh; Jer-Young Lin (Plant Cell Reports, 2024)

Integral validation for two-fluid thermal hydraulic system analysis code LOCUST 1.2 based on LOFT L9-3 experiment - Zhenyu Feng; Dalin Zhang; Yiwen Chen; Yangchun Pu; Shichang Yun; Sisi Wang; Caihong Xu; Dongyu He; Ting Wang; Wenxi Tian; Suizheng Qiu; Guanghui Su (Annals of Nuclear Energy, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

High-resolution comprehensive regional development mapping using multisource geographic data - Linxin Li; Ting Hu; Guangyi Yang; Wei He; Hongyan Zhang (Sustainable Cities and Society, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Changhsingian (Lopingian, Permian) radiolarian paleobiogeography on and around the Yangtze Platform - Yi-Fan Xiao; Kai-Yue Wang; Wei-Hong He; Noritoshi Suzuki; Ke-Xin Zhang; Ting-Lu Yang; Shun-Bao Wu (Palaeoworld, 2024)

PML_30: A high resolution (30 m) estimates of evapotranspiration based on remote sensing model with application in an arid region - Ting Liang; Changming Li; Yufen He; Jing Tan; Wenqian Niu; Yaokui Cui; Hanbo Yang (Journal of Hydrology, 2024)

High-value terminal treatment: Utilizing copper slag heat in the manufacture of copper-containing weathering steel - Jun Hao; Zhi-he Dou; Xing-yuan Wan; Song Qi; Kun Wang; Ting-an Zhang (Journal of Cleaner Production, 2024)

Nitrogen removal performance and functional microbial communities evolution in a continuous up-flow fixed bed anammox system - Zheng Lu; Junting Zhao; Zhenjun Wu; Ting Guo; Menghan Wang; Xiaomin Li; Dongjin Wan; Zhimin Du; Qiaochong He (Journal of Environmental Chemical Engineering, 2024)

Preventive and reparative potentials of heat-inactivated and viable commensal Bacillus pumilus SE5 in ameliorating the adverse impacts of high soybean meal in grouper (Epinephelus coioides) - Bi-Yun Zhang; Qing-Jie Nie; Jian-Ming Xu; Guo-He Cai; Ji-Dan Ye; Ting Jin; Hong-Ling Yang; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Preparation and characterization of micro-cellular melamine foam supported SiO2 aerogel for building thermal insulation - Yapeng Wang; Zhaofeng Chen; Lixia Yang; Chengqian Bian; Zongjin Du; Ting Xu; Haisheng Wu; Jianxun Zhang; Lihua He (Energy and Buildings, 2024)

A Janus evaporator based on Donnan effect for efficient solar thermal desalination - Hai-Tao Ren; Hong-Bei He; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin (Desalination, 2024)

Silencing of the Phytoene Desaturase (PDS) gene through virus infection using Tobacco Rattle Virus in Physalis grisea - Hai-Meng Zhang; Ru-Xin Wang; Yi-Ting Liu; Peng-Wei Jing; Qiao-Fang Shi; Yi-He Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Nitrogen availability and its related enzyme activities affect microbial residue nitrogen accumulation during Chinese fir plantation development - Junjie Lei; Peng Dang; Xiaoqian Gao; Yichen Xu; Ting He; Zongxin Liu; Wende Yan (Applied Soil Ecology, 2024)

Retraction Note: Energy financing, energy projects retrofit and energy poverty: a scenario-analysis approach for energy project cost estimation and energy price determination - RuiYing Wang; Ting Cao; XingYuan He; YiMin Fan (Environmental Science and Pollution Research, 2024)

One undescribed glycoside benzofuran derivative and a new p -hydroxybenzoate glycoside from the leaves of Illicium dunnianum Tutcher - Xiao-qing He; Hai-bo Li; Ting Li; Xin-yin Chen; Zhen-zhong Wang; Xin-sheng Yao; Wei Xiao; Yang Yu (Natural Product Research, 2024)

Synergistic promotion of antimony transformation in the interaction of Acidithiobacillus ferrooxidans and pyrite by driving the formation of reactive oxygen species and secondary minerals - Peng He; Quanliu Yang; Chunyao Gu; Mengfei Liu; Penghui Li; Ting Luo; Jiancheng Chen; Junwen Chen; Jianyu Zhu; Min Gan (Chemosphere, 2024)

Fast neural distance field-based three-dimensional reconstruction method for geometrical parameter extraction of walnut shell from multiview images - Ting Huang; Yongliang Bian; Ziang Niu; Mohamed Farag Taha; Yong He; Zhengjun Qiu (Computers and Electronics in Agriculture, 2024)

Nitrogenous fertilizer plays a more important role than cultivars in shaping sorghum-associated microbiomes - Fangfang Li; Anqi Sun; Xiaoyan Jiao; Dan-Ting Yu; Peixin Ren; Bing-Xue Wu; Peng He; Li Bi; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

The impact of China certified emission reduction market resumption on manufacturers' stock market valuations: The role of OSCM factors - Fu Jia; Ting Pan; Qin He; Lujie Chen (Journal of Cleaner Production, 2024)

Preparation of gelatin-starch shell-yolk microspheres by water-in-water emulsion method: Effects of starch crystal type and cross-linking - Zhirenyong Zhang; Xiaoxue He; Ting Yan; Yuyu He; Chaoxi Zeng; Shiyin Guo; Qingming Li; Huiping Xia (Food Hydrocolloids, 2024)

High-rate pig manure substitution enhances comammox Nitrospira abundance and diversity in the Cinnamomum camphora coppice planting soils - Luyuan Sun; Jie Zhang; Jia Liu; Jiao Zhao; Ting Zhang; Fengyi Han; Zi-Yang He; Yongxin Lin (European Journal of Soil Biology, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Crustal and uppermost mantle structures of the North American Midcontinent Rift revealed by joint full-waveform inversion of ambient-noise data and teleseismic P waves - Bin He; Kai Wang; Tianshi Liu; Ting Lei; Nanqiao Du; Suzan van der Lee; Fiona Ann Darbyshire; Andrew Frederiksen; Hejun Zhu; David Lumley; Henry Halls; Qinya Liu (Earth and Planetary Science Letters, 2024)

Amorphous bimetallic-organic framework enable accelerated redox kinetics and polysulfide trapping for lithium-sulfur batteries - Jingkun Bi; Lu Chen; Xiao Yan; Jian Guo; Ya Tang; Ma Jian; Shuo Meng; Kexuan Liao; Jia Yu; Wenli Yao; Ting He; Hongbin Zhao (Chemical Engineering Journal, 2024)

Pressure-driven molecule implantation enabling ultrahigh-rate and ultralong-life zinc ion batteries - Ting He; Jiugang Hu; Yuqing Luo; Pengfei Zhu; Shan Cai; Guoqiang Zou; Hongshuai Hou; Xiaobo Ji (Chemical Engineering Journal, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Identification of odorant-binding proteins in the antennal transcriptome of Cotesia ruficrus and the response of CrufOBP3 and CrufOBP17 to maize volatiles - Wen-Wen Wang; Peng-Yang He; Bi-Ting Tian; Tong-Xian Liu; Xiang-Feng Jing; Shi-Ze Zhang (Journal of Pest Science, 2024)

Quaternary phosphonium AIEgens nanoparticles as innovative agents for developing latent fingerprints - He-Shin Huang; Yu-Hsin Chen; Wei-Ting Chien; Mei-Yu Yeh (Analytica Chimica Acta, 2024)

Identification and characterization of a novel type II toxin-antitoxin system in Aeromonas veronii - Caihong Ji; Ting He; Binbin Wu; Xiaomei Cao; Xiaping Fan; Xia Liu; Xiaodan Li; Miao Yang; Jihan Wang; Ling Xu; Shengbiao Hu; Liqiu Xia; et al. (Archives of Microbiology, 2024)

Metaphire guillelmi exhibited predominant capacity of arsenic efflux - Xiayun Zang; Mingyue He; Yuanzhou Xu; Ting Che; Fei Wang; Jingjing Xu; Huijuan Zhang; Feng Hu; Li Xu (Chemosphere, 2024)

Evaluation of a new real-time source apportionment system of PM2.5 and its implication on rapid aging of vehicle exhaust - Pei-Ting Yao; Xing Peng; Li-Ming Cao; Li-Wu Zeng; Ning Feng; Ling-Yan He; Xiao-Feng Huang (Science of The Total Environment, 2024)

Universal materials model of deep-learning density functional theory Hamiltonian - Yuxiang Wang; Yang Li; Zechen Tang; He Li; Zilong Yuan; Honggeng Tao; Nianlong Zou; Ting Bao; Xinghao Liang; Zezhou Chen; Shanghua Xu; Ce Bian; et al. (Science Bulletin, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

The investigation of the influence of wave spectrum pattern on focused breaking waves profile and kinematics evolution - Hangwei Zhang; Ting Cui; Guanghua He; Penglin Jing; Chuankai Zhao; Zhengxiao Luan (Ocean Engineering, 2024)

Complete genome sequence of a novel Pseudomonas sp. IT1137 isolated from Antarctic intertidal sediment showing potential for alkane degradation at low temperatures - Hui-Yan Ge; Yi-He Zhang; Yong-Qiang Hu; Wei Han; Yu Du; Ting Hu; Yin-Xin Zeng (Marine Genomics, 2024)

Bio-inspired gradient poly(lactic acid) nanofibers for active capturing of PM0.3 and real-time respiratory monitoring - Guiying Zhu; Cunmin Wang; Ting Yang; Na Gao; Yifan Zhang; Jintuo Zhu; Xinjian He; Jiang Shao; Shihang Li; Mingming Zhang; Shenghui Zhang; Jiefeng Gao; et al. (Journal of Hazardous Materials, 2024)

Factor analysis of geogas data for concealed lithium deposits detection and false anomalies identification in Jiajika area - Zhiqiang Xu; Bin Liang; Hui Jiang; Ting Liu; Qiubo Wang; Jiaxin Duan; Bangqiao Chen; Yangpiao He (Journal of Geochemical Exploration, 2024)

A review of amendments for simultaneously reducing Cd and As availability in paddy soils and rice grain based on meta-analysis - Frank Stephano Mabagala; Ting Zhang; Xibai Zeng; Chao He; Hong Shan; Cheng Qiu; Xue Gao; Nan Zhang; Shiming Su (Journal of Environmental Management, 2024)

The reduction of antibiotic resistance genes in lettuce and soil amended with sewage sludge compost - Ling Luo; Xin Zhao; Jie Hu; Petros Gikas; Yan He; Yinlong Xiao; Shihuai Deng; Yanzong Zhang; Chengyi Huang; Wei Zhou; Ting Lan; Ouping Deng (Journal of Environmental Chemical Engineering, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Corrigendum to “Size distribution and lung-depostion of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays” [Environ. Pollut. 336 (2023) 122437] - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2024)

Cube2sph : A toolkit enabling flexible and accurate continental-scale seismic wave simulations using the SPECFEM3D_Cartesian package - Tianshi Liu; Kai Wang; Yujiang Xie; Bin He; Ting Lei; Nanqiao Du; Ping Tong; Yingjie Yang; Catherine A. Rychert; Nicholas Harmon; Giovanni Grasselli; Qinya Liu (Computers & Geosciences, 2024)

Robust and tunable hydrogels strengthened by dynamic amphiphilic ionic domains - Wenzhe Xiao; Ting He; Wanting Zhao; Wenjin Li; Yichen Liu; Cheng Li; Qizhen Luo; Weidong Zhao; Jipeng Yan; Jian Sun (Chemical Engineering Journal, 2024)

Low-temperature one-step synthesis of surfactant-free ZnO nanoparticles for efficient glycolysis of PET - Zhifeng Ao; Jiaxing Deng; Wenxuan He; Ting Liu; Jiexin Wang; Hongyun Yang; Zhigang Shen; Jianfeng Chen (Chemical Engineering Journal, 2024)

Rational design of Bacteria-Targeted and Photo-Responsive MOF gel with antibacterial and anti-inflammatory function for infected wound healing - Qiao-Tong He; Peipei Qian; Xin-Yi Yang; Qiancheng Kuang; Yue-Ting Lin; Wei Yi; Tianzhao Tian; Yue-Peng Cai; Xu-Jia Hong (Chemical Engineering Journal, 2024)

Elucidating the role of polar functional groups in fluorinated polymer artificial interphase for stable lithium anodes - Kun Li; Zhen Wang; Borui Yang; Ting Li; Bin Li; Jiahao Chen; Zhongfu Yan; Miao He; Anjun Hu; Jianping Long (Chemical Engineering Journal, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Coupling Coordination of Green Sugarcane Production and Comprehensive Social Development in Chinese Sugar Industry - Yuan Xie; Ting He; Xinyi Chen; Qibin Wu; RuKai Chen; Niandong Chen; Youxiong Que (Sugar Tech, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

TAG encodes an adenine nucleotide transport protein that regulates leaf color in rice - Xinfang Zhang; Wenwen Xiao; Mi Wei; Ruhui Wu; Jinyan Liu; Jing You; Jianyan Mu; Jichao Zhang; Yanling Yang; Yitao Wan; Yinghua Lin; Guanghua He; et al. (Euphytica, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

The permeability evolution mechanism of ore-bearing strata during acid in-situ leaching of uranium: A case study of Bayanwula uranium mine in Inner Mongolia of China - Ting He; Jinhui Liu; Bei Zhao; Huichun Gong; Zhangzhe Feng; Shiyu Liu (Journal of Contaminant Hydrology, 2024)

Elucidate the molecular basis of ampholytic chitosan as a high-performance cryoprotectant to myosin denaturation: The importance of saccharide charges - Ting Zhang; Yongxin Teng; Yaluan He; Yonghui Li; Yue Yuan; Bin Li; Yijie Chen; Xiangwei Zhu (Food Hydrocolloids, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Dabrafenib alleviates hepatotoxicity caused by lenvatinib via inhibiting the death receptor signaling pathway - Xinyu Tao; Mengting Cheng; Xiangliang Huang; Jiajia Chen; Yunfang Zhou; Ting Liu; Xiaochun Zheng; Nonger Shen; Yiwen Zhang; Peihua Luo; Qiaojun He; Hao Yan; et al. (Toxicology Letters, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Carbon emissions changes of animal husbandry in China: Trends, attributions, and solutions: A spatial shift-share analysis - Ruirui Du; Ting He; Aftab Khan; Minjuan Zhao (Science of The Total Environment, 2024)

Rare earth elements applied to phytoremediation: Enhanced endocytosis promotes remediation of antimony contamination with different valence levels in Solanum nigrum L. - Ding He; Ting Guo; Zhongtian Dong; Jining Li; Fenghe Wang (Science of The Total Environment, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

Changes in the lithosphere, atmosphere, and ionosphere before and during the Mw = 7.7 Jamaica 2020 earthquake - Dedalo Marchetti; Kaiguang Zhu; Alessandro Piscini; Essam Ghamry; Xuhui Shen; Rui Yan; Xiaodan He; Ting Wang; Wenqi Chen; Jiami Wen; Yiqun Zhang; Yuqi Cheng; et al. (Remote Sensing of Environment, 2024)

Two-way predation between larvae of Spodoptera frugiperda and Spodoptera litura - Yuxue Wang; Natasha Isabel Tanatsiwa Mbiza; Yonghao Yu; Haoran Zhang; Zongwei Hu; Ting Liu; Yi Wang; Yi Zhang; Xincheng Luo; Longyan Chu; Yazhen Yang; Xiangping Wang; et al. (Journal of Asia-Pacific Entomology, 2024)

CoNi alloy nanoparticles confined by N-doped carbon matrix with tailored d-Band center for electrocatalytic hydrogen evolution - Ting Zhang; Zhen He; Li Yin; Wei Gao; Yuxin Wang (Fuel, 2024)

Petrophysical characterization of coal subjected to cyclic N-methylpyrrolidone treatment based on two-dimensional NMR T1-T2 - He Li; Qingyi Guo; Meng Liu; Jiexin Lu; Yidu Hong; Ting Liu; Zheng Wang (Fuel, 2024)

Metabolic behavior of Aspergillus oryzae in salt-reduced soy sauce and its regulation for the brewing process - Xinyun Zhou; Ting Guo; Hadiatullah Hadiatullah; Yulin Lu; Jing He; Guozhong Zhao (Food Bioscience, 2024)

Emulsion stability enhancement against storage and environment stresses using complex plant protein and betanin - Qin Geng; Ting Hu; Jun Chen; Changhong Li; Ti Li; Xuemei He; Jialong Han; Chengmei Liu; Taotao Dai (Food Bioscience, 2024)

Enhanced exosome capture in urine using aptamer-modified temperature-responsive polymer for sensitive early detection of bladder cancer - Min Liu; Kezhen Yi; Yaran Zhang; Fei Long; Xin Hu; Gaihua Jia; Ting Xiao; Xianqun Xu; Yongwei Duan; Hongjie Shi; Zhipeng Yao; Tongzu Liu; et al. (Chemical Engineering Journal, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Metagenomic and transcriptomic analysis revealing the impact of oxytetracycline and ciprofloxacin on gut microbiota and gene expression in the Chinese giant salamander (Andrias davidianus) - Ting Ye; Shumao He; Jiahui Li; Jianlin Luo; Sixue Yang; Peng Wang; Can Li (Aquatic Toxicology, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

Popcorn-like bimetallic palladium/platinum exhibiting enhanced peroxidase-like activity for signal enhancement in lateral flow immunoassay - Qianqian Cao; Yiqin Liu; Lin Yang; Ting Tan; Jian He; Weiwei Chen; Ranhui Li; Weiguo Wang (Analytica Chimica Acta, 2024)

Photobiomodulation therapy moderates cancer cachexia-associated muscle wasting through activating PI3K/AKT/FoxO3a pathway - Yonghua Li; Yibing Chen; Yuan Liao; Ting Huang; Qing Tang; Chengsi He; Liu Xu; Haocai Chang; Hongsheng Li; Quentin Liu; Dongming Lai; Qing Xia; et al. (Apoptosis, 2024)

Industry chain and challenges of microalgal food industry-a review - Yuanhao Chen; Honghao Liang; Hong Du; Valentina Jesumani; Weiling He; Kit-Leong Cheong; Tangcheng Li; Ting Hong (Critical Reviews in Food Science and Nutrition, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Nutrient comparisons among the noble scallops Chlamys nobilis with three different shell colours to provide advices for consumers to choose high-quality food - Cheng He; Ting Ye; Junxi Zeng; Hongkuan Zhang; Yizhou Sun; Chuanxu Zhang; Xianqing He; Jiale Qiu; Huaiping Zheng (Frontiers in Marine Science, 2024)
Introduction In aquatic animals, colors not only reflect their sensory qualities but also affect their nutritional components and market price. Noble scallop Chlamys nobilis is an importantly economical bivalve cultured in the south sea of China and renowned for its various shell colors. Methods In this study, the nutrient compositions were compared among golden, yellow, and brown shell colour noble scallops originating from the same population for breeding new varieties. Results Among three colour scallops, there is no significant difference in the content of moisture, ash, and total protein content (TPC) but significant differences in total carotenoid content (TCC), total lipid content (TLC), and amino acids (AAs) ( P < 0.05), with the TCC of the brown scallop being about 2 times lower. The yellow scallop contained the same nutrients as TCC, TLC, ∑PUFAs (including EPA and DHA), and n-3/n-6 as the golden scallop, and both were significantly higher than the brown scallop ( P < 0.05), but they had significantly lower ∑SFAs than the latter ( P < 0.05). The correlation between the nutrient indices and the shell color of scallops was 67.5%. There is a significantly positive correlation between TCC and ∑PUFAs ( P < 0.05), while a significantly negative correlation exists between TCC and ∑SFAs ( P < 0.05). More importantly, the yellow scallop had significantly higher EAAs and FAAs than the golden scallop ( P < 0.05). Discussion This study showed that the yellow noble scallop not only enriched in carotenoids and PUFAs but also enriched in amino acids. Therefore, the yellow scallop is more benefit to human health, which can provide high-quality food for customers.

Four new compounds from fruits of Hypericum patulum Thunb. - Li Jiang; Xue Ma; Yang Wang; Jingyi Xue; Zhilong He; Yushan Nie; Ting Liu; Yong-Lin Wang; Yongjun Li (Natural Product Research, 2024)

Selective breeding in the noble scallop (Chlamys nobilis) for low-temperature resistance to reduce overwintering losses - Chuanxu Zhang; Cheng He; Yizhou Sun; Hongkuan Zhang; Ting Ye; Faxin Liu; Hongyu Ma; Shengkang Li; Huaiping Zheng (Aquaculture, 2024)

Potential retention of dissolved organic matter by soil minerals during wetland water-table fluctuations - Simin Wang; Ting Liu; Erxiong Zhu; Chen He; Quan Shi; Xiaojuan Feng (Water Research, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Lemon essential oil nanoemulsions: Potential natural inhibitors against Escherichia coli - Wenbin Xiao; Zhipeng Gao; Ting Liu; Weiming Zhong; Sifan Jiang; Mingwang He; Fuhua Fu; Gaoyang Li; Donglin Su; Jiajing Guo; Yang Shan (Food Microbiology, 2024)

Branched polymer grafted loose nanofiltration membrane with high surface potential for dye desalination - Yuanyuan Yang; Guijing Chen; Ting Lei; Qingqing Qin; Shaowen Huang; Ming He; Shuhao Qin (Desalination, 2024)

Curcumin attenuates aflatoxin B1-induced ileum injury in ducks by inhibiting NLRP3 inflammasome and regulating TLR4/NF-κB signaling pathway - Hang Pan; Ting Hu; Ying He; Gaolong Zhong; Shaofeng Wu; Xuanxuan Jiang; Gan Rao; Yanli You; Zhiyan Ruan; Zhaoxin Tang; Lianmei Hu (Mycotoxin Research, 2024)

The influence of in situ purification system on pathogen in the river fed by the drainage of sewage plant - Zhao-xu Peng; Yu He; Lu-ji Yu; Zi-yao Hao; Ting-mei Li; Li-kun Gu; Li Wang (Environmental Science and Pollution Research, 2024)

LSD1 promotes the FSH responsive follicle formation by regulating autophagy and repressing Wt1 in the granulosa cells - Zijian Zhu; Meina He; Tuo Zhang; Ting Zhao; Shaogang Qin; Meng Gao; Wenji Wang; Wenying Zheng; Ziqi Chen; Longping Liu; Ming Hao; Bo Zhou; et al. (Science Bulletin, 2024)

Complete genome sequence of the novel Antarctic Oceanisphaera sp. IT1–181 that carried five plasmids - Yong-Qiang Hu; Yi-He Zhang; Wei Han; Ting Hu; Yu Du; Yin-Xin Zeng (Marine Genomics, 2024)

Complex pollution of Fluoroquinolone antibiotics and metal oxides/metal ions in water: a review on occurrence, formation mechanisms, removal and ecotoxicity - Zeting Chen; Guilin He; Ting You; Tuqiao Zhang; Baozhen Liu; Yonglei Wang (Journal of Environmental Chemical Engineering, 2024)

Tunable schiff-based networks with different bonding sites for enhanced photocatalytic activity under visible-light irradiation: The effects of steric hindrance - Han Wang; Piao Xu; Eydhah Almatrafi; Ziwei Wang; Chengyun Zhou; Ting Xiong; Hong Qin; Yangzhuo He; Hailan Yang; Zhuotong Zeng; Guangming Zeng (Environmental Research, 2024)

Enhancing compound confidence in suspect and non-target screening through machine learning-based retention time prediction - Dehao Song; Ting Tang; Rui Wang; He Liu; Danping Xie; Bo Zhao; Zhi Dang; Guining Lu (Environmental Pollution, 2024)

Tough, self-healing and injectable dynamic nanocomposite hydrogel based on gelatin and sodium alginate - Li Ting Gao; Yong Mei Chen; Yasir Aziz; Wei Wei; Xin Yi Zhao; Yuan He; Jianhui Li; Haopeng Li; Hideyuki Miyatake; Yoshihiro Ito (Carbohydrate Polymers, 2024)

Stem Cell-Based Strategies: The Future Direction of Bioartificial Liver Development - Lei Feng; Yi Wang; Yu Fu; Ting Li; Guolin He (Stem Cell Reviews and Reports, 2024)

Quantitative Trait Locus Mapping Combined with RNA Sequencing Reveals Candidate Genes for Chlorophyll Content in Oilseed Rape Leaves - Li Yuanhong; Cai Lei; He Yuqi; Ding Ting; Tian Entang; Zhang Jiefu; Yu Kunjiang; Chen Zhuo; Wang Xiaodong (Journal of Plant Growth Regulation, 2024)

Sorption of cadmium by layered double hydroxides: Performance, structure-related mechanisms, and sequestration stability assessment - Dong Zhang; Zhishun Zhong; Zilong Liu; Shichong He; Jun Lin; Yiyan Lv; Ting Lü; Ying Pan; Huading Shi; Hongting Zhao (Chemosphere, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Global prevalence of Plasmodium infection in wild birds: A systematic review and meta-analysis - Wei-Lan Yan; He-Ting Sun; Yi-Chen Zhao; Xin-Wen Hou; Miao Zhang; Quan Zhao; Hany M. Elsheikha; Hong-Bo Ni (Research in Veterinary Science, 2024)

Transcriptomics combined with physiological analysis provided new insights into the Zn enrichment capacity and tolerance mechanism of Dendrobium denneanum Kerr - Yuanyuan Liu; Erya Xu; Yijun Fan; Linlong Xu; Jie Ma; Xuebing Li; Hui Wang; Siyu He; Ting Li; Yujiao Qin; Jingtao Xiao; Aoxue Luo (Plant Science, 2024)

RNAi-mediated silencing of the neverland gene inhibits molting in the migratory locust, Locusta migratoria - Jia Lv; Qi-Hui He; Peng Shi; Feng Zhou; Ting-Ting Zhang; Min Zhang; Xue-Yao Zhang (Pesticide Biochemistry and Physiology, 2024)

A data-driven approach to determine the distinct contribution of human factors to different types of maritime accidents - Laihao Ma; Xiaoxue Ma; Ting Wang; Yulan Zhao; He Lan (Ocean Engineering, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Effect of Resveratrol on physicochemical structure evolution of lignite during spontaneous combustion - Xianhua Shen; He Li; Jiexin Lu; Yi Lu; Meng Liu; Baiquan Lin; Wei Yang; Yidu Hong; Ting Liu; Zheng Wang (Fuel, 2024)

Modulation of pea protein isolate nanoparticles by interaction with OSA-corn starch: Enhancing the stability of the constructed Pickering emulsions - Xin-Yue Liu; Ting-Shi He; Chen-Chen Wang; Bao-Cai Xu; Ran Feng; Bao Zhang; Han Tao (Food Chemistry, 2024)

Mowing and nitrogen management guidelines for superior rice ratoon yields - Deqiang Qi; Yalong Chen; Matthew Tom Harrison; Ke Liu; Huiling He; Changli Ji; Kai Du; Jiaqi Wang; Yajun Sun; Guilong Yu; Ye Liu; Yafan Zhao; et al. (Field Crops Research, 2024)

Common vetch intercropping with reduced irrigation ensures potato production by optimizing microbial interactions - Ting Che; Xinyue Zhang; Mingyue He; Fei Wang; Na Li; Xiayun Zang; Zhuoliang Xiao; Yuanzhou Xu; Feng Hu; Yongfeng Ren; Huijuan Zhang; Li Xu; et al. (Field Crops Research, 2024)

Forming enlarged grain and fixed boundary via a two-step surface modification to achieve stable inverted perovskite solar cells - Hongkang Gong; Qi Song; Ting Zhu; Chenhui Zhang; Xinghai Huang; Xiping Jing; Fangtian You; Chunjun Liang; Zhiqun He (Chemical Engineering Journal, 2024)

A novel process for efficient utilization of bamboo fiber resource in dissolving pulp production by fiber fractionation: Laboratory study and mill trials - Yishan Liu; Chenglong Fu; Lianli Liu; Ke Wang; Ting Wu; Jingjing Wu; Junmiao Zhang; Zhanghong Xie; Yinchuan Xu; Chao Duan; Yonghao Ni; Zhibin He (Bioresource Technology, 2024)

Mechanisms of Ferritinophagy and Ferroptosis in Diseases - Siqi Li; Ping Huang; Feifan Lai; Ting Zhang; Jiaqi Guan; Haitong Wan; Yu He (Molecular Neurobiology, 2024)

Novel compound heterozygous variants in FANCI cause premature ovarian insufficiency - Lili Cao; Xinmiao He; Jiayi Ren; Canxin Wen; Ting Guo; Fan Yang; Yingying Qin; Zi-Jiang Chen; Shidou Zhao; Yajuan Yang (Human Genetics, 2024)

Prediction of state transitions in 3D core dynamics and xenon transients based on dynamic mode decomposition - Wenhuai Li; Sitao Peng; Jinggang Li; Qingyun He; Tao Wang; Yijun Zhang; Haoliang Lu; Ting Wang; Peng Ding (Annals of Nuclear Energy, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

On the development and measurement of human factors complex network for maritime accidents: A case of ship groundings - Laihao Ma; Xiaoxue Ma; Ting Wang; Liguang Chen; He Lan (Ocean & Coastal Management, 2024)

Tanshinone IIA modulates cancer cell morphology and movement via Rho GTPases-mediated actin cytoskeleton remodeling - En-yu Liang; Meng-he Huang; Ying-ting Chen; Peng-wei Zhang; Yan Shen; Xiao-xin Tu; Wei-ye Chen; Yi Wang; Jun Yan; Hong-yu Wang; Pei-feng Ke; Xian-zhang Huang (Toxicology and Applied Pharmacology, 2024)

The E3 ubiquitin ligase RNF135 modulates chemotherapy resistance to oxaliplatin for colorectal cancer by modulating autophagy - Zhen Qiu; Shuyan He; Boyi Lu; Yuejun Sun; Ting Zhang; Wei Lv; Dong Shen (Tissue and Cell, 2024)

Comprehensive characterization of speciated volatile organic compounds (VOCs), gas-phase and particle-phase intermediate- and semi-volatile volatility organic compounds (I/S-VOCs) from Chinese diesel trucks - Xiao Zhang; Xiao He; Yihuan Cao; Ting Chen; Xuan Zheng; Shaojun Zhang; Ye Wu (Science of The Total Environment, 2024)

Lanthanum promotes Solanum nigrum L. growth and phytoremediation of cadmium and lead through endocytosis: Physiological and biochemical response, heavy metal uptake and visualization - Ting Guo; Ding He; Yongqiang Liu; Jining Li; Fenghe Wang (Science of The Total Environment, 2024)

Urbanization and weather dynamics co-dominated the spatial-temporal variation in pCO2 and CO2 fluxes in small montanic rivers draining diverse landscapes - Zhaoyin Qing; Xiaofeng Wang; Xianxiang Li; Chen Jian; Yi Yang; Ting Zhou; Tingting Liu; Shuangshuang Liu; Yafang Huang; Yixin He (Journal of Environmental Management, 2024)

Degradation on BDE209 in the soil by kaolin-supported sulfurized nano-zero-valent iron activated persulfate system: Insights mechanism and DFT calculations - Fang Zhu; Huijie Lu; Ting Li; Siying He; Huishen Xu (Journal of Environmental Chemical Engineering, 2024)

Enhancing the NOx storage and hydrothermal stability of Pd/SSZ-13 passive NOx adsorbers by regulating the Al distributions - Yinan Wang; Xuteng Zhao; Ting Chen; Zuwei Zheng; Rijing Zhan; He Lin (Fuel, 2024)

Integrated analysis of transcriptome and metabolome reveals the regulatory mechanism of largemouth bass (Micropterus salmoides) in response to Nocardia seriolae infection - Fen Dong; Yu-Long Sun; Yuan-Xin Qian; Qiang Chen; Jia-Le He; Ji-Teng Wang; Tao Han; Xiu-Mei Zhang; Yu-Ting Deng (Fish & Shellfish Immunology, 2024)

Triclocarban exhibits higher adipogenic activity than triclosan through peroxisome proliferator-activated receptors pathways - Jia-Da Zhang; Sen He; Ting-Ting He; Chuan-Hai Li; Bing-Hua Yan; Yuan Yang; Jian Yang; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Environmental Pollution, 2024)

Visible-light-driven photo-Fenton oxidation enhanced by Fe/Bi-nanocrystal phase transformation as a universal way for various organic pollutants mineralization - Tulai Sun; Zi-Yan Jin; Bin Deng; Gan He; Qiong-Yu Wang; Mian Hu; Zhangliang Han; Zhaoke Zheng; Jun Zhao; Jimmy Yun; Jia Zhao; Yihan Zhu; et al. (Chemical Engineering Journal, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Complete decomposition of poly(ethylene terephthalate) by crude PET hydrolytic enzyme produced in Pichia pastoris - Chun-Chi Chen; Xian Li; Jian Min; Ziyin Zeng; Zhiyuan Ning; Hailin He; Xin Long; Du Niu; Rouming Peng; Xin Liu; Yu Yang; Jian-Wen Huang; et al. (Chemical Engineering Journal, 2024)

Activated carbon-boosted BiOI in CO2 adsorption and electron transfer for photothermally catalyzed CO2 oxidative dehydrogenation of propane - Run-Qing Miao; Zhen-Hong He; Bao-Ting Wu; Jiajie Liu; Sen-Wang Wang; Kuan Wang; Weitao Wang; Lu Li; Zhao-Tie Liu (Chemical Engineering Journal, 2024)

Effect of Electroacupuncture Stimulation on Proliferation and Differentiation of Endogenous Neural Stem Cells in Rats with Spinal Cord Injury - Qilong Deng; Lili Ma; Yu Yang; Ting Chen; Luding Zhan; Qiaoqiao He; Yingying Jiang; Lizhong Ma (Molecular Neurobiology, 2024)

RETRACTED ARTICLE: Carnosic acid nanocluster-based framework combined with PD-1 inhibitors impeded tumorigenesis and enhanced immunotherapy in hepatocellular carcinoma - Wenhua Wu; Yaping Li; Xiaokang Wu; Junrong Liang; Weiming You; Xinyuan He; Qinhui Feng; Ting Li; Xiaoli Jia (Functional & Integrative Genomics, 2024)

Accurate Shortwave Radiation Simulation with a Two-Layer Aerosol Model in Xinjiang Region - Guan Huang; Yonghang Chen; Qiong Liu; Pengtao Wang; Qianshan He; Qing He; Shuai Li; Weiling Shao; Ting Fan (Journal of Meteorological Research, 2024)

Quantitative SARS-CoV-2 exposure assessment for workers in wastewater treatment plants using Monte-Carlo simulation - Cheng Yan; Yi-ning Hu; Zi-cheng Gui; Tian-nuo Lai; Wajid Ali; Nian-hong Wan; Shan-shan He; Sai Liu; Xiang Li; Ting-xu Jin; Zaheer Ahmad Nasir; Sonia Garcia Alcega; et al. (Water Research, 2024)

Understanding the traffic flow in different types of freeway tunnels based on car-following behaviors analysis - Ting Shang; Jiaxin Lu; Ying Luo; Song Wang; Zhengyu He; Aobo Wang (Tunnelling and Underground Space Technology, 2024)

Foliar spraying of lanthanum activates endocytosis in lettuce (Lactuca sativa L.) root cells, increasing Cd and Pb accumulation and their bioaccessibility - Xinyan Zong; Yongqiang Liu; Xinying Lin; Ding He; Zhongtian Dong; Ting Guo; Jining Li; Hongbo Li; Fenghe Wang (Science of The Total Environment, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Breathing in danger: Unveiling the link between human exposure to outdoor PM2.5-bound polycyclic aromatic hydrocarbons and lung cancer risk in an urban residential area of China - Lord Famiyeh; Honghui Xu; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Hang Xiao; Lei Tong; Chunrong Jia; Qingjun Guo; Jun He (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Exploring the effect of photobiomodulation and gamma visual stimulation induced by 808 nm and visible LED in Alzheimer's disease mouse model - Hao Xu; Ziyi Luo; Renlong Zhang; Iuliia Golovynska; Yanxia Huang; Soham Samanta; Ting Zhou; Shaowei Li; Bingang Guo; Liwei Liu; Xiaoyu Weng; Jun He; et al. (Journal of Photochemistry and Photobiology B: Biology, 2024)

Energy conservation and emission reduction through utilization of latent heat of copper slag for iron and copper recovery - Jun Hao; Zhi-he Dou; Ting-an Zhang; Xing-yuan Wan; Kun Wang (Journal of Cleaner Production, 2024)

A tailored slow-release film with synergistic antibacterial and antioxidant activities for ultra-persistent preservation of perishable products - Liang Zhang; Wenze Wang; Wen He; Ting Du; Shaochi Wang; Puyuan Hu; Bing Pan; Jingjing Jin; Lizhi Liu; Jianlong Wang (Food Chemistry, 2024)

MicroRNA-217-5p triggers dopaminergic neuronal degeneration via autophagy activation under Atrazine exposure - Bingyun Li; Yujia Jiang; Ting Wang; Weiwei Liu; Xiaojuan Chen; Jinyi He; Zeyu Du; Ruijiao Yang; Danxiu Miao; Yanshu Li (Environmental Pollution, 2024)

Boosting promote C2 products formation in electrochemical CO2 reduction reaction via phosphorus-enhanced proton feeding - Shitao Han; Wei Xia; Shuaiqiang Jia; Jiapeng Jiao; Ting Yao; Xue Dong; Min Wang; Jianxin Zhai; Jiahao Yang; Yijun Xie; Xueqing Xing; Haihong Wu; et al. (Chemical Engineering Journal, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Efficiently Removal of Tetracycline from Water by Fe3O4-sludge Biochar - Liyang Zhao; Peixi He; Qian Li; Honghui Pan; Ting Xie; Shiyong Huang; Shaohua Cao; Xixiang Liu (Water, Air, & Soil Pollution, 2024)

Estimating the complete in-situ stress tensor along deep tunnels with frequent rockbursts near a steep valley - Ben-Guo He; Hong-Pu Li; Xia-Ting Feng; Xiang-Rui Meng (Bulletin of Engineering Geology and the Environment, 2024)

Transcriptome analysis of Iris japonica var. variegata for chlorophyll and photosynthesis-related pathways involved in white–green striped leaves - Xiaofang Yu; Linjie Yue; Qingling He; Shurui Li; Yunhao Zheng; Zhiwen Wang; Heting Wang; Rouzhi Liu; Xin Huang; Xue Xiao; Lijuan Yang; Ting Lei (Acta Physiologiae Plantarum, 2024)

Long‐term warming increased carbon sequestration capacity in a humid subtropical forest - Xujun Liu; Zhiyang Lie; Peter B. Reich; Guoyi Zhou; Junhua Yan; Wenjuan Huang; Yingping Wang; Josep Peñuelas; David T. Tissue; Mengdi Zhao; Ting Wu; Donghai Wu; et al. (Global Change Biology, 2024)
Tropical and subtropical forests play a crucial role in global carbon (C) pools, and their responses to warming can significantly impact C‐climate feedback and predictions of future global warming. Despite earth system models projecting reductions in land C storage with warming, the magnitude of this response varies greatly between models, particularly in tropical and subtropical regions. Here, we conducted a field ecosystem‐level warming experiment in a subtropical forest in southern China, by translocating mesocosms (ecosystem composed of soils and plants) across 600 m elevation gradients with temperature gradients of 2.1°C (moderate warming), to explore the response of ecosystem C dynamics of the subtropical forest to continuous 6‐year warming. Compared with the control, the ecosystem C stock decreased by 3.8% under the first year of 2.1°C warming; but increased by 13.4% by the sixth year of 2.1°C warming. The increased ecosystem C stock by the sixth year of warming was mainly attributed to a combination of sustained increased plant C stock due to the maintenance of a high plant growth rate and unchanged soil C stock. The unchanged soil C stock was driven by compensating and offsetting thermal adaptation of soil microorganisms (unresponsive soil respiration and enzyme activity, and more stable microbial community), increased plant C input, and inhibitory C loss (decreased C leaching and inhibited temperature sensitivity of soil respiration) from soil drying. These results suggest that the humid subtropical forest C pool would not necessarily diminish consistently under future long‐term warming. We highlight that differential and asynchronous responses of plant and soil C processes over relatively long‐term periods should be considered when predicting the effects of climate warming on ecosystem C dynamics of subtropical forests.

Diversity of fungal communities in the rhizosphere soil of Tamarix chinensis in saline–alkaline wetland - Xiaoyun Qi; Ting Chen; Cheng Ding; Xuemei Chen; Bo He; Wenge Hu (Environment, Development and Sustainability, 2023)

Enhanced visible-light activation of persulfate for the removal of RhB by supported nano-(C,N,B)-tridoped TiO2/copper foam mixed-crystals - Qin Tong; Ting Cai; Jing Yuan; Dannong He (Environmental Science and Pollution Research, 2023)

The dual effect of disodium anthraquinone-2,6-disulfonate (AQDS) on the Cr(VI) removal by biochar: The enhanced electron transfer and the inhibited adsorption - Xue Wang; Peng Zhang; Meixuan Wu; Ting He; Can Li; Lijuan Liu; Shunling Li; Zhaofeng Chang; Di Lang; Wei Du; Hao Li; Bo Pan (Chemosphere, 2023)

Intraspecific variations of leaf hydraulic, economic, and anatomical traits in Cinnamomum camphora along an urban-rural gradient - Cheng Zhang; Nuo Huang; Fengyu Zhang; Ting Wu; Xianjin He; Jianan Wang; Yiyong Li (Science of The Total Environment, 2023)

Cultivation and biogeochemical analyses reveal insights into biomineralization caused by piezotolerant iron-reducing bacteria from petroleum reservoirs and their application in MEOR - Hao Dong; Li Yu; Ting Xu; Yulong Liu; Jian Fu; Yanlong He; Ji Gao; Jiaqi Wang; Shanshan Sun; Yuehui She; Fan Zhang (Science of The Total Environment, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Recycling and reutilization of smelting dust as a secondary resource: A review - Xinxin Liu; Fenghui Wu; Guangfei Qu; Ting Zhang; Minjie He (Journal of Environmental Management, 2023)

Stable ZIF-8-derived iron-immobilized ZnFe/NC catalyst for RhB degradation via persulfate activation - Qin Tong; Ting Cai; Jing Yuan; Dannong He (Journal of Environmental Chemical Engineering, 2023)

Advances in the Effects of Iron-Based Materials on Antibiotics and Resistance Genes in Anaerobic Digestion: Mechanisms, Applications, and Development Prospects - Yuying Zhang; Tianjue Hu; Zhifeng Liu; Chunping Yang; Jamila Aliyeva; Binbin Shao; Qinghua Liang; Qingyun He; Ting Wu; Songhao Luo; Yuan Pan; Chenhui Zhao (Water, Air, & Soil Pollution, 2023)

Numerical Study of Nonlinear Effects on the Performance of the Self-Protected Energy Concentrator - Hangwei Zhang; Ting Cui; Guanghua He (Journal of Marine Science and Engineering, 2023)
Wave concentrators have important application value in ocean engineering. Moreover, the performance of a concentrator on structural protection is important in the context of the complex ocean environment. A series of numerical simulations of the self-protected energy concentrator (SPEC) is performed under nonlinear wave conditions. The SPEC includes eight truncated cylinders arranged in a concentric circle. The performance of SPEC and the distribution of fluid field are studied by establishing a computational fluid dynamics (CFDs) model. It can be concluded that increasing wave steepness can weaken the self-protection performance and concentration effects due to its strong nonlinearity. The wave directions have little effect on the performance of SPEC. In addition, the change based on the target wave number can result in poor performance of SPEC.

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Synergistic effect between electric field and Ce-doped catalysts to promote hydrogen production from ammonia decomposition - Xiaochao Wang; Zijian Zhang; Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Dong Han; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

Insoluble dietary fiber from wheat bran retards starch digestion by reducing the activity of alpha-amylase - Ting He; Xin Zhang; Lei Zhao; Jincheng Zou; Runkang Qiu; Xuwei Liu; Zhuoyan Hu; Kai Wang (Food Chemistry, 2023)

Excellent hydration properties and oil holding capacity of citrus fiber: Effects of component variation and microstructure - Chun-ai He; Jun-ru Qi; Jin-song Liao; Ya-ting Song; Chun-lin Wu (Food Hydrocolloids, 2023)

Lithium impacts the function of hematopoietic stem cells via disturbing the endoplasmic reticulum stress and Hsp90 signaling - Yalin Liu; Yifan Zhao; Jiaojiao Wu; Ting Liu; MengKe Tang; Ye Yao; Peng Xue; Miao He; Yanyi Xu; Peng Zhang; Minghua Gu; Weidong Qu; et al. (Food and Chemical Toxicology, 2023)

Mercury chloride activates the IFNγ-IRF1 signaling in myeloid progenitors and promotes monopoiesis in mice - Mengke Tang; Yifan Zhao; Yue Zhai; Yufan Zhang; Yalin Liu; Ting Liu; Jiaojiao Wu; Leyi He; Ye Yao; Peng Xue; Miao He; Yanyi Xu; et al. (Environmental Pollution, 2023)

Long-term oral tribasic copper chloride exposure impedes cognitive function and disrupts mitochondrial metabolism by inhibiting mitophagy in rats - Wenlan Yu; Xiaoyue Chang; Jianzhao Liao; Jinwen Quan; Siying Liu; Ting He; Gaolong Zhong; Jilei Huang; Zhonghua Liu; Zhaoxin Tang (Environmental Pollution, 2023)

Size distribution and lung-deposition of ambient particulate matter oxidative potential: A contrast between dithiothreitol and ascorbic acid assays - Lord Famiyeh; Chunrong Jia; Ke Chen; Yu-Ting Tang; Dongsheng Ji; Jun He; Qingjun Guo (Environmental Pollution, 2023)

Accurate prediction of the through plane effective thermal conductivity of GDB-MPL composite region in PEMFC with a layered model - Jian Hou; Hongdong Liu; Jiansheng Zhang; Ting He (Chemical Engineering Journal, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

Enhanced poly(3-hydroxybutyrateco-3-hydroxyvalerate) production from high-concentration propionate by a novel halophile Halomonas sp. YJ01: Detoxification of the 2-methylcitrate cycle - Jun Yin; Jincan Yang; Xiaoqin Yu; Ting Chen; Shanying He (Bioresource Technology, 2023)

Failure Modes of Jointed Granite Subjected to Weak Dynamic Disturbance Under True-Triaxial Compression - Ben-Guo He; Lei Wang; Xia-Ting Feng; Rong-Li Zhen (Rock Mechanics and Rock Engineering, 2023)

Insufficient SIRT1 in macrophages promotes oxidative stress and inflammation during scarring - Ting He; Xiaozhi Bai; Yan Li; Dongliang Zhang; Zhigang Xu; Xuekang Yang; Dahai Hu; Juntao Han (Journal of Molecular Medicine, 2023)

NR1 Splicing Variant NR1a in Cerebellar Granule Neurons Constitutes a Better Motor Learning in the Mouse - Ting Tan; Linyan Jiang; Zhengxiao He; Xuejiao Ding; Xiaoli Xiong; Mingxi Tang; Yuan Chen; Yaping Tang (The Cerebellum, 2023)
As an excitatory neuron in the cerebellum, the granule cells play a crucial role in motor learning. The assembly of NMDAR in these neurons varies in developmental stages, while the significance of this variety is still not clear. In this study, we found that motor training could specially upregulate the expression level of NR1a, a splicing form of NR1 subunit. Interestingly, overexpression of this splicing variant in a cerebellar granule cell-specific manner dramatically elevated the NMDAR binding activity. Furthermore, the NR1a transgenic mice did not only show an enhanced motor learning, but also exhibit a higher efficacy for motor training in motor learning. Our results suggested that as a “junior” receptor, NR1a facilitates NMDAR activity as well as motor skill learning.

Capturing Cu2+ and recycling spent Cu-adsorbents as catalyst for eliminating Rhodamine B: reactivity and mechanism - Caiyun Han; Jing Xie; Qin Shi; Liying Liang; Ting Yang; Sufang He (Environmental Science and Pollution Research, 2023)

Breaking the salty spell: Understanding action mechanism of melatonin and beneficial microbes as nature's solution for mitigating salt stress in soybean - Zhenyu Fan; Feifei He; Ting Wu; Bowen Li; Jin Xiao; Zhigang Wang (South African Journal of Botany, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

Labdane and ent-halimane diterpenoids with STAT3-inhibitory activity from Leonurus sibiricus - Chen Wang; Jiao Tian; Chaoge Liu; Yiming He; Jiahang Li; Qiang Zhang; Ting Xiao; Chunfeng Xie; Cheng Yang (Phytochemistry, 2023)

Asymmetry of blue and green water changes in the Yangtze river basin, China, examined by multi-water-variable calibrated SWAT model - Ning Nie; Ting Li; Yiyi Miao; Wanchang Zhang; Huiran Gao; Hongming He; Dengzhong Zhao; Min Liu (Journal of Hydrology, 2023)

Effects of microplastics on functional genes related to CH4 and N2O metabolism in bacteriophages during manure composting and its planting applications - Wei-Kang Deng; Jun-Liang He; Jing-Yuan Chen; Rui-Ting Wu; Si-Cheng Xing; Xin-Di Liao (Journal of Hazardous Materials, 2023)

Adjusting Zn2+ diffusion kinetics and storage capability of MnOOH nanofibers for high-performance cathode of aqueous zinc-ion batteries - Lijuan Chen; Yaoyong Dong; Mengwei Han; Ting Song; Xuejun Zheng; Wenyuan He; Bei Long; Xiongwei Wu; Yong Pei; Xianyou Wang (Chemical Engineering Journal, 2023)

Quantifying ant diversity and community in a subalpine forest mosaic: a comparison of two methods - Chuan-Jing Zhang; Yi-Ting Cheng; Xian-Shu Luo; Yao Chen; Yu-Chao He; Yan-Pang Li; Zhi-Pang Huang; Matthew B. Scott; Wen Xiao (Journal of Insect Conservation, 2023)
Sampling efficiency, composition and detection biases associated with pitfall-trap and sample plot (standardised hand-collecting) methods were compared at seven high montane sites at Lasha Mountain, Yunnan, China. Rarefaction-interpolation curves showed total species diversity and sample coverage from each method were undifferentiated. Permutational multivariate analysis of variance showed highly overlapping communities. However, of all species collected, just 53% of all species found were shared between the two methods; 30% were exclusive to sample plot samples and 17% were exclusive to pitfall traps. Modelled comparisons of species richness (alpha) and proportion of species from the population (beta diversity) showed differences between methods. Permutational multivariate analysis of variance blocked by site showed community composition differed between methods, defined largely by the presence of a few dominant species. Implications for insect conservation : Our findings suggest that results from the two methods cannot be directly compared and are imperfect substitutes to one another. For long-term monitoring of biodiversity in complex forest mosaic systems, we suggest integrating a suite of complementary methods to achieve more complete representation of ant composition and diversity.

Inline phase transition trapping-selective supercritical fluid extraction-supercritical fluid chromatography: A green and efficient integrated method for determining prohibited substances in cosmetics - Binhong He; Jieqing Feng; Jiaqi Liu; Qisheng Zhong; Ting Zhou (Analytica Chimica Acta, 2023)

The cooling models of Earth’s early mantle - Ting He; Qingwen Zhang; Yun Liu (Acta Geochimica, 2023)

RETRACTED ARTICLE: Energy financing, energy projects retrofit and energy poverty: a scenario-analysis approach for energy project cost estimation and energy price determination - RuiYing Wang; Ting Cao; XingYuan He; YiMin Fan (Environmental Science and Pollution Research, 2023)

Drought shifts soil nematodes to smaller size across biological scales - Leilei Lu; Gen Li; Nianpeng He; Huixin Li; Ting Liu; Xianping Li; Joann K. Whalen; Stefan Geisen; Manqiang Liu (Soil Biology and Biochemistry, 2023)

Bisphenol A induced hepatic steatosis by disturbing bile acid metabolism and FXR/TGR5 signaling pathways via remodeling the gut microbiota in CD-1 mice - Ting Hong; Jun Zou; Youming He; Hongmin Zhang; Hao Liu; Haiyan Mai; Jie Yang; Zhuo Cao; Xiaobing Chen; Jiale Yao; Dan Feng (Science of The Total Environment, 2023)

Effective mechanisms in the formation of pool-rimstone dams in continental carbonate systems: The case study of Huanglong, China - Ting Zhang; Qunwei Dai; Dejun An; R. Agustin Mors; Qiongfang Li; Ricardo A. Astini; Jingwen He; Jie Cui; Ruiyang Jiang; Faqin Dong; Zheng Dang (Sedimentary Geology, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

A review of anorexia induced by T-2 toxin - Ting-Yu Huang; Wen-Xi Song; You-Shuang Wang; Yu Liu; Feng-Juan Chen; Yun-He Chen; Yi-Bao Jiang; Cong Zhang; Xu Yang (Food and Chemical Toxicology, 2023)

Association between Di-2-ethylhexyl phthalate and nonalcoholic fatty liver disease among US adults: Mediation analysis of body mass index and waist circumference in the NHANES - Youming He; Jun Zou; Ting Hong; Dan Feng (Food and Chemical Toxicology, 2023)

Dual-vapour-thermal engineering evoking bound water pathways of vanadium oxide for high-rate and durable zinc-ion storage - Ting He; Jiugang Hu; Yuqing Luo; Pengfei Zhu; Shan Cai; Yi Wang; Hongshuai Hou; Guoqiang Zou; Xiaobo Ji (Chemical Engineering Journal, 2023)

Identification of suitable tributaries to compensate fish habitat loss in dammed rivers using environmental DNA metabarcoding - Yuqing Lin; Tao Feng; Lei Tang; Hui Zhang; Jianyun Zhang; Qiuwen Chen; Shufeng He; Ting Li (Hydrobiologia, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

4-hydroxylonchocarpin and corylifol A: The potential hepatotoxic components of Psoralea corylifolia L - Linqi Ouyang; Zhiqiang Fan; Yang He; Long Tan; Guoyan Deng; Qin He; Yiran He; Ting Ouyang; Congjie Li; Qin Zhang; Hongyu Liu; Yajie Zuo (Toxicology Letters, 2023)

Beneficial effects of triadimefon in overcoming drought stress in soybean at fluorescence stage - Bingjie Xu; Chonglan Zheng; Ting Sun; Yue Wu; Mingjie He; Weiping Chen; Pei Zhang; Haidong Jiang (Journal of Plant Physiology, 2023)

Conversion of medical waste into value-added products using a novel integrated system with tail gas treatment: Process design, optimization, and thermodynamic analysis - Yin Ting Chu; Jianzhao Zhou; Jingzheng Ren; Weifeng Shen; Chang He (Journal of Hazardous Materials, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

Electron-donating/withdrawing groups functionalized porphyrin complex as high performance organic lithium batteries - Xiuhui Huang; Yangmei Zhou; Youlian Zeng; Xi Chen; Fangfang He; Ting Wang; Donghui Lan; Wei Liu; Songting Tan; Ping Gao (Chemical Engineering Journal, 2023)

Atomically well-mixed quad-metallic sulfide as multi-functional electrocatalyst for overall water electrolysis and zinc-air battery - Chun-Lung Huang; Zi-Fan He; Jui-Yu Pai; Yu-Hsiang Yang; Wen-Yang Jao; Chi-Yu Lai; Yi-Ting Lu; Hao-Yu Ku; Chi-Chang Hu (Chemical Engineering Journal, 2023)

Biochar enhanced the stability and microbial metabolic activity of aerobic denitrification system under long-term oxytetracycline stress - Qidi Mao; Jianguo Bao; Jiangkun Du; Ting He; Yi Zhang; Benai Cheng (Bioresource Technology, 2023)

Endothelial Cell–Derived Let-7c-Induced TLR7 Activation on Smooth Muscle Cell Mediate Vascular Wall Remodeling in Moyamoya Disease - Xiaopeng Ma; Yimin Huang; Xuejun He; Xincheng Zhang; Yanchao Liu; Yiping Yang; Pengjie Yue; Yuan Liu; Chao Gan; Kai Shu; Ting Lei; Sheng Wang; et al. (Translational Stroke Research, 2023)

Lacticaseibacillus paracasei K56 Attenuates High-Fat Diet-Induced Obesity by Modulating the Gut Microbiota in Mice - Zhonghua Miao; Hanying Zheng; Wei-Hsien Liu; Ruyue Cheng; Hui Lan; Ting Sun; Wen Zhao; Jinxing Li; Xi Shen; Hongwei Li; Haotian Feng; Wei-Lian Hung; et al. (Probiotics and Antimicrobial Proteins, 2023)

Redox states and genesis of Cu- and Au-mineralized granite porphyries in the Jinshajiang Cu–Au metallogenic belt, SW China: studies on the zircon chemistry - Xinshang Bao; Wenyan He; Jingwen Mao; Ting Liang; Hui Wang; Yunman Zhou; Jijiang Wang (Mineralium Deposita, 2023)

Association between air pollution exposure and outpatient visits for dermatomyositis in a humid subtropical region of China: a time-series study - Zheng-Dong Wu; Cong Chen; Yi-Sheng He; Yue Chen; Ya-Ting Feng; Ji-Xiang Huang; Kang-Jia Yin; Jie Wang; Jin-Hui Tao; Hai-Feng Pan (Environmental Geochemistry and Health, 2023)

Blood Selenium and Serum Glutathione Peroxidase Levels Were Associated with Serum β-Amyloid in Older Adults - Jiao Luo; Liqin Su; Xiaohong He; Yegang Du; Ning Xu; Rangpeng Wu; Yunfeng Zhu; Ting Wang; Ranqi Shao; Frederick W. Unverzagt; Ann M. Hake; Yinlong Jin; et al. (Biological Trace Element Research, 2023)

Gross nitrogen transformations and ammonia oxidizers affected by nitrification inhibitors and/or organic amendments in a calcareous soil: A 15N tracing study - Xiaoqian He; Mengxiao Li; Minghua Zhou; Wei Zhou; Guangdeng Chen; Yanyan Zhang; Yang Li; Min Zeng; Xuesong Gao; Ting Lan (Applied Soil Ecology, 2023)

Application of HS-SPME-GC-MS combined with electronic nose technology in the odor recognition of pseudostellariae radix - Tehui Huang; Yan Sun; Yuanyuan Guo; Wei Wang; Ting He; Junling Cao (Natural Product Research, 2023)

Treatment and utilization of swine wastewater – A review on technologies in full-scale application - Liangwei Deng; Dan Zheng; Jingni Zhang; Hongnan Yang; Lan Wang; Wenguo Wang; Ting He; Yunhong Zhang (Science of The Total Environment, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Advanced oxidation-based combined conditioning technologies to improve sludge dewaterability: A mini review - Zhongqi He; Xu Zhou; Xiumin Fan; Wenbiao Jin; Chuan Chen; Bowen Yan; Shiyu Yin; Ting Zhou; Xuan Li; Guangming Jiang (Journal of Water Process Engineering, 2023)

Chickpea protein hydrolysate as a novel plant-based cryoprotectant in frozen surimi: Insights into protein structure integrity and gelling behaviors - Chao Wang; Junhui Rao; Xueyin Li; Diheng He; Ting Zhang; Jianteng Xu; Xi Chen; Lan Wang; Yue Yuan; Xiangwei Zhu (Food Research International, 2023)

Temporal dynamics, driving factor and mutual relationship analysis for the holistic virtual water trade network in China (2002–2017) - Huanzhi Wang; Xue Yang; Huimin Hou; Ting Liu; Yang Zhang; He Xu (Environmental Impact Assessment Review, 2023)

Long-term drying trends since the mid-Holocene in the Qaidam Basin - Ting Zhang; Gen Wang; Yongli Wang; Zhifu Wei; Wei He; Xueyun Ma; He Ma; Xiaoli Yu; Pengyuan Zhang; Shangkun Li; Jingyi Wei; Lun Li (CATENA, 2023)

Peroxymonosulfate and peroxydisulfate activation by fish scales biochar for antibiotics removal: Synergism of N, P-codoped biochar - Qingyun He; Chenhui Zhao; Lin Tang; Zhifeng Liu; Binbin Shao; Qinghua Liang; Ting Wu; Yuan Pan; Jiajia Wang; Yang Liu; Shehua Tong; Tianjue Hu (Chemosphere, 2023)

The catalytic oxidation process of atrazine by ozone microbubbles: Bubble formation, ozone mass transfer and hydroxyl radical generation - Ting Liu; Bin Zhang; Wenqian Li; Boda Li; Ziwen Han; Yanjie Zhang; An Ding; Shutao Wang; Jun Ma; Xu He (Chemosphere, 2023)

Development and application of a rapid screening and quantification method for multi-class herbicide residues in fishery products using UPLC-Q-Tof-MS/MS: Evidence for prometryn residues in shellfish - Jie Peng; Jinhua Gan; Ting Liu; Xiaoqian Ju; Jianwu Chen; Li He (Food Control, 2023)

Impact history and origin of lunar meteorite Northwest Africa 15528 - Runchuan Liu; Huaiyu He; Thomas Smith; Hanqing Ye; Huapei Wang; Xuhang Zhang; Fei Su; Ziheng Liu; Wei Guo; Peng Yang; Chuantong Zhang; Dingshuai Xue; et al. (Science China Earth Sciences, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Watershed urbanization dominated the spatiotemporal pattern of riverine methane emissions: Evidence from montanic streams that drain different landscapes in Southwest China - Xianxiang Li; Yixin He; Xiaofeng Wang; Huai Chen; Tingting Liu; Yizi Que; Xingzhong Yuan; Shengnan Wu; Ting Zhou (Science of The Total Environment, 2023)

Synergistic densification treatment technology of phosphogypsum and aluminum ash - Fenghui Wu; Minjie He; Guangfei Qu; Ting Zhang; Xinxin Liu (Process Safety and Environmental Protection, 2023)

UDP-glucose epimerase 1, moonlighting as a transcriptional activator, is essential for tapetum degradation and male fertility in rice - Nan Wang; Yao Deng; Lisha Zhang; Yingchun Wan; Ting Lei; Yimin Yang; Can Wu; Hai Du; Ping Feng; Wuzhong Yin; Guanghua He (Molecular Plant, 2023)

Phylogenomic analyses of Camellia support reticulate evolution among major clades - Ting Zan; Yi-Tao He; Min Zhang; Takahiro Yonezawa; Hong Ma; Qiang-Min Zhao; Wen-Yu Kuo; Wen-Ju Zhang; Chien-Hsun Huang (Molecular Phylogenetics and Evolution, 2023)

Enhanced photo-electro-Fenton degradation performance using graphene structure-oriented MOFs (2Fe/Co)/CNF cathode membrane - Bingzhang Li; Yao Meng; Xiaoxia Lin; Degui Tu; Shunxi Shen; Ting He; Yuqi Li; Hui Zhang (Journal of Cleaner Production, 2023)

Foliar application of lanthanum promotes growth and phytoremediation potential Solanum nigrum L - Ding He; Ting Guo; Chunqing Peng; Jining Li; Fenghe Wang (Journal of Environmental Management, 2023)

Quantifying the effects of submicroscopic metallic iron on VIS–NIR spectra of lunar soils - Yanhua Peng; Siting Zhang; Hong Tang; Zhuang Guo; Wen Yu; Guozhu Chen; Chen Li; Bingkui Miao; Bing Mo; Encheng He; Ting Zhou; Zhipeng Xia; et al. (Icarus, 2023)

Effect of tea polyphenols on sturgeon myofibrillar protein structure in the in vitro anti-glycation model mediated by low temperature vacuum heating - Dan-li Jin; Jian-ling Wei; Fan-yu He; Ting-ting Chai; Shao-tian Ren; Jing-jing Fu; Yue-wen Chen (Food Chemistry, 2023)

Non-covalent interaction of complex plant protein and betanin: Mechanism of improving thermal stability of betanin - Ting Hu; Taotao Dai; Xuemei He; Lizhen Deng; Ti Li; Jian Sun; Chengmei Liu; Jun Chen (Food Hydrocolloids, 2023)

Post-assessment in policy-based strategic environmental assessment: Taking China's agricultural support and protection subsidy policy as an example - Ting Liu; He Xu (Environmental Impact Assessment Review, 2023)

Quenching-induced surface reconstruction of perovskite oxide for rapid and durable oxygen catalysise - Lingfeng Ke; Shengli Pang; Chao Long; Ting Fang; Gongmei Yang; Yifan Song; Xudong He; Shuai Ma; Yaozheng Qian; Xiangqian Shen; Chonglin Chen (Chemical Engineering Journal, 2023)

Adjacent diatomic Cu1N3/Mo1S2 entities decorated carbon nitride for markedly enhanced photocatalytic hydrogen generation - Zhang Xue; Weiwei Yu; Ting Zhang; Siyuan He; Wantong Zhao; Baojun Wang; Yuefeng Liu; Benxue Zou; Riguang Zhang; Zhongkui Zhao (Chemical Engineering Journal, 2023)

The importance of moisture in regulating soil organic carbon content based on a comparison of “enzymic latch” and “iron gate” in Zoige Plateau peatland - Ruixuan Li; Hanqing Luo; Jianlan Yu; Ling Luo; Yan He; Shihuai Deng; Ouping Deng; Dezhi Shi; Jinsong He; Hong Xiao; Lilin Wang; Ting Lan (CATENA, 2023)

Links between geochemical weathering on the NE Tibetan Plateau and global climate change since the Last Deglacial - Xueyun Ma; Zhifu Wei; Yongli Wang; Gen Wang; Ting Zhang; Wei He; Xiaoli Yu; He Ma; Pengyuan Zhang; Shangkun Li; Qiaohui Fan (CATENA, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Response of Vicia faba to short-term uranium exposure: chelating and antioxidant system changes in roots - Pi-xian Xiao; Xi Chen; Ning-ying Zhong; Ting Zheng; Ying-mei Wang; Guo Wu; Hong Zhang; Bing He (Journal of Plant Research, 2023)

Construction of ZnIn2S4/MOF-525 heterojunction system to enhance photocatalytic degradation of tetracycline - Xiansheng Zhang; Zhifeng Liu; Binbin Shao; Ting Wu; Yuan Pan; Songhao Luo; Miao He; Lin Ge; Jingwen Sun; Chunyun Cheng; Jian Huang (Environmental Science and Pollution Research, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

The palynology of the Permian succession in the CSDP-2 Well, South Yellow Sea, China - Xing-Kai Ji; Xing-Wei Guo; Ning Yang; Jiří Bek; Ting Nie; Hui-Nan Lu; Hong-He Xu (Palynology, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Optimize lettuce washing methods to reduce the risk of microplastics ingestion: The evidence from microplastics residues on the surface of lettuce leaves and in the lettuce washing wastewater - Ding He; Ting Guo; Jining Li; Fenghe Wang (Science of The Total Environment, 2023)

Calcium isotopic geochemistry of geothermal systems in the tectonically active southeastern Tibetan Plateau - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; Jun Zhong; Ting-Ting Ma; Jian Sun; Wen-Yan He; Cong-Qiang Liu (Science of The Total Environment, 2023)

Structural variation (SV)-based pan-genome and GWAS reveal the impacts of SVs on the speciation and diversification of allotetraploid cottons - Shangkun Jin; Zegang Han; Yan Hu; Zhanfeng Si; Fan Dai; Lu He; Yu Cheng; Yiqian Li; Ting Zhao; Lei Fang; Tianzhen Zhang (Molecular Plant, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Depositional processes of the mixed siliciclastic-carbonate system in the Lower Cambrian Xiannüdong Formation in the northern Sichuan Basin, South China - Ting Li; Weiqiang Yang; Chaojin Lu; Pingping Li; Zhehang Xu; Yuan He; Jinbao Duan; Huayao Zou (Marine and Petroleum Geology, 2023)

Watershed land use change indirectly dominated the spatial variations of CH4 and N2O emissions from two small suburban rivers - Ziyi Que; Xiaofeng Wang; Tingting Liu; Shengnan Wu; Yixin He; Ting Zhou; Lele Yu; Zhaoyin Qing; Huai Chen; Xingzhong Yuan (Journal of Hydrology, 2023)

Neutralization of interleukin-11 attenuates silica particles-induced pulmonary inflammation and fibrosis in vivo - Jixuan Ma; Yujia Xie; Yiju Xu; Pei Gu; Yingdie Zhang; Lieyang Fan; Yun Zhou; Haijiao Wang; Ting Zhou; Jintong He; Dongming Wang; Weihong Chen (Journal of Environmental Sciences, 2023)

Sustainable and multifunctional cellulose-lignin films with excellent antibacterial and UV-shielding for active food packaging - Yuan He; Hai-Chuan Ye; Ting-Ting You; Feng Xu (Food Hydrocolloids, 2023)

Silica-nickel catalyst interfaces promote highly efficient CO2 electroreduction to CO with a wide potential range - Yijun Xie; Wei Xia; Shuaiqiang Jia; Shitao Han; Ting Yao; Minghui Fang; Dawei Zhou; Xueqing Xing; Haihong Wu; Mingyuan He; Buxing Han (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

Brittle failure modes of underground powerhouses: an insight based on true triaxial compression tests - Ben-Guo He; Qiang Tong; Xia-Ting Feng; Qiang Jiang; Hui Li; Yonghong Li; Zhiguo Li (Bulletin of Engineering Geology and the Environment, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Identification of a new benzophenanthridine alkaloid from Eomecon chionantha induced necroptosis in breast cancer cells - Peng Yang; Ya-ting Cheng; Xin Huang; Bin Huang; Li Yi; Hai-lang He; Yang Xie (Natural Product Research, 2023)

A novel method of imposing external water pressure to explore the failure behavior of railway tunnel linings - Ben-Guo He; Rui-Hua Xue; Zhi-Qiang Zhang; Xia-Ting Feng; Chuan Wu (Tunnelling and Underground Space Technology, 2023)

Predatory protists play predominant roles in suppressing soil-borne fungal pathogens under organic fertilization regimes - Peixin Ren; Anqi Sun; Xiaoyan Jiao; Ju-Pei Shen; Dan-Ting Yu; Fangfang Li; Bingxue Wu; Ji-Zheng He; Hang-Wei Hu (Science of The Total Environment, 2023)

Applications of convolutional neural networks for intelligent waste identification and recycling: A review - Ting-Wei Wu; Hua Zhang; Wei Peng; Fan Lü; Pin-Jing He (Resources, Conservation and Recycling, 2023)

The association between genital mycoplasma infection and spontaneous abortion: A systematic review and meta-analysis - Wei Chen; Shimin Xiong; Xubo Shen; Ting Qiu; Caidie He; Songlin An; Yuanzhong Zhou (Reproductive Toxicology, 2023)

Preventive effect of Ya'an Tibetan tea on obesity in rats fed with a hypercaloric high-fat diet revealed by gut microbiology and metabolomics studies - Ye Yuan; Jingliu He; Ming Tang; Hong Chen; Ting Wei; Bin Zhang; Dawei Liang; Xuqiang Nie (Food Research International, 2023)

Characterization and shelf stability of sweetened condensed milk formulated with different sucrose substitutes during storage - Ruosi Fang; He Jiang; Chenqi Lin; Ting Xia; Shixuan Xu; Qihe Chen; Gongnian Xiao (Food Chemistry, 2023)

Identification of a key locus, qNL3.1, associated with seed germination under salt stress via a genome-wide association study in rice - Chengfang Zhan; Peiwen Zhu; Yongji Chen; Xinyi Chen; Kexin Liu; Shanshan Chen; Jiaxiao Hu; Ying He; Ting Xie; Shasha Luo; Zeyuan Yang; Sunlu Chen; et al. (Theoretical and Applied Genetics, 2023)
Key message Two causal OsTTL and OsSAPK1 genes of the key locus qNL3.1 significantly associated with seed germination under salt stress were identified via a genome-wide association study, which could improve rice seed germination under salt stress. Abstract Rice is a salt-sensitive crop, and its seed germination determines subsequent seedling establishment and yields. In this study, 168 accessions were investigated for the genetic control of seed germination under salt stress based on the germination rate (GR), germination index (GI), time at which 50% germination was achieved ( T 50 ) and mean level (ML). Extensive natural variation in seed germination was observed among accessions under salt stress. Correlation analysis showed significantly positive correlations among GR, GI and ML and a negative correlation with T 50 during seed germination under salt stress. Forty-nine loci significantly associated with seed germination under salt stress were identified, and seven of these were identified in both years. By comparison, 16 loci were colocated with the previous QTLs, and the remaining 33 loci might be novel. qNL3.1 , colocated with qLTG-3 , was simultaneously identified with the four indices in two years and might be a key locus for seed germination under salt stress. Analysis of candidate genes showed that two genes, the similar to transthyretin-like protein OsTTL and the serine/threonine protein kinase OsSAPK1 , were the causal genes of qNL3.1 . Germination tests indicated that both Osttl and Ossapk1 mutants significantly reduced seed germination under salt stress compared to the wild type. Haplotype analysis showed that Hap.1 of OsTTL and Hap.1 of OsSAPK1 genes were excellent alleles, and their combination resulted in high seed germination under salt stress. Eight accessions with elite performance of seed germination under salt stress were identified, which could improve rice seed germination under salt stress.

Analgesic effect of electroacupuncture on bone cancer pain in rat model: the role of peripheral P2X3 receptor - Shu-xin Tian; Ting Xu; Ren-yi Shi; Yang-qian Cai; Ming-hui Wu; Si-jia Zhen; Wen Wang; You Zhou; Jun-ying Du; Jun-fan Fang; Xiao-mei Shao; Bo-yi Liu; et al. (Purinergic Signalling, 2023)

DEGENERATED LEMMA (DEL) regulates lemma development and affects rice grain yield - You Jing; Chen Wenbo; He Zhifeng; Xiang Yan; Zhang XinFang; Wei Mi; Wu RuHui; Shen Wenqiang; Zhang Jun; Duan QianNan; He Guanghua; Li Yunfeng; et al. (Physiology and Molecular Biology of Plants, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

Neuroplasticity-Related Genes and Dopamine Receptors Associated with Regional Cortical Thickness Increase Following Electroconvulsive Therapy for Major Depressive Disorder - Gong-Jun Ji; Jiao Li; Wei Liao; Yingru Wang; Lei Zhang; Tongjian Bai; Ting Zhang; Wen Xie; Kongliang He; Chuyan Zhu; Juergen Dukart; Chris Baeken; et al. (Molecular Neurobiology, 2023)

Effects of exogenous carbon and nitrification inhibitors on denitrification rate, product stoichiometry and nirS/nirK-type denitrifiers in a calcareous soil: evidence from 15 N anaerobic microcosm assays - Ting Lan; Mengxiao Li; Xiaoqian He; Junji Yuan; Minghua Zhou; Xiaoyan Tang; Yanyan Zhang; Yang Li; Zhaonan Tian; Xuesong Gao (Journal of Soils and Sediments, 2023)

Correlates of Rhizosphere Soil Properties, Fungal Community Composition, and Active Secondary Metabolites in Cornus officinalis in Different Regions of China - Haoqiang Sun; Binkai Han; Xiaolin Yang; Changfen He; Ke Zhao; Ting Wang; Shujing An; Xiaochang Xue; Jiefang Kang (Journal of Soil Science and Plant Nutrition, 2023)

The Nasal Bacteria Microbiome Comparison Among Fungal Ball Sinusitis, Chronic Sinusitis with Polyps - Pengyu Shi; Hongzheng Wei; Xin Liu; Shouxiang Dong; Shuai He; Yun Zeng; Ting Yang; Chengyao Liu; Yunchuan Li (Indian Journal of Microbiology, 2023)

Associations between short-term and long-term exposure to particulate matter and preterm birth - Yun-Fei Su; Cheng Li; Jing-Jing Xu; Fang-Yue Zhou; Tao Li; Cong Liu; Yan-Ting Wu; He-Feng Huang (Chemosphere, 2023)

High-precision early warning system for rice cadmium accumulation risk assessment - Huili Yan; Hanyao Guo; Ting Li; Hezifan Zhang; Wenxiu Xu; Jianyin Xie; Xiaoyang Zhu; Yijun Yu; Jian Chen; Shouqing Zhao; Jun Xu; Minjun Hu; et al. (Science of The Total Environment, 2023)

Triclocarban and triclosan exacerbate high-fat diet-induced hepatic lipid accumulation at environmental related levels: The potential roles of estrogen-related receptors pathways - Xin Li; Jia-Da Zhang; Han Xiao; Sen He; Ting-Ting He; Xiao-Min Ren; Bing-Hua Yan; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2023)

A pore-scale investigation of microplastics migration and deposition during unsaturated flow in porous media - Haiyang He; Ting Wu; Yi-Feng Chen; Zhibing Yang (Science of The Total Environment, 2023)

Overexpression of two CONSTANS-like 2 (MiCOL2) genes from mango delays flowering and enhances tolerance to abiotic stress in transgenic Arabidopsis - Rong-Zhen Liang; Cong Luo; Yuan Liu; Wan-Li Hu; Yi-Hang Guo; Hai-Xia Yu; Ting-Ting Lu; Shu-Quan Chen; Xiu-Juan Zhang; Xin-Hua He (Plant Science, 2023)

Construction of a novel S-scheme heterojunction piezoelectric photocatalyst V-BiOIO3/FTCN and immobilization with floatability for tetracycline degradation - Ting Wu; Qinghua Liang; Lin Tang; Jialin Tang; Jiajia Wang; Binbin Shao; Shanxi Gong; Qingyun He; Yuan Pan; Zhifeng Liu (Journal of Hazardous Materials, 2023)

FSP synthesized core-shell CuOx@SiO2 catalyst with excellent thermal stability for catalytic combustion of ammonia - Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Yu Gui; Xiaochao Wang; Linjia Li; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

A clean and efficient utilization of fly ash with a focus on the strengthening decomposition mechanism of mullite - Jun Hao; Zhi-he Dou; Ting-an Zhang; Kun Wang; Xing-yuan Wan; Song Qi (Fuel, 2023)

Complex plant protein prepared from rice protein and pea protein: Improve the thermal stability of betanin - Ting Hu; Jun Chen; Xuemei He; Yayuan Tang; Jian Sun; Chengmei Liu; Taotao Dai (Food Research International, 2023)

Acute exposure to microcystins affects hypothalamic-pituitary axes of male rats - Ting Shi; Lin-Lin Xu; Liang Chen; Jun He; Ye-Ke Wang; Feng Chen; Yang Chen; John P. Giesy; Yu-Ting Wang; Qian-Hui Wu; Wen-Li Xu; Jun Chen; et al. (Environmental Pollution, 2023)

Template-assisted synthesis of ultrathin graphene aerogels as bifunctional oxygen electrocatalysts for water splitting and alkaline/neutral zinc-air batteries - Qiang Li; Zhifang Sun; Chunyang Yin; Yang Chen; Dingjie Pan; Bingzhe Yu; Yi Zhang; Ting He; Shaowei Chen (Chemical Engineering Journal, 2023)

Artificial skin with fast and robust self-healing ability for durable intelligent protection of magnesium alloys - Lei Liu; Jinglei Lei; Ting Liu; Bo Shang; Xingwang Zhao; Jianxin He; Fusheng Pan; Lingjie Li (Chemical Engineering Journal, 2023)

Effect of electric field and water on Pd-based catalyst for complete oxidation of methane: Study on promotion and deactivation - Xuteng Zhao; Ting Chen; Yinan Wang; Ke Li; Reggie Zhan; He Lin (Chemical Engineering Journal, 2023)

Dithio-bridged chelate network for stabilizing thermo-kinetics of dendrite-free zinc anode - Shan Cai; Jiugang Hu; Yuqing Luo; Pengfei Zhu; Ting He; Hongshuai Hou; Guoqiang Zou; Xiaobo Ji (Chemical Engineering Journal, 2023)

Injectable Host-Guest supramolecular hydrogel Co-Delivers hydrophobic and hydrophilic agents for enhanced wound healing - Jie Xu; Kangning Wang; Yanyan Li; Yue Li; Bingxin Li; Hangqi Luo; Huiling Shi; Xueran Guan; Ting Zhang; Yixiao Sun; Feng Chen; Huacheng He; et al. (Chemical Engineering Journal, 2023)

Maltol ameliorates intervertebral disc degeneration through inhibiting PI3K/AKT/NF-κB pathway and regulating NLRP3 inflammasome-mediated pyroptosis - Yuhang Gong; Jianxing Qiu; Ting Jiang; Ze Li; Weikang Zhang; Xiaohang Zheng; Zixuan He; Weifu Chen; Zhangfu Wang; Xingbing Feng; Meizhen Wang; Zhenghua Hong (Inflammopharmacology, 2023)
Objectives As one of the major causes of low back pain, intervertebral disc degeneration (IDD) has caused a huge problem for humans. Increasing evidence indicates that NLRP3 inflammasome-mediated pyroptosis of NP cells displays an important role in the progression of IDD. Maltol (MA) is a flavoring agent extracted from red ginseng. Due to its anti-inflammatory and antioxidant effects, MA has been widely considered by researchers. Therefore, we hypothesized that MA may be a potential IVD protective agent by regulating NP cells and their surrounding microenvironment. Methods In vitro, qRT-PCR, and Western blot were used to explore the effect of MA on the transcription and protein expression of the anabolic protein (ADAMTS5, MMP3, MMP9) catabolic protein (Aggrecan), and pro-inflammatory factor (iNOS COX-2). Next, the effects of MA on PI3K/AKT/NF-κB pathway and pyroptosis pathway were analyzed by Western blot and immunofluorescence. Molecular docking was used to investigate the relationship between PI3K and MA. Moreover, ELISA was also used to detect the effects of MA on inflammatory factors (TNF-α, PGE2, IL-1β, and IL-18). In vivo, the effects of MA on the vertebral structure of IDD mice were studied by HE and SO staining and the effects of MA on ECM and PI3K/AKT/NF-κB and pyroptosis pathway of IDD mice were studied by immunohistochemical staining. Results MA can ameliorate intervertebral disc degeneration in vivo and in vitro. Specifically, the molecular docking results showed that the binding degree of MA and PI3K was significant. Second, in vitro studies showed that MA inhibited the degradation of ECM and inflammatory response by inhibiting the PI3K/AKT/NF-κB pathway and the pyroptosis mediated by NLRP3 inflammasome, which increased the expression of anabolic proteins, decreased the expression of catabolic proteins, and decreased the secretion of inflammatory mediators such as IL-18 and IL-1β. In addition, according to the study results of the mouse lumbar instability model, MA also improved the tissue disorder and degradation of the intervertebral disc, reduced the loss of proteoglycan and glycosaminoglycan, and inhibited intervertebral disc inflammation, indicating that MA has a protective effect on the intervertebral disc to intervertebral disc in mice. Conclusions Our results suggest that MA slowed IDD development through the PI3K/AKT/NF-κB signaling pathway and NLRP3 inflammasome-mediated pyroptosis, indicating that MA appeared to be a viable medication for IDD treatment.

Coupled folding-upon-binding of human tumor suppressor MIG6 to lung cancer EGFR kinase domain and molecular trimming/stapling of MIG6-derived β-hairpins to target the coupling event - Quan He; Shuanglan Xu; Xiaomei Ma; Ting Ling; Weiqi Feng; Xuzhi Lu; Weihua Liu; Zi Chen (European Biophysics Journal, 2023)

Experimental study on the distribution law of the blade foot resistance of a large deep-water open caisson in sand - Bing-nan Jiang; Ting Yu; Wen-ming Peng; Ying-bin Zhang; Shun-bin He; Jian-lin Ma (Ocean Engineering, 2023)

Activated abscisic acid pathway and C4 pathway, inhibited cell cycle progression, responses of Ulva prolifera to short term high temperature elucidated by multi-omics - Hui Zhao; Xuanhong Liu; Ting Jiang; Chuner Cai; Kai Gu; Yuling Liu; Peimin He (Marine Environmental Research, 2023)

Cross-biome soil viruses as an important reservoir of virulence genes - Li Bi; Li-Li Han; Shuai Du; Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Hang-Wei Hu (Journal of Hazardous Materials, 2023)

GWAS-assisted genomic prediction of cadmium accumulation in maize kernel with machine learning and linear statistical methods - Huili Yan; Hanyao Guo; Wenxiu Xu; Changhua Dai; Wilson Kimani; Jianyin Xie; Hezifan Zhang; Ting Li; Feng Wang; Yijun Yu; Mi Ma; Zhuanfang Hao; et al. (Journal of Hazardous Materials, 2023)

Clean hydrometallurgical route for highly efficient decontamination and recycling of multiple heavy metals from hazardous Pb smelting residues: Multi-objective leaching optimization, adsorption, and risk assessment - Yu Zhang; Ting Li; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Yulin Pu; Lulu Long; Jinsong He; Wei Zhou; Guoshu Gong; Ling Luo (Journal of Cleaner Production, 2023)

Application of carbon aerogel-based materials in persulfate activation for water treatment: A review - Binbin Shao; Yuantao Xu; Zhifeng Liu; Ting Wu; Yuan Pan; Xiansheng Zhang; Miao He; Lin Ge; Yue Lu; Yang Liu; Weimin Zeng; Lin Tang (Journal of Cleaner Production, 2023)

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

Comparative analysis of cryogenic distillation and chemical absorption for carbon capture in integrated natural gas liquefaction processes - Ting He; Zhongxuan Liu; Heechang Son; Truls Gundersen; Wensheng Lin (Journal of Cleaner Production, 2023)

Study on the dynamics mechanism of methane diffusion in coal under microwave heating - He Li; Xiaolong Wang; Jiexin Lu; Yi Lu; Shiliang Shi; Zheng Wang; Ting Liu; Qing Ye; Zhenzhen Jia (Fuel, 2023)

Insight into interfacial adsorption behavior of high-density lipoprotein hydrolysates regulated by carboxymethyl dextrin and in vitro digestibility of curcumin loaded high internal phase emulsions - Bao Zhang; Wen-Jie Liu; Ting-Shi He; Bao-Cai Xu; Qiu-Tao Xie (Food Chemistry, 2023)

Residential greenness and risk of incident dementia: A prospective study of 375,342 participants - He-Ying Hu; Ya-Hui Ma; Yue-Ting Deng; Ya-Nan Ou; Wei Cheng; Jian-Feng Feng; Lan Tan; Jin-Tai Yu (Environmental Research, 2023)

Understanding the effect of environment on macrobenthic invertebrate in naturally occurring repeated mesohabitats from the warm-temperate zone river - Amit Jagannath Patil; Zhenhong Wang; Xiaole He; Pangen Li; Ting Yan; He Li (Ecohydrology & Hydrobiology, 2023)

Disinfection byproducts formation from emerging organic micropollutants during chlorine-based disinfection processes - Binbin Shao; Leyuan Shen; Zhifeng Liu; Lin Tang; Xiaofei Tan; Dongbo Wang; Weimin Zeng; Ting Wu; Yuan Pan; Xiansheng Zhang; Lin Ge; Miao He (Chemical Engineering Journal, 2023)

Single-Atom-Catalyzed MXene-Based nanoplatform with Photo-Enhanced Peroxidase-Like activity nanotherapeutics for Staphylococcus aureus infection - ZhangPing Li; Dongqian Xu; Zaian Deng; Jiana Yin; Yuna Qian; Ji-Ting Hou; Xi Ding; Jianliang Shen; Xiaojun He (Chemical Engineering Journal, 2023)

Synergistic effect of F doping and WO3 loading on electrocatalytic oxygen evolution - Ke Lu; Zongyuan Wang; Yaoxin Wu; Xingwu Zhai; Chenxu Wang; Ju Li; Zhimou Wang; Xinyi Li; Yuxuan He; Ting An; Kun Yang; Dezheng Yang; et al. (Chemical Engineering Journal, 2023)

An improved model assessing variation characteristics of pore structure of sandy soil thawing from extremely low temperature using NMR technique - Bo Liu; Yanqing He; Yanhui Han; Ting Li; Dongyang Li; Rong Gao (Cold Regions Science and Technology, 2023)

Identification of major quantitative trait loci and candidate genes for seed weight in soybean - Mengge Xu; Keke Kong; Long Miao; Jianbo He; Tengfei Liu; Kai Zhang; Xiuli Yue; Ting Jin; Junyi Gai; Yan Li (Theoretical and Applied Genetics, 2023)
Key message Four major quantitative trait loci for 100-seed weight were identified in a soybean RIL population under five environments, and the most likely candidate genes underlying these loci were identified. Abstract Seed weight is an important target of soybean breeding. However, the genes underlying the major quantitative trait loci (QTL) controlling seed weight remain largely unknown. In this study, a soybean population of 300 recombinant inbred lines (RILs) derived from a cross between PI595843 (PI) and WH was used to map the QTL and identify candidate genes for seed weight. The RIL population was genotyped through whole genome resequencing, and phenotyped for 100-seed weight under five environments. A total of 38 QTL were detected, and four major QTL, each explained at least 10% of the variation in 100-seed weight, were identified. Six candidate genes within these four major QTL regions were identified by analyses of their tissue expression patterns, gene annotations, and differential gene expression levels in soybean seeds during four developmental stages between two parental lines. Further sequence variation analyses revealed a C to T substitution in the first exon of the Glyma.19G143300 , resulting in an amino acid change between PI and WH, and thus leading to a different predicted kinase domain, which might affect its protein function. Glyma.19G143300 is highly expressed in soybean seeds and encodes a leucine-rich repeat receptor-like protein kinase (LRR-RLK). Its predicted protein has typical domains of LRR-RLK family, and phylogenetic analyses reveled its similarity with the known LRR-RLK protein XIAO ( LOC_Os04g48760 ), which is involved in controlling seed size. The major QTL and candidate genes identified in this study provide useful information for molecular breeding of new soybean cultivars with desirable seed weight.

Differences in methane and nitrous oxide emissions and soil bacteria communities between straw return methods in central China - Jing Zhang; Shuaibing Zhao; Ye Liu; He Liang; Tongtong Wang; Yafan Zhao; Quanzhi Zhao; Ting Peng (Environmental Science and Pollution Research, 2023)

High Fe and Mn groundwater in the Nanchang, Poyang Lake Basin of China: hydrochemical characteristics and genesis mechanisms - Xiaodong Chu; Zhifei Ma; Daishe Wu; Hao Wang; Jingyuan He; Ting Chen; Ziyin Zheng; Hugang Li; Peng Wei (Environmental Monitoring and Assessment, 2023)

Evaluation and subgroup analysis of the efficacy and safety of intensive rosuvastatin therapy combined with dual antiplatelet therapy in patients with acute ischemic stroke - Ting Deng; Tong Zhang; Haitao Lu; Jingmian Chen; Xiaomeng Liu; Wei He; Xiaohua Yao (European Journal of Clinical Pharmacology, 2022)
Objectives We investigated the efficacy of intensive rosuvastatin therapy plus 7-day dual antiplatelet therapy (DAPT) in reducing stroke recurrence for patients with acute ischemic stroke (AIS) and compared subgroups of patients. Methods We enrolled patients with AIS whose time of onset to medication was ≤ 72 h, and the baseline scores of NIHSS (bNIHSS) were 0–10. The patients received intensive rosuvastatin therapy plus 7-day DAPT with aspirin and clopidogrel (study group) or rosuvastatin plus single antiplatelet therapy (SAPT, control group). The primary outcomes were recurrence of ischemic stroke, bleeding, statin-induced liver injury, and statin-associated myopathy (SAM) within 90 days. We also performed a subgroup analysis to assess the heterogeneity of the two therapy regimens in reducing recurrent stroke. Results Recurrent stroke occurred in 10 patients in the study group and 42 patients in the control group (hazard ratio [HR], 0.373, 95% confidence interval [CI], 0.178–0.780; P = 0.009). Bleeding events occurred in 9 patients in the study group and 14 patients in the control group (HR, 1.019; 95%CI, 0.441–2.353; P = 0.966). Statin-induced liver injury and SAM were not recorded. Intensive rosuvastatin plus 7-day DAPT was generally effective in reducing the risk of recurrent stroke, except in the subgroup with bNIHSS ≤ 2. The therapy was particularly efficient in the elderly, male, high-bNIHSS, and hypertension, diabetes, and hyperlipidemia subgroups, with P < 0.02. Conclusions Without increasing bleeding and statin-associated adverse events, intensive rosuvastatin therapy plus 7-day DAPT significantly reduced the risk of recurrent stroke, especially for subgroups with high-risk factors. Clinical trial registration . China Clinical Trial Registration Center (ChiCTR1800017809).

Plastid phylogenomic insights into relationships, divergence, and evolution of Apiales - Deng-Feng Xie; Chuan Xie; Ting Ren; Bo-Ni Song; Song-Dong Zhou; Xing-Jin He (Planta, 2022)

ZmSPO11-2 is critical for meiotic recombination in maize - Menghan Li; Shuyue Li; Yan He; Yan Wang; Ting Zhang; Ping Li; Yan He (Chromosome Research, 2022)

Correction to: Source apportionment and health risk assessment of air pollution particles in eastern district of Chengdu - Yi Huang; Li Wang; Shipeng Zhang; Meng Zhang; Jinjin Wang; Xin Cheng; Ting Li; Min He; Shijun Ni (Environmental Geochemistry and Health, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

A novel bio-washing eluent obtained from fermentation of fruit wastes for removal of soil Pb: efficiency, mechanism, and risk assessment - Xiaomei Pan; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Yun Li; Wei Zhou; Jinsong He; Lulu Long; Ouping Deng; Ling Luo; Guoshu Gong (Environmental Science and Pollution Research, 2022)

First report of Bacillus velezensis JK-F2 for the biological control of crown gall in kiwifruit - Ting Ting Chen; Fei Ran; Jin Qiao Shi; Fei Xu Mo; Xian Hui Yin; Zhi Bo Zhao; Zhu Zhu Zhang; Wen Zhi Li; Li Nan He; You Hua Long (Journal of Plant Diseases and Protection, 2022)

Marked changes in biochar’s ability to directly immobilize Cd in soil with aging: implication for biochar remediation of Cd-contaminated soil - Xinhao Ren; Jiayi He; Qiao Chen; Fei He; Ting Wei; Honglei Jia; Junkang Guo (Environmental Science and Pollution Research, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Mathematical modeling for mutator phenotype and clonal selection advantage in the risk analysis of lung cancer - Lingling Li; Ting Zhao; Xingshi He; Xinshe Yang; Tianhai Tian; Xinan Zhang (Theory in Biosciences, 2022)

Effects of Cerebellar Transcranial Direct Current Stimulation in Patients with Stroke: a Systematic Review - Li Hong-yu; Zhang Zhi-jie; Li Juan; Xiong Ting; He Wei-chun; Zhu Ning (The Cerebellum, 2022)

Study on Water Quality Prediction of Urban Reservoir by Coupled CEEMDAN Decomposition and LSTM Neural Network Model - Lei Zhang; Zhiqiang Jiang; Shanshan He; Jiefeng Duan; Pengfei Wang; Ting Zhou (Water Resources Management, 2022)

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

Particle Design and Inhalation Delivery of Iodine for Upper Respiratory Tract Infection Therapy - Kaikai Zhang; Xiaohong Ren; Jiacai Chen; Caifen Wang; Siyu He; Xiaojin Chen; Ting Xiong; Jiawen Su; Shujun Wang; Weifeng Zhu; Jiwen Zhang; Li Wu (AAPS PharmSciTech, 2022)

Prediction of drought/flood intensities based on a 500-year time series in three different climate provinces of China - Yu Peng; Zhaohua Wang; Yixin Cui; Yali Su; Yiyun Tang; Shiqian Luo; Lianlin Liu; Yanqiu Zhou; Jihui Dong; Wentao Wang; Xiang Li; Jiaxin Shang; et al. (Regional Environmental Change, 2022)

Potential vorticity perspective of the genesis of a Tibetan Plateau vortex in June 2016 - Guoxiong Wu; Yiqiong Tang; Bian He; Yimin Liu; Jiangyu Mao; Tingting Ma; Ting Ma (Climate Dynamics, 2022)
At midnight on 27–28 June 2016, a Tibetan Plateau (TP) Vortex (TPV) generated over the western TP that subsequently caused a downstream record-breaking rainstorm and extremely severe natural disaster. Based on reanalysis data and satellite imagery, this study investigates the formation of this TPV from a potential vorticity (PV) perspective. Results show that, in late June 2016, a remarkable circulation anomaly occurred over the TP and its peripheral area, with easterly flow in the middle and lower troposphere developing in the subtropical zone, replacing the normal westerly flow there. Its forefront merged with the southwesterly flow from the west and penetrated and converged over the western TP where the surface was warmer than normal, forming a low-level jet and downward slantwise isentropic surfaces in-situ. When the air parcel slid down the slantwise isentropic surface, its vertical relative vorticity developed owing to slantwise vorticity development associated with PV restructuring. At the same time, the penetrating southwesterly flow brought abundant water vapor to the western TP and induced increasing sub-cloud entropy and air ascent there. Low-layer cloud formed and the cloud liquid water content increased. The strong latent heat that was released in association with the formation of cloud produced strong diabatic heating near 400 hPa at night and strong PV generation below. The normal diurnal variation was interrupted and the vortex was generated near the surface. These results demonstrate that, against a favorable circulation background, both adiabatic and diabatic PV processes are crucial for TPV genesis.

Study on the seepage control of ultra-deep in situ test wells in deep overburden of riverbeds - Ting Yu; Bing-nan Jiang; Shun-bin He; Wen-ming Peng; Cong-yong Ran (Arabian Journal of Geosciences, 2022)

Effects of synthetic nitrification inhibitor (3,4-dimethylpyrazole phosphate; DMPP) and biological nitrification inhibitor (methyl 3-(4-hydroxyphenyl) propionate; MHPP) on the gross N nitrification rate and ammonia oxidizers in two contrasting soils - Ting Lan; Mengxiao Li; Xiaoqian He; Ouping Deng; Wei Zhou; Ling Luo; Guangdeng Chen; Shu Yuan; Jing Ling; Min Zeng; Xuesong Gao (Biology and Fertility of Soils, 2022)

A study of health management of LWD tool based on data-driven and model-driven - Hui Li; Zi-Hua He; Yu-ting Zhang; Jin Feng; Zun-Yi Jian; Yi-Bo Jiang (Acta Geophysica, 2022)

OsMYB103 is essential for tapetum degradation in rice - Ting Lei; Lisha Zhang; Ping Feng; Yang Liu; Wuzhong Yin; Lina Shang; Guanghua He; Nan Wang (Theoretical and Applied Genetics, 2022)

Exogenous IAA Alleviates Arsenic Toxicity to Rice and Reduces Arsenic Accumulation in Rice Grains - Yue He; Ting Zhang; Yu Sun; Xuejing Wang; Qingqing Cao; Zhigang Fang; Ming Chang; Qingsheng Cai; Laiqing Lou (Journal of Plant Growth Regulation, 2022)

Prediction and validation of cross-protective candidate antigen of Hyalomma asiaticum cathepsin L between H. asiaticum and H. anatolicum - Ruiqi Song; Xuejie Zhai; Xinli Fan; Yongchang Li; Huercha; Ting Ge; Caishan Li; Min Li; Wenwen He; Huizhen Zheng; Lu Gan; Yang Zhang; et al. (Experimental and Applied Acarology, 2022)

Identifying the priority areas for enhancing the ecosystem services in hilly and mountainous areas of southern China - Jia-ling Tian; Yu Peng; Yi-hang Huang; Ting Bai; Lian-lin Liu; Xiao-ao He; Shi-qian Luo (Journal of Mountain Science, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Transcriptome analysis reveals MYB and WRKY transcription factors involved in banana (Musa paradisiaca AA) magnesium deficiency - Yong Yang; Xinping Li; Baolin Kan; Hongsu He; Ting Li; Yuanhao Ding; Pengmeng Du; Wenjie Lai; Haiyan Hu; Jiaquan Huang (Planta, 2021)

Monochloropropanediol in edible vegetable oils from Hangzhou market in China: occurrence and exposure risk assessment - Ji-Cai Fan; Hua-li He; Ren Ren; Shu-ting Wang (Food Additives & Contaminants: Part A, 2021)

Recent advances in lentiviral vectors for gene therapy - Xiaoyu Wang; Cuicui Ma; Roberto Rodríguez Labrada; Zhou Qin; Ting Xu; Zhiyao He; Yuquan Wei (Science China Life Sciences, 2021)

Enhanced SA and Ca2+ signaling results in PCD-mediated spontaneous leaf necrosis in wheat mutant wsl - Huijuan Li; Zhixin Jiao; Peipei Zhang; Yongjing Ni; Ting Wang; Jing Zhang; Junchang Li; Yumei Jiang; Xiwen Yang; Lei Li; Ziping Yao; Jishan Niu; et al. (Molecular Genetics and Genomics, 2021)

Efficiency and comprehensive risk assessment of soil Pb and Cd by washing technique with three biodegradable eluents - Qinmei Zhong; Shirong Zhang; Xiaomei Pan; Guiyin Wang; Xiaoxun Xu; Ting Li; Wei Zhou; Yan He; Ling Luo; Yan Liu; Lulu Long (Environmental Science and Pollution Research, 2021)

Analysis of the Spatial and Temporal Variation of Sea Ice and Connectivity in the NEP of the Arctic in Summer in Hot Years - Guochong Liu; Min Ji; Fengxiang Jin; Ying Li; Yawen He; Ting Li (Journal of Marine Science and Engineering, 2021)
Climate warming has enabled the Arctic region to achieve seasonal navigation, and sea ice concentration is an important factor affecting the navigation of the Arctic waterways. This article uses the Arctic sea ice concentration data of the three highest temperatures in 2016, 2019, and 2020, combined with the Arctic summer sea level pressure, wind field, temperature, temperature anomaly, ice age, and sea ice movement data to analyze the spatial and temporal variation of sea ice and connectivity in the Northeast Passage (NEP) of the Arctic in Summer in three hot years, and summarizes the causes of sea ice anomalies. The results show that: (1) the summer Arctic sea ice extent in 2016, 2019 and 2020 were all lower than the multi-year average sea ice extent, and the summer sea ice extent in 2020 had the largest change trend; (2) in October of these three years, the sea ice was all negative anomalies, extending the opening time of the NEP; (3) when the sea ice concentration was 30% as the threshold, the navigation period of the NEP in 2016 was from mid-August to late October, 2019 was from the beginning of August to mid-October, 2020 was from the end of July to the end of October, and 2020 was the longest year since the opening of the NEP; (4) when the sea ice concentration was 10% as the threshold, the navigation period of the NEP in 2016 was from the end of August to the end of October, 2019 was from early August to mid-October, and 2020 was from the beginning of August to the end of October; (5) the key navigable areas of the NEP in the past three years were the central waters of the East Siberian Sea, the New Siberian Islands and the Vilkitsky Strait; (6) the navigation period of the NEP in 2016, 2019 and 2020 was longer. The main reasons were that the temperature of the NEP in the past 3 years was relatively high, the wind was weak, the sea ice movement had little effect, and the sea ice age in the key navigable areas was first year ice, which was easy to melt, which greatly promoted the opening of the NEP.

Activation of the Hippocampal LXRβ Improves Sleep-Deprived Cognitive Impairment by Inhibiting Neuroinflammation - Chen Qiu; Min Wang; Wen Yu; Zheng Rong; He-Sheng Zheng; Ting Sun; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2021)

Weakened growth, cell division, and energy metabolism, but enhanced resistance, signaling, and anabolism: responses of Ulva prolifera to copper elucidated by omics - Chuner Cai; Xuanhong Liu; Hui Zhao; Ting Jiang; Rui Jia; Peimin He (Journal of Applied Phycology, 2021)

Prenatal phthalate exposure reduction through an integrated intervention strategy - Wei Wu; Liu Cao; Ting-Ting Zheng; Shu-Yu Feng; Guan-Wei Ma; Ying-Ying He; Ping Wu (Environmental Science and Pollution Research, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Structure–activity relationship studies on Pd176252 derivatives leading to discovery of novel GRP receptor antagonist with potent anticancer activity - Ming-jun Yu; Chao Li; Meng He; Yu-ting Zhu; Rui Yang; Sheng-song Deng; Xiao-ming Meng; Ri-sheng Yao (Medicinal Chemistry Research, 2021)

Experimental study on the pressure of impulse waves generated by landslides on a bank slope - Ting Cao; Pingyi Wang; Jielong Hu; Zhenfeng Qiu; Pengchao He (Marine Georesources & Geotechnology, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

Effects of climate change on ecosystem services and their components in southern hills and northern grasslands in China - Lan Bai; Jialing Tian; Yu Peng; Yihang Huang; Xiaoao He; Xueying Bai; Ting Bai (Environmental Science and Pollution Research, 2021)

DJ-1 activates the noncanonical NF-κB pathway via interaction with Cezanne to inhibit the apoptosis and promote the proliferation of Ishikawa cells - Qi-Zhou Zhu; Hao-Yue Liu; Xiao-Yan Zhao; Le-Jia Qiu; Ting-Ting Zhou; Xue-Ying Wang; He-Ping Chen; Zhong-Qing Xiao (Molecular Biology Reports, 2021)

Microwave-assisted high-efficiency degradation of methyl orange by using CuFe2O4/CNT catalysts and insight into degradation mechanism - Zhifeng Liu; Wei Zhang; Qinghua Liang; Jinhui Huang; Binbin Shao; Yang Liu; Yujie Liu; Qingyun He; Ting Wu; Jilai Gong; Ming Yan; Wangwang Tang (Environmental Science and Pollution Research, 2021)

Analysis of Sea Ice Timing and Navigability along the Arctic Northeast Passage from 2000 to 2019 - Min Ji; Guochong Liu; Yawen He; Ying Li; Ting Li (Journal of Marine Science and Engineering, 2021)
The ablation of Arctic sea ice makes seasonal navigation possible in the Arctic region, which accounted for the apparent influence of sea ice concentration in the navigation of the Arctic route. This paper uses Arctic sea ice concentration daily data from January 1, 2000, to December 31, 2019. We used a sea ice concentration threshold value of 40% to define the time window for navigating through the Arctic Northeast Passage (NEP). In addition, for the year when the navigation time of the NEP is relatively abnormal, we combined with wind field, temperature, temperature anomaly, sea ice age and sea ice movement data to analyze the sea ice conditions of the NEP and obtain the main factors affecting the navigation of the NEP. The results reveal the following: (1) The sea ice concentration of the NEP varies greatly seasonally. The best month for navigation is September. The opening time of the NEP varies from late July to early September, the end of navigation is concentrated in mid-October, and the navigation time is basically maintained at more than 30 days. (2) The NEP was not navigable in 2000, 2001, 2003 and 2004. The main factors are the high amount of multi-year ice, low temperature and the wind field blowing towards the Vilkitsky Strait and sea ice movement. The navigation time in 2012, 2015 and 2019 was longer, and the driving factors were the high temperature, weak wind and low amount of one-year ice. The navigation time in 2003, 2007 and 2013 was shorter, and the influencing factors were the strong wind field blowing towards the Vilkitsky Strait. (3) The key navigable areas of the NEP are the central part of the East Siberian Sea and the Vilkitsky Strait, and the Vilkitsky Strait has a greater impact on the NEP than the central part of the East Siberian Sea. The main reason for the high concentration of sea ice in the central part of the East Siberian Sea (2000 and 2001) was the large amount of multi-year ice. The main reason for the high concentration of sea ice in the Vilkitsky Strait (2000 to 2004 and 2007, 2013) was the strong offshore wind in summer, all of which were above 4 m s−1, pushing the sea ice near the Vilkitsky Strait to accumulate in the strait, thus affecting the opening of the NEP.

Difference in the binding mechanism of distinct antimony forms in bovine serum albumin - Jiali Gu; Gang Yang; Xiang Li; Qian He; Xiyao Huang; Ting Sun (BioMetals, 2021)

A calculation model of the normal coefficient of restitution based on multi-factor interaction experiments - Zhong-Min Ji; Zhi-Jian Chen; Qing-He Niu; Ting-Hui Wang; Tian-Jun Wang; Tian-Li Chen (Landslides, 2021)

Protein expression pattern of calcium-responsive transactivator in early postnatal and adult testes - Ana Du; Li Li; Zhaoshuang Jiao; Gaochun Zhu; Ting Peng; He Li (Histochemistry and Cell Biology, 2021)
Calcium-responsive transactivator (CREST), a nuclear protein highly expressed in postmitotic neurons, is involved in the regulation of cell cycle, differentiation and dendritic development of neuronal cells. Its mRNA has been detected in the testis of adult rat, whilst its protein expression and distribution pattern in the testis remain to be elucidated. In this study, we examined the distribution of CREST in the adult testes of both rats and human as well as the expression pattern of CREST in the testes of postnatal developing rats. In the adult testes of both human and rats, immunohistochemical analysis revealed that CREST was selectively distributed in the mature Sertoli cells but not in the spermatogenic cells. In the testes of postnatal developmental rats, CREST was expressed not only in Sertoli cells but also in the gonocytes and spermatogenic cells at the initial stage of spermatogenic cell differentiation. CREST immunoreactivity continued to increase in Sertoli cells during differentiation, reaching its peak in adulthood. However, CREST immunostaining intensity dramatically decreased as the spermatogenic cells differentiate, disappearing in the post-differentiation stage. Furthermore, Brg1 and p300, two CREST-interacting proteins ubiquitously expressed in the body, are found to be colocalized with CREST in the spermatogenic epithelial cells including Sertoli cells. The unique expression pattern of CREST in developing testis suggests that CREST might play regulatory roles in the differentiation of spermatogenic epithelial cells. The Sertoli cell-specific expression of CREST in the adulthood hints that CREST might be a novel biomarker for the mature Sertoli cells.

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

Diurnal expression of circadian clock genes period 1 and period 3 in Pelteobagrus vachellii - Chuanjie Qin; Ting Shao; Xufeng Liao; Yang He; Jun Wang; Peng Hu (Journal of Oceanology and Limnology, 2021)

Methane and nitrous oxide emission characteristics of high-yielding rice field - Zi-Hao Wang; Liu-Hang Wang; He Liang; Ting Peng; Gui-Ping Xia; Jing Zhang; Quan-Zhi Zhao (Environmental Science and Pollution Research, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Spatial-temporal pattern evolution and driving force analysis of ecological environment vulnerability in Panzhihua City - Xiaoai Dai; Yu Gao; Xuwei He; Ting Liu; Bohan Jiang; Huaiyong Shao; Yuanzhi Yao (Environmental Science and Pollution Research, 2021)

Distribution of n ‐alkan‐2‐ones in Qionghai Lake sediments, southwest China, and its potential for late Quaternary paleoclimate reconstruction - Gen Wang; Yongli Wang; Zhifu Wei; Wei He; Ting Zhang; Xueyun Ma; Xiaoli Yu (Journal of Quaternary Science, 2021)
Studies on long‐chain n ‐alkan‐2‐ones from lake sediments remain sparse. In this study, we present an n ‐alkan‐2‐one record from Qionghai Lake, southwest China, to assess the paleoclimate significance of variations in their compositions. A homologous series of n ‐alkan‐2‐ones ranging from C 21 to C 35 were identified, with maximum concentrations of the C 29 or C 31 chain lengths and a strong odd‐over‐even predominance. This type of n ‐alkan‐2‐one is considered to derive mainly from microbial oxidation of the corresponding n ‐alkanes, and partial inputs from plants. The n ‐alkan‐2‐one‐derived average chain length (ACL) and carbon preference index (CPI) values changed significantly over the past 28k cal a bp , consistent with the sediment grain size and n ‐alkane proxies from the same core. Generally, the high CPI 27‐33 ‐ket and low ACL 27‐33 ‐ket values indicated cold and dry climates such as for the Last Glacial Maximum (23.2–19.7k cal a bp ), Heinrich 1 event (17.6–15.6k cal a bp ) and Younger Dryas (12.8–11.6k cal a bp ), but low CPI 27‐33 ‐ket and high ACL 27‐33 ‐ket values denoted a warm and humid Holocene Climatic Optimum (7.0–4.3k cal a bp ). Therefore, n ‐alkan‐2‐ones have great paleoclimatic potential and can be applied together with other biomarkers to reconstruct a reliable paleoclimate record in lake sediments.

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

Effect of pyrolysis temperature on the bioavailability of heavy metals in rice straw-derived biochar - Tiexin Yang; Jun Meng; Paramsothy Jeyakumar; Ting Cao; Zunqi Liu; Tianyi He; Xuena Cao; Wenfu Chen; Hailong Wang (Environmental Science and Pollution Research, 2021)

Characteristics of the potential vorticity and its budget in the surface layer over the Tibetan plateau - Chen Sheng; Guoxiong Wu; Yiqiong Tang; Bian He; Yongkun Xie; Tingting Ma; Ting Ma; Jinxiao Li; Qing Bao; Yimin Liu (International Journal of Climatology, 2021)
The variability of interior atmospheric potential vorticity (PV) is linked with PV generation at the Earth's surface. The present paper reveals the features of the surface PV and provides a stepping stone to investigate the surface PV budget. In this study, the formats of the PV and PV budget adopting a generalized vertical coordinate were theoretically examined to facilitate the calculation of the surface PV and its budget. Results show that the formats of the PV and PV budget equations are independent of the vertical coordinate. While the vertical component of the surface PV dominates over the platform of the Tibetan Plateau, the horizontal component plays an important role over the slopes of the Tibetan Plateau, especially the southern slope owing to the strong in‐situ meridional gradient of the potential temperature. These results indicate that the employment of complete surface PV not only provides a finer PV structure but also more appropriately reveals its effect on atmospheric circulation. Diagnosis based on reanalysis and model output demonstrates that the surface PV budget equation is well balanced both in terms of the climate mean and synoptic process, and the surface PV budget in June has a prominent diurnal cycle. The diabatic heating with a minimum in the early morning and a maximum from evening to midnight contributes dominantly to this diurnal cycle. It is further indicated that positive PV generation due to diabatic heating is essential for the formation, development, and movement of the Tibetan Plateau vortex.

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Determination of phthalate esters in breast milk before and after frozen storage in milk storage bags - Ji-Cai Fan; Ren Ren; Hua-Li He; Quan Jin; Shu-Ting Wang (Food Additives & Contaminants: Part A, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

Blood-derived molecular signatures as biomarker panels for the early detection of colorectal cancer - Xia Gan; Ting Wang; Zhi-Yong Chen; Kun-He Zhang (Molecular Biology Reports, 2020)

Chemical composition of Erycibe schmidtii and antiproliferative activity of scopoletin on immature dendritic cells - Wang Ren; Yantang Wang; Qinhui He; Yue Zhou; Chunxin Li; Wenling Wang; Xiao Leng; Ting Zeng; Qiang Zou; Limei Li (Natural Product Research, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

Impact of Maternal Separation on Dopamine System and its Association with Parkinson's Disease - Kai-jie He; Yu-ting Zhang; Shi-zhuang Wei; Shu-min Jiang; Lin Xu; Chao Ren; Fen Wang (NeuroMolecular Medicine, 2020)

Arrival picking method for microseismic phases based on curve fitting - Zhi-Chao Yu; Jing Yu; Fang-Fang Feng; Yu-Yang Tan; Gui-Ting Hou; Chuan He (Applied Geophysics, 2020)

Annual Characteristics, Source Analysis of PM1-Bound Potentially Harmful Elements in the Eastern District of Chengdu, China - Jinjin Wang; Yi Huang; Ting Li; Huibin Shi; Min He; Xin Cheng; Shijun Ni; Chengjiang Zhang (Archives of Environmental Contamination and Toxicology, 2020)

Source apportionment and health risk assessment of air pollution particles in eastern district of Chengdu - Yi Huang; Li Wang; Shipeng Zhang; Meng Zhang; Jinjin Wang; Xin Cheng; Ting Li; Min He; Shijun Ni (Environmental Geochemistry and Health, 2020)

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Tryptophan (Trp) modulates gut homeostasis via aryl hydrocarbon receptor (AhR) - Meige Sun; Ning Ma; Ting He; Lee J. Johnston; Xi Ma (Critical Reviews in Food Science and Nutrition, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Hostaflavanol A, a new anti-inflammatory and antioxidant activities flavanol from the flowers of Hosta plantaginea - Li Yang; Yi-min Lin; Zhong-wei He; Ting-fang Zhang; Yu Li; Xiao-tong Xie; Yi-feng Wu; Jun-wei He (Medicinal Chemistry Research, 2020)

Polyploidization of Plumbago auriculata Lam. in vitro and its characterization including cold tolerance - Yulan Jiang; Shiliang Liu; Ju Hu; Guangti He; Yingqi Liu; Xi Chen; Ting Lei; Qiao Li; Lijuan Yang; Wenji Li; Di Hu; Jiani Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Spent yeast as an efficient medium supplement for fucoxanthin and eicosapentaenoic acid (EPA) production by Phaeodactylum tricornutum - Xue Yuan; Limin Liang; Kui Liu; Lijuan Xie; Luqiang Huang; Wenjin He; Youqiang Chen; Ting Xue (Journal of Applied Phycology, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Complexin I knockout rats exhibit a complex neurobehavioral phenotype including profound ataxia and marked deficits in lifespan - Yang Xu; Xiao-Ming Zhao; Jia Liu; Yang-Yang Wang; Liu-Lin Xiong; Xiu-Ying He; Ting-Hua Wang (Pflügers Archiv - European Journal of Physiology, 2020)

Interactions Between Different Selenium Compounds and Essential Trace Elements Involved in the Antioxidant System of Laying Hens - Xue Lin; Ting Yang; Hua Li; Yinli Ji; Yurong Zhao; Jianhua He (Biological Trace Element Research, 2020)

Phosphate-Solubilizing Pseudomonas sp. Strain P34-L Promotes Wheat Growth by Colonizing the Wheat Rhizosphere and Improving the Wheat Root System and Soil Phosphorus Nutritional Status - Xixi Liu; Xiaoxun Jiang; Xiangyi He; Weirong Zhao; Yuanyuan Cao; Tingting Guo; Ting Li; Haiting Ni; Xinyun Tang (Journal of Plant Growth Regulation, 2019)

Profiling of lysine-acetylated proteins in human urine - Weiwei Qin; Ting Wang; He Huang; Youhe Gao (Science China Life Sciences, 2019)

Deriving water quality criteria for China for the organophosphorus pesticides dichlorvos and malathion - Ting-ting Ding; Ya-hui Zhang; Yan Zhu; Shi-lin Du; Jin Zhang; Ying Cao; Yi-zhe Wang; Gong-ting Wang; Lian-sheng He (Environmental Science and Pollution Research, 2019)

Detection of 20 phthalate esters in breast milk by GC-MS/MS using QuEChERS extraction method - Ji-Cai Fan; Ren Ren; Quan Jin; Hua-Li He; Shu-Ting Wang (Food Additives & Contaminants: Part A, 2019)

Vibralactone Z 4 , the first chain-like vibralactone derivative from cultures of the basidiomycete Boreostereum vibrans - Juan He; Kai-Ting Duan; Zheng-Hui Li; Hong-Lian Ai; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Laboratory study on the influencing factors and their control for the coefficient of restitution during rockfall impacts - Zhong-Min Ji; Zhi-Jian Chen; Qing-He Niu; Tian-Jun Wang; Hao Song; Ting-Hui Wang (Landslides, 2019)

Overexpression of acetyl-CoA carboxylase increases fatty acid production in the green alga Chlamydomonas reinhardtii - Duo Chen; Xue Yuan; Limin Liang; Kui Liu; Haoying Ye; Zhiyu Liu; Yanfei Liu; Luqiang Huang; Wenjin He; Youqiang Chen; Yanding Zhang; Ting Xue (Biotechnology Letters, 2019)

Geosites in Karamay city, Xinjiang Uygur Autonomous Region, northwest China - Jun-Ting Qiu; Liang Qiu; Hong-Xu Mu; Wen-Xin Yang; Feng Chen; Bo-Kun Yan; Jun-Chuan Yu; He-Ming Yang (Geoheritage, 2019)

MicroRNA-494 targets PTEN and suppresses PI3K/AKT pathway to alleviate hypertrophic scar formation - Ting He; Yue Zhang; Yang Liu; Hongtao Wang; Wanfu Zhang; Jiaqi Liu; Na Li; Yan Li; Luxu Wang; Songtao Xie; Dahai Hu (Journal of Molecular Histology, 2019)

Recently duplicated sesterterpene (C25) gene clusters in Arabidopsis thaliana modulate root microbiota - Qingwen Chen; Ting Jiang; Yong-Xin Liu; Haili Liu; Tao Zhao; Zhixi Liu; Xiangchao Gan; Asis Hallab; Xuemei Wang; Juan He; Yihua Ma; Fengxia Zhang; et al. (Science China Life Sciences, 2019)

Biological perchlorate reduction: which electron donor we can choose? - Li He; Yu Zhong; Fubing Yao; Fei Chen; Ting Xie; Bo Wu; Kunjie Hou; Dongbo Wang; Xiaoming Li; Qi Yang (Environmental Science and Pollution Research, 2019)

Characterization of Cucurbita maxima Fruit Metabolomic Profiling and Transcriptome to Reveal Fruit Quality and Ripening Gene Expression Patterns - He-Xun Huang; Ting Yu; Jun-Xing Li; Shu-Ping Qu; Man-Man Wang; Ting-Quan Wu; Yu-Juan Zhong (Journal of Plant Biology, 2019)

Fine mapping of a novel yellow-green leaf 14 (ygl14) mutant in rice - Jia Tan; Ting Zhang; Saisai Xia; Meng Yan; Fengfei Li; Xianchun Sang; Guanghua He; Yinghua Ling (Euphytica, 2019)

Characterization of the Cd(II) and nitrate removal by bacterium Acinetobacter sp. SZ28 under different electron donor conditions - Jun Feng Su; Chun Yu Gao; Ting Lin Huang; Xue Chen Bai; Dong Hui Liang; Lei He (Environmental Science and Pollution Research, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Distribution and partitioning of heavy metals in large anthropogenically impacted river, the Pearl River, China - Silan Liu; Zhongwei Wang; Yuanyuan Zhang; Yulong Liu; Wei Yuan; Ting Zhang; Yujie Liu; Ping Li; Li He; Jiubin Chen (Acta Geochimica, 2019)

Identification of key genes relevant to the prognosis of ER-positive and ER-negative breast cancer based on a prognostic prediction system - Bin Xiao; Jianfeng Hang; Ting Lei; Yongyin He; Zhenzhan Kuang; Li Wang; Lidan Chen; Jia He; Weiyun Zhang; Yang Liao; Zhaohui Sun; Linhai Li (Molecular Biology Reports, 2019)

Clinical relationships between the rs2212020 and rs189897 polymorphisms of the ITGA9 gene and epithelial ovarian cancer - Jinyang Liu; Ting Liu; Lin Liang; Junyu He; Manying Zhang; Yanshan Ge; Shan Liao; Yanhong Zhou; Keqiang Zhang (Journal of Genetics, 2019)

The control of a virtual automatic car based on multiple patterns of motor imagery BCI - Hongtao Wang; Ting Li; Anastasios Bezerianos; Hui Huang; Yuebang He; Peng Chen (Medical & Biological Engineering & Computing, 2019)

Viral metagenomics analysis and eight novel viral genomes identified from the Dushanzi mud volcanic soil in Xinjiang, China - Dan-Ting Yu; Ji-Zheng He; Li-Mei Zhang; Li-Li Han (Journal of Soils and Sediments, 2019)

Comparative study on mitogenomes of green tide algae - Chuner Cai; Feng Liu; Ting Jiang; Lingke Wang; Rui Jia; Lingjie Zhou; Kai Gu; Jianfeng Ren; Peimin He (Genetica, 2018)

Abnormal intrinsic cerebro-cerebellar functional connectivity in un-medicated patients with bipolar disorder and major depressive disorder - Yuan He; Ying Wang; Ting-Ting Chang; Yanbin Jia; Junjing Wang; Shuming Zhong; Huiyuan Huang; Yao Sun; Feng Deng; Xiaoyan Wu; Chen Niu; Li Huang; et al. (Psychopharmacology, 2018)

A new abietane diterpenoid from the roots of Tripterygium regelii - Zhi-Hua Jiang; Yan-Ping Liu; Miao He; Jin-Hua Zhao; Ting-Ting Wang; Xing-Yang Feng; Hao Yue; Ren-Bo An; Yan-Hui Fu (Natural Product Research, 2018)

Improved bioethanol production using CRISPR/Cas9 to disrupt the ADH2 gene in Saccharomyces cerevisiae - Ting Xue; Kui Liu; Duo Chen; Xue Yuan; Jingping Fang; Hansong Yan; Luqiang Huang; Youqiang Chen; Wenjin He (World Journal of Microbiology and Biotechnology, 2018)

Immobilization of Calcined Layered Double Hydroxide into Alginate Hydrogel Beads for PNP and PAP Removal: Kinetics, Isotherms, Thermodynamics, and Mechanism - Ranran Shan; Yuan He; Ting Zi; Guiyan Wang; Xiuyu Liu; Zhe Han; Tao Zhang; Ying Zhu (Water, Air, & Soil Pollution, 2018)

Using Huntingtin Knock-In Minipigs to Fill the Gap Between Mouse Models and Patients with Huntington’s Disease - Xiangqian Liu; Ting Peng; He Li (Neuroscience Bulletin, 2018)

Herp Promotes Degradation of Mutant Huntingtin: Involvement of the Proteasome and Molecular Chaperones - Huanhuan Luo; Liying Cao; Xuan Liang; Ana Du; Ting Peng; He Li (Molecular Neurobiology, 2018)

A corn straw-based diet increases release of inflammatory cytokines in peripheral blood mononuclear cells of dairy cows - Yan-yi Che; Xiao-jing Xia; Bo-ping He; Yuan-yuan Gao; Wen-bo Ren; Hong-tao Liu; Jian-fang Liu; Ting-hao Huang; Wen-yu Han; Lian-cheng Lei (Journal of Zhejiang University-SCIENCE B, 2018)

Cellular stress and redox activity proteins are involved in gastric carcinogenesis associated with Helicobacter pylori infection expressing high levels of thioredoxin-1 - Yan-yan Shi; Jing Zhang; Ting Zhang; Man Zhou; Ye Wang; He-jun Zhang; Shi-gang Ding (Journal of Zhejiang University-SCIENCE B, 2018)

Gene mapping of starch accumulation and premature leaf senescence in the ossac3 mutant of rice - Junyang Huang; Meng Yan; Xiaoyan Zhu; Ting Zhang; WenQiang Shen; Peng Yu; Yantong Wang; Xianchun Sang; Guoling Yu; Bingbing Zhao; Guanghua He (Euphytica, 2018)

Research Progress of Raman Spectroscopy in Drug Analysis - Wen-ting Wang; Hua Zhang; Yuan Yuan; Ya Guo; Shi-xin He (AAPS PharmSciTech, 2018)

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

The complete mitochondrial genomes of green tide algae Ulva flexuosa (Ulvophyceae, Chlorophyta) - Chuner Cai; Lingke Wang; Ting Jiang; Lingjie Zhou; Peimin He; Binghua Jiao (Conservation Genetics Resources, 2018)

Negative regulation of MAVS-mediated innate immune response by ASC - Yue Han; Xiang He; Congwen Wei; Ting Song; Ling Zou; Zihui Li; Jiazhou Ye; Lunan Qi; Lequn Li; Hui Zhong; Feixiang Wu (Molecular and Cellular Biochemistry, 2018)

Production of functional human CuZn-SOD and EC-SOD in bitransgenic cloned goat milk - Rui Lu; Ting Zhang; Daijin Wu; Zhengyi He; Lei Jiang; Minya Zhou; Yong Cheng (Transgenic Research, 2018)

Kaleido: Visualizing Big Brain Data with Automatic Color Assignment for Single-Neuron Images - Ting-Yuan Wang; Nan-Yow Chen; Guan-Wei He; Guo-Tzau Wang; Chi-Tin Shih; Ann-Shyn Chiang (Neuroinformatics, 2018)

Methylation of secreted frizzled-related protein 1 (SFRP1) promoter downregulates Wnt/β-catenin activity in keloids - Jiaqi Liu; Huayu Zhu; Hongtao Wang; Jun Li; Fu Han; Yang Liu; Wanfu Zhang; Ting He; Na Li; Zhao Zheng; Dahai Hu (Journal of Molecular Histology, 2018)

Current State, Distribution, and Sources of Phthalate Esters and Organophosphate Esters in Soils of the Three Gorges Reservoir Region, China - Ming-Jing He; Ting Yang; Zhi-Hao Yang; Hong Zhou; Shi-Qiang Wei (Archives of Environmental Contamination and Toxicology, 2018)

Cross-cultural adaption and psychometric properties of the Chinese version of the Diabetes Behavior Rating Scale: a pilot study - Jing Zhu; Jingjing Xu; Yang Chen; Yong Gu; Li Ji; Yufeng Zhou; Min Zhu; Hsiang-Ting Hsu; Xiaoping Huang; Cuiping Yuan; Yun Shi; Dan Yan; et al. (Science China Life Sciences, 2018)

Physiological and biochemical responses of Camellia sinensis to stress associated with Empoasca vitis feeding - Jian-yu Li; Meng-zhu Shi; Jian-wei Fu; Yue-chao He; David J. Perović; Ting Wang (Arthropod-Plant Interactions, 2018)

Soma Detection in 3D Images of Neurons using Machine Learning Technique - Guan-Wei He; Ting-Yuan Wang; Ann-Shyn Chiang; Yu-Tai Ching (Neuroinformatics, 2018)

Assessment of tidal range energy resources based on flux conservation in Jiantiao Bay, China - Min Du; He Wu; Huaming Yu; Ting Lv; Jiangyu Li; Yujun Yu (Journal of Ocean University of China, 2017)

Occurrence and Distribution of Organophosphate Esters in Surface Soil and Street Dust from Chongqing, China: Implications for Human Exposure - Ming-Jing He; Ting Yang; Zhi-Hao Yang; Qi Li; Shi-Qiang Wei (Archives of Environmental Contamination and Toxicology, 2017)

Orexin Directly Enhances the Excitability of Globus Pallidus Internus Neurons in Rat by Co-activating OX1 and OX2 Receptors - He-Ren Gao; Qian-Xing Zhuang; Yong-Xiao Zhang; Zhang-Peng Chen; Bin Li; Xiao-Yang Zhang; Yi-Ting Zhong; Jian-Jun Wang; Jing-Ning Zhu (Neuroscience Bulletin, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Altered functional connectivity within and between the default model network and the visual network in primary open-angle glaucoma: a resting-state fMRI study - Jieqiong Wang; Ting Li; Peng Zhou; Ningli Wang; Junfang Xian; Huiguang He (Brain Imaging and Behavior, 2017)

Molecular adaptation in the world's deepest‐living animal: Insights from transcriptome sequencing of the hadal amphipod Hirondellea gigas - Yi Lan; Jin Sun; Renmao Tian; Douglas H. Bartlett; Runsheng Li; Yue Him Wong; Weipeng Zhang; Jian‐Wen Qiu; Ting Xu; Li‐Sheng He; Harry G. Tabata; Pei‐Yuan Qian (Molecular Ecology, 2017)
The Challenger Deep in the Mariana Trench is the deepest point in the oceans of our planet. Understanding how animals adapt to this harsh environment characterized by high hydrostatic pressure, food limitation, dark and cold is of great scientific interest. Of the animals dwelling in the Challenger Deep, amphipods have been captured using baited traps. In this study, we sequenced the transcriptome of the amphipod Hirondellea gigas collected at a depth of 10,929 m from the East Pond of the Challenger Deep. Assembly of these sequences resulted in 133,041 contigs and 22,046 translated proteins. Functional annotation of these contigs was made using the go and kegg databases. Comparison of these translated proteins with those of four shallow‐water amphipods revealed 10,731 gene families, of which 5659 were single‐copy orthologs. Base substitution analysis on these single‐copy orthologs showed that 62 genes are positively selected in H. gigas , including genes related to β‐alanine biosynthesis, energy metabolism and genetic information processing. For multiple‐copy orthologous genes, gene family expansion analysis revealed that cold‐inducible proteins (i.e., transcription factors II A and transcription elongation factor 1) as well as zinc finger domains are expanded in H. gigas . Overall, our results indicate that genetic adaptation to the hadal environment by H. gigas may be mediated by both gene family expansion and amino acid substitutions of specific proteins.

Derivation of Haploid Neurons from Mouse Androgenetic Haploid Embryonic Stem Cells - He Xu; Chunmei Yue; Ting Zhang; Yuanyuan Li; Ao Guo; Jiaoyang Liao; Gang Pei; Jinsong Li; Naihe Jing (Neuroscience Bulletin, 2017)

Updates on East Asian Asterostroma (Russulales, Basidiomycota): new species and new records from Thailand and China - Shi-Liang Liu; Yan Tian; Ting Nie; Anan Thawthong; Kevin D. Hyde; Ling-Ling Xu; Shuang-Hui He (Mycological Progress, 2017)

DNA hypermethylation of sFRP5 contributes to indoxyl sulfate-induced renal fibrosis - Yanlin Yu; Xu Guan; Ling Nie; Yong Liu; Ting He; Jiachuan Xiong; Xinli Xu; Yan Li; Ke Yang; Yiqin Wang; Yunjian Huang; Bing Feng; et al. (Journal of Molecular Medicine, 2017)

Non-viral and viral delivery systems for CRISPR-Cas9 technology in the biomedical field - Zhi-Yao He; Ke Men; Zhou Qin; Yang Yang; Ting Xu; Yu-Quan Wei (Science China Life Sciences, 2017)

Epigenetic synergism between interleukin-4 and aryl-hydrocarbon receptor in human macrophages - Wei-Ting Liao; Jian-He Lu; Wei-Ting Wang; Chih-Hsing Hung; Chau-Chyun Sheu; Shau-Ku Huang (Journal of Molecular Medicine, 2017)

Nr3C1-Bhlhb2 Axis Dysregulation Is Involved in the Development of Attention Deficit Hyperactivity - Li Hui Wu; Wei Cheng; Mei Yu; Bao Mei He; Hui Sun; Qi Chen; Yi Wei Dong; Xiao Ting Shao; Qian Qian Cai; Min Peng; Xing Zhong Wu (Molecular Neurobiology, 2017)

Unique community structure of viruses in a glacier soil of the Tianshan Mountains, China - Li-Li Han; Dan-Ting Yu; Li-Mei Zhang; Jun-Tao Wang; Ji-Zheng He (Journal of Soils and Sediments, 2017)

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

Transiently expressed pattern during myogenesis and candidate miRNAs of Tmem8C in goose - KE HE; TING REN; SONGHUI ZHU; SHIRI LIANG; AYONG ZHAO (Journal of Genetics, 2017)

Antioxidant and antidiabetic properties of tartary buckwheat rice flavonoids after in vitro digestion - Tao Bao; Ye Wang; Yu-ting Li; Vemana Gowd; Xin-he Niu; Hai-ying Yang; Li-shui Chen; Wei Chen; Chong-de Sun (Journal of Zhejiang University-SCIENCE B, 2016)

Resveratrol inhibits renal interstitial fibrosis in diabetic nephropathy by regulating AMPK/NOX4/ROS pathway - Ting He; Jiachuan Xiong; Ling Nie; Yanlin Yu; Xu Guan; Xinli Xu; Tangli Xiao; Ke Yang; Liang Liu; Daohai Zhang; Yunjian Huang; Jingbo Zhang; et al. (Journal of Molecular Medicine, 2016)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Levels of five metals in male hair from urban and rural areas of Chongqing, China - Ming-Jing He; Shi-Qiang Wei; Yu-Xin Sun; Ting Yang; Qi Li; Deng-Xiang Wang (Environmental Science and Pollution Research, 2016)

Rockburst Generation in Discontinuous Rock Masses - Ben-Guo He; Ravit Zelig; Yossef H. Hatzor; Xia-Ting Feng (Rock Mechanics and Rock Engineering, 2016)

Ethanol Increases Mechanical Pain Sensitivity in Rats via Activation of GABAA Receptors in Medial Prefrontal Cortex - Kai-Wen Geng; Ting He; Rui-Rui Wang; Chun-Li Li; Wen-Jun Luo; Fang-Fang Wu; Yan Wang; Zhen Li; Yun-Fei Lu; Su-Min Guan; Jun Chen (Neuroscience Bulletin, 2016)

Erratum to: Initiation and evolution of the South China Sea: an overview - Wei-dong Sun; Chiou-ting Lin; Chan-chan Zhang; Yong-bin Hu; Ming-xing Ling; Xing Ding; Cong-ying Li; He Li; Kai Wu; Wei-ming Fan (Acta Geochimica, 2016)

Nuclear genetic variation of Rosa odorata var. gigantea (Rosaceae): population structure and conservation implications - Jing Meng; Shui-Lian He; De-Zhu Li; Ting-Shuang Yi (Tree Genetics & Genomes, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Ketamine Affects the Neurogenesis of the Hippocampal Dentate Gyrus in 7-Day-Old Rats - He Huang; Cun-Ming Liu; Jie Sun; Ting Hao; Chun-Mei Xu; Dan Wang; Yu-Qing Wu (Neurotoxicity Research, 2016)

PEGylation of cytochrome c at the level of lysine residues mediated by a microbial transglutaminase - Jian Qin Zhou; Ting He; Jian Wen Wang (Biotechnology Letters, 2016)

The pharmacokinetics of vancomycin in patients with severe acute pancreatitis - Juan He; En-Qiang Mao; Jing Feng; Hui-Ting Jiang; Wan-Hua Yang; Er-Zhen Chen (European Journal of Clinical Pharmacology, 2016)

Changing roles of ammonia-oxidizing bacteria and archaea in a continuously acidifying soil caused by over-fertilization with nitrogen - He Song; Zhao Che; Wenchao Cao; Ting Huang; Jingguo Wang; Zhaorong Dong (Environmental Science and Pollution Research, 2016)

Origins of Early Mesozoic granitoids and their enclaves from West Kunlun, NW China: implications for evolving magmatism related to closure of the Paleo-Tethys ocean - Chao Wang; Liang Liu; Fawna Korhonen; Wen-Qiang Yang; Yu-Ting Cao; Shi-Ping He; Xiao-Hui Zhu; Wen-Tian Liang (International Journal of Earth Sciences, 2016)

Gene expression profile analysis indicate SEPALLATA3 and AGL15 potentially involved in arabidopsis silique dehiscence by regulating glycosyl hydrolase - Xingshan Jiang; Hanjun He; Ting Wang; Xiaojing Wang; Hong Wu (Journal of Plant Biology, 2016)

GOLPH3 Mediated Golgi Stress Response in Modulating N2A Cell Death upon Oxygen-Glucose Deprivation and Reoxygenation Injury - Ting Li; Hong You; Xiaoye Mo; Wenfang He; Xiangqi Tang; Zheng Jiang; Shiyu Chen; Yang Chen; Jie Zhang; Zhiping Hu (Molecular Neurobiology, 2016)

Gabapentinoid Insensitivity after Repeated Administration is Associated with Down-Regulation of the α2δ-1 Subunit in Rats with Central Post-Stroke Pain Hypersensitivity - Yan Yang; Fei Yang; Fan Yang; Chun-Li Li; Yan Wang; Zhen Li; Yun-Fei Lu; Yao-Qing Yu; Han Fu; Ting He; Wei Sun; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2016)

Influence of the Ring Size on the Binding Ability of FTO Investigated by Fluorescence Spectroscopy - Wu He; Zhigang Li; Lingling Yang; Qingwei Jiang; Ting Ren; Lijiao Zhang; Zhenhua Shen; Qinghua Yang; Ruiyong Wang; Junbiao Chang (Journal of Fluorescence, 2015)

An epimer of deoxynivalenol: purification and structure identification of 3- epi -deoxynivalenol - Jian Wei He; Raymond Yang; Ting Zhou; Greg J. Boland; Peter M. Scott; Genevieve S. Bondy (Food Additives & Contaminants: Part A, 2015)

Toward neurobiological characterization of functional homogeneity in the human cortex: regional variation, morphological association and functional covariance network organization - Lili Jiang; Ting Xu; Ye He; Xiao-Hui Hou; Jinhui Wang; Xiao-Yan Cao; Gao-Xia Wei; Zhi Yang; Yong He; Xi-Nian Zuo (Brain Structure and Function, 2015)

Bacterial communities of Beijing surface waters as revealed by 454 pyrosequencing of the 16S rRNA gene - Yu-Mei Wei; Jing-Qi Wang; Ting-Ting Liu; Wei-Wen Kong; Nan Chen; Xiao-Qing He; Yi Jin (Environmental Science and Pollution Research, 2015)

HAP1 helps to regulate actin-based transport of insulin-containing granules in pancreatic β cells - Zhiyong Wang; Ting Peng; Hongnian Wu; Jun He; He Li (Histochemistry and Cell Biology, 2015)

Simulation of long-term spring wheat yields, soil organic C, N and water dynamics using DSSAT-CSM in a semi-arid region of the Canadian prairies - Zhuo Ting Li; J. Y. Yang; W. N. Smith; C. F. Drury; R. L. Lemke; B. Grant; W. T. He; Xiao Gang Li (Nutrient Cycling in Agroecosystems, 2015)

Inhibition of Transglutaminase Exacerbates Polyglutamine-Induced Neurotoxicity by Increasing the Aggregation of Mutant Ataxin-3 in an SCA3 Drosophila Model - Yunting Lin; Hua He; Yingying Luo; Ting Zhu; Ranhui Duan (Neurotoxicity Research, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Phylogenetic analysis of STK gene family and Usp domain in maize - Ting Zhou; Mingxia Fan; Muhammad Irfan; He Wang; Dongxu Wang; Lin Wang; Chunyu Zhang; Lin Feng (Molecular Biology Reports, 2014)

Endoplasmic Reticulum Protein 29 Protects Cortical Neurons From Apoptosis and Promoting Corticospinal Tract Regeneration to Improve Neural Behavior via Caspase and Erk Signal in Rats with Spinal Cord Transection - Ran Liu; Wei Zhao; Qi Zhao; Su-Juan Liu; Jia Liu; Mu He; Yang Xu; Wei Wang; Wei Liu; Qing-Jie Xia; Cheng-Yun Li; Ting-Hua Wang (Molecular Neurobiology, 2014)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Stratigraphic framework and microfacies of the Triassic Lower Karamay Formation in districts I, III, NW Junggar, China - Miao He; Zhenkui Jin; Tingdong Li; Xiujuan Guo; Ting Yang (Journal of Earth Science, 2014)

SNAP25 Ameliorates Sensory Deficit in Rats with Spinal Cord Transection - Wei Wang; Fang Wang; Jia Liu; Wei Zhao; Qi Zhao; Mu He; Bao-Jiang Qian; Yang Xu; Ran Liu; Su-Juan Liu; Wei Liu; Jin Liu; et al. (Molecular Neurobiology, 2014)

Rapamycin promotes podocyte autophagy and ameliorates renal injury in diabetic mice - Tangli Xiao; Xu Guan; Ling Nie; Song Wang; Lei Sun; Ting He; Yunjian Huang; Jingbo Zhang; Ke Yang; Junping Wang; Jinghong Zhao (Molecular and Cellular Biochemistry, 2014)

Detection of cytokines in supernatant from hematopoietic stem/progenitor cells co-cultured with mesenchymal stem cells and endothelial progenitor cells - Yue Chi; Yufen Jin; Ziyang He; Ting Yu (Cell and Tissue Banking, 2014)

In Vitro Biocompatibility and Antibacterial Efficacy of a Degradable Poly(l-lactide-co-epsilon-caprolactone) Copolymer Incorporated with Silver Nanoparticles - Meghan E. Samberg; Peter Mente; Ting He; Martin W. King; Nancy A. Monteiro-Riviere (Annals of Biomedical Engineering, 2014)

Study of GOLPH3: a Potential Stress-Inducible Protein from Golgi Apparatus - Ting Li; Hong You; Jie Zhang; Xiaoye Mo; Wenfang He; Yang Chen; Xiangqi Tang; Zheng Jiang; Ranran Tu; Liuwang Zeng; Wei Lu; Zhiping Hu (Molecular Neurobiology, 2014)

A normalized wavefield separation cross-correlation imaging condition for reverse time migration based on Poynting vector - Ting Chen; Bing-Shou He (Applied Geophysics, 2014)

Visualizing the microtubule-associated protein tau in the nucleus - Jing Lu; Ting Li; RongQiao He; Perry F. Bartlett; Jürgen Götz (Science China Life Sciences, 2014)

Uric formaldehyde levels are negatively correlated with cognitive abilities in healthy older adults - Jing Yu; Tao Su; Ting Zhou; Yingge He; Jing Lu; Juan Li; Rongqiao He (Neuroscience Bulletin, 2014)

Genetic variability of MHC class II DQB exon 2 alleles in yak (Bos grunniens) - Yiduo He; Dongmei Xi; Jing Leng; Tao Qian; Dan Jin; Ting Chen; Chunling Yang; Tiantian Hao; Zaiqing Yang; Weidong Deng (Molecular Biology Reports, 2014)

Catastrophe theory to assess water security and adaptation strategy in the context of environmental change - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Xia Xing-hui; He Rui-min; Shang Man-ting (Mitigation and Adaptation Strategies for Global Change, 2014)

Silencing the glycerol-3-phosphate dehydrogenase gene in Saccharomyces cerevisiae results in more ethanol being produced and less glycerol - Wenjin He; Shichao Ye; Ting Xue; Shengyan Xu; Weiyan Li; Jihua Lu; Luoyuan Cao; Bingying Ye; Youqiang Chen (Biotechnology Letters, 2014)

Numerical simulation of surface and downhole deformation induced by hydraulic fracturing - Yi-Yuan He; Bao-Ping Zhang; Yu-Ting Duan; Cheng-Jin Xue; Xin Yan; Chuan He; Tian-Yue Hu (Applied Geophysics, 2014)

Chondrogenic differentiation and three dimensional chondrogenesis of human adipose-derived stem cells induced by engineered cartilage-derived conditional media - Hengyun Sun; Yu Liu; Ting Jiang; Xia Liu; Aijuan He; Jie Li; Wenjie Zhang; Wei Liu; Yilin Cao; Guangdong Zhou (Tissue Engineering and Regenerative Medicine, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

Left hemiparalexia of Chinese characters: neglect dyslexia or disruption of pathway of visual word form processing? - Wenchao Yi; Ting Wu; Wei Chen; Ti-fei Yuan; Benyan Luo; Chunlei Shan; Jianan Li; Sheng He; Xuchu Weng (Brain Structure and Function, 2014)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Introgression of bacterial wilt resistance from eggplant to potato via protoplast fusion and genome components of the hybrids - Yan Yu; Wenxuan Ye; Li He; Xingkui Cai; Ting Liu; Jun Liu (Plant Cell Reports, 2013)

Advances in monoclonal antibody application in myocarditis - Li-na Han; Shuang He; Yu-tang Wang; Li-ming Yang; Si-yu Liu; Ting Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Myeloperoxidase Activity and Its Corresponding mRNA Expression as well as Gene Polymorphism in the Population Living in the Coal-Burning Endemic Fluorosis Area in Guizhou of China - Ting Zhang; Ke-Ren Shan; Xi Tu; Yan He; Jin-Jing Pei; Zhi-Zhong Guan (Biological Trace Element Research, 2013)

Dynamic mechanism and present situation of rural settlement evolution in China - Guohua Zhou; Yanhua He; Chengli Tang; Tao Yu; Guozhen Xiao; Ting Zhong (Journal of Geographical Sciences, 2013)

Pharmacokinetic study of arctigenin in rat plasma and organ tissue by RP-HPLC method - Fan He; De-Qiang Dou; Qiang Hou; Yu Sun; Ting-Guo Kang (Natural Product Research, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Factors influencing sexual cannibalism and its benefit to fecundity and offspring survival in the wolf spider Pardosa pseudoannulata (Araneae: Lycosidae) - Lingbing Wu; Huaping Zhang; Ting He; Zeliang Liu; Yu Peng (Behavioral Ecology and Sociobiology, 2013)

Hydrogen sulfide alleviates aluminum toxicity in barley seedlings - Juan Chen; Wen-Hua Wang; Fei-Hua Wu; Chun-Yan You; Ting-Wu Liu; Xue-Jun Dong; Jun-Xian He; Hai-Lei Zheng (Plant and Soil, 2013)

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2012)

Selection and validation of reference genes for studying stress-related agarwood formation of Aquilaria sinensis - Zhi-Hui Gao; Jian-He Wei; Yun Yang; Zheng Zhang; Wen-Ting Zhao (Plant Cell Reports, 2012)

Use of multi-electrode array recordings in studies of network synaptic plasticity in both time and space - Ming-Gang Liu; Xue-Feng Chen; Ting He; Zhen Li; Jun Chen (Neuroscience Bulletin, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Preparation and Biological Effect of Nucleotide-Capped CdSe/ZnS Quantum Dots on Tetrahymena thermophila - Qi Xiao; Ting Qiu; Shan Huang; Yi Liu; Zhike He (Biological Trace Element Research, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Genetic diversity of Centella asiatica in China analyzed by inter-simple sequence repeat (ISSR) markers: combination analysis with chemical diversity - Xiao-Gang Zhang; Ting Han; Zhi-Gao He; Qiao-Yan Zhang; Lei Zhang; Khalid Rahman; Lu-Ping Qin (Journal of Natural Medicines, 2012)

Rickettsia-like organism infection associated with mass mortalities of blood clam, Tegillarca granosa, in the Yueqing Bay in China - Zewen Zhu; Ting Xu; Zhongyang He; Xinzhong Wu; Liuji Wu; Qingguo Meng; Jiaqing Huang (Acta Oceanologica Sinica, 2012)

Clostridium beijerinckii mutant obtained by atmospheric pressure glow discharge producing high proportions of butanol and solvent yields - Ting Guo; Yan Tang; Yong-lan Xi; Ai-yong He; Bai-jun Sun; Hao Wu; Da-feng Liang; Min Jiang; Ping-kai Ouyang (Biotechnology Letters, 2011)

Effect of diindolylmethane on Ca2+ movement and viability in HA59T human hepatoma cells - Jin-Shiung Cheng; Su-Shung Shu; Chun-Chi Kuo; Chiang-Ting Chou; Wei-Lun Tsai; Yi-Chien Fang; Li-Ni Kuo; Jeng-Hsien Yeh; Wei-Chuan Chen; Jau-Min Chien; Ti Lu; Chih-Chuan Pan; et al. (Archives of Toxicology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

A strategy to deal with water crisis under climate change for mainstream in the middle reaches of Yellow River - Xiao-jun Wang; Jian-yun Zhang; Rui-min He; ElMahdi Amgad; ElSawah Sondoss; Man-ting Shang (Mitigation and Adaptation Strategies for Global Change, 2011)

A regional ocean reanalysis system for coastal waters of China and adjacent seas - Guijun Han; Wei Li; Xuefeng Zhang; Dong Li; Zhongjie He; Xidong Wang; Xinrong Wu; Ting Yu; Jirui Ma (Advances in Atmospheric Sciences, 2011)

VP15R from infectious spleen and kidney necrosis virus is a non-muscle myosin-II-binding protein - Xiaopeng Xu; Ting Lin; Lichao Huang; Shaoping Weng; Wei Wei; Zhongsheng Li; Ling Lü; Zhijian Huang; Jianguo He (Archives of Virology, 2011)

Application of Hyperion data to land degradation mapping in the Hengshan region of China - Jian Wu; Yaolin Liu; Jing Wang; Ting He (International Journal of Remote Sensing, 2010)

Groundwater environmental capacity and its evaluation index - Li Ting Xing; Qiang Wu; Chun He Ye; Nan Ye (Environmental Monitoring and Assessment, 2010)

Identification of the VP92R gene from infectious spleen and kidney necrosis virus - Xiaopeng Xu; Qingxia Lu; Rui Wang; Ting Lin; Shaoping Weng; Ling Lu; Zhongsheng Li; Xiaoqiang Yu; Junliang Tang; Jianguo He (Virus Genes, 2010)

Sevoflurane postconditioning reduces myocardial reperfusion injury in rat isolated hearts via activation of PI3K/Akt signaling and modulation of Bcl-2 family proteins - Li-na Yu; Jing Yu; Feng-jiang Zhang; Mei-juan Yang; Ting-ting Ding; Jun-kuan Wang; Wei He; Tao Fang; Gang Chen; Min Yan (Journal of Zhejiang University-SCIENCE B, 2010)

Cordycepin induces apoptosis by enhancing JNK and p38 kinase activity and increasing the protein expression of Bcl-2 pro-apoptotic molecules - Wei He; Mei-fang Zhang; Jun Ye; Ting-ting Jiang; Xu Fang; Ying Song (Journal of Zhejiang University-SCIENCE B, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

Cr(III) oxidation coupled with Mn(II) bacterial oxidation in the environment - Ji-Zheng He; You-Ting Meng; Yuan-Ming Zheng; Li-Mei Zhang (Journal of Soils and Sediments, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Extended expression of B-class MADS-box genes in the paleoherb Asarum caudigerum - Yin-He Zhao; Michael Möller; Jun-Bo Yang; Ting-Song Liu; Jin-Feng Zhao; Li-Na Dong; Jin-Peng Zhang; Cheng-Yun Li; Guo-Ying Wang; De-Zhu Li (Planta, 2010)

Prevalence, genetic diversity, and antimicrobial susceptibility profiles of Staphylococcus aureus isolated from bovine mastitis in Zhejiang Province, China - Jian-ping Li; Hai-jian Zhou; Lin Yuan; Ting He; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2009)

Sample clean-up methods, immunoaffinity chromatography and solid phase extraction, for determination of deoxynivalenol and deepoxy deoxynivalenol in swine serum - Jianwei He; Xiu-Zhen Li; Ting Zhou (Mycotoxin Research, 2009)

Expression of fasciculation and elongation protein zeta-1 (FEZ1) in cultured rat neonatal astrocytes - Jianghong He; Jun Liu; Zhijun Zhang; Maomin Sun; Ting Zhu; Chunlin Xia (Molecular and Cellular Biochemistry, 2009)

Proliferating cell nuclear antigen destabilizes c-Abl tyrosine kinase and regulates cell apoptosis in response to DNA damage - Xiang He; Congwen Wei; Ting Song; Jing Yuan; Yanhong Zhang; Qingjun Ma; Wei Shi; Hui Zhong (Apoptosis, 2009)

Interspecific and intraspecific comparisons of ejaculates in the cotton bollworm Helicoverpa armigera and the tobacco budworm H. assulta - Zhao-Qian Teng; Qian He; Hui-Ting Li; Qing-Wen Zhang (Journal of Ethology, 2009)

Effect of calmidazolium on [Ca2+]i and viability in human hepatoma cells - Wei-Chuan Liao; Chorng-Chih Huang; He-Hsiung Cheng; Jue-Long Wang; Ko-Long Lin; Jin-Shiung Cheng; Kuo-Liang Chai; Pei-Te Hsu; Jeng-Yu Tsai; Yi-Chien Fang; Yih-Chau Lu; Hong-Tai Chang; et al. (Archives of Toxicology, 2009)

The distribution of HBV genotypes and clinical significance in familial clustering in an infected population with unfavorable prognosis - Jinfeng Liu; Yongqin Li; Tianyan Chen; Yuan Yang; Ke Wang; Yingli He; Qian Yang; Feng Ye; Yan Jin; Ting Qiu; Shumei Lin; Min Liu; et al. (Archives of Virology, 2008)

Microbial activity and community diversity in a variable charge soil as affected by cadmium exposure levels and time - Jia-li Shentu; Zhen-li He; Xiao-e Yang; Ting-qiang Li (Journal of Zhejiang University-SCIENCE B, 2008)

Dynamic Changes of Sandy Land in Northwest of Beijing, China - Jing Wang; Ting He; Xudong Guo; Aixia Liu; Qing Zhou (Environmental Monitoring and Assessment, 2006)